Cellulose microfiber and method for producing the same, nonwoven fabric, and fiber-reinforced resin and method for producing the same
By controlling the shape parameters and chemical modification of cellulose microfibers and combining hot press synthesis technology, the shortcomings of cellulose microfibers and resin composites in terms of strength, elastic modulus and strain damage are solved, and high-performance fiber reinforced resins are realized. preparation.
Patent Information
- Application Number
- CN202280051195.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-11-12
- Filing Date
- 2022-07-27
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-07-27
AI Technical Summary
In the prior art, cellulose microfibers and resin composites have poor performance in strength, elastic modulus and strain failure, and have insufficient heat resistance during melt-kneading, making it difficult to meet high levels of strength and elastic properties at the same time.
By controlling the shape parameters of cellulose microfibers, such as fiber length, fiber diameter, fine fiber area ratio and fibrillation rate, combined with chemical modification and multi-stage microfinement treatment, cellulose microfibers that meet specific parameters are prepared and combined with resin Perform hot pressing synthesis to form a high-performance fiber reinforced resin.
The strength, elastic modulus and failure strain of cellulose microfibers in fiber-reinforced resin are achieved, and the mechanical properties and dimensional stability of the material are improved.
Smart Images

Figure CN117751218B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to cellulose microfibers and a method for producing the same, a nonwoven fabric, and a fiber-reinforced resin using the cellulose microfibers and a method for producing the same. Background Art
[0002] In recent years, cellulose fibers, especially cellulose microfibers, have attracted attention as plant resources that can be effectively utilized in a wide range of application fields and as materials with high elastic modulus and excellent thermal dimensional stability, such as composite fillers for automobiles or core materials suitable for fiber reinforced plastics (FRP) from the perspective of environmental protection and performance with various characteristics. However, the resin mixed with cellulose microfibers is highly brittle and can be broken even by a small change, so there are still problems from the perspective of strength and impact resistance.
[0003] Patent Document 1 describes a technique for improving flexural strength and flexural modulus while maintaining impact resistance by compounding a resin having a specific relative viscosity and carboxyl terminal concentration with acetylated microfibrillated cellulose fibers.
[0004] Patent Document 2 describes microfibrillated cellulose having an average fiber length of 0.02 to 3.0 mm, an average fiber diameter of 0.1 μm or more, and a fibrillation ratio of 1.0% or more, and describes a technique for improving the flexural modulus of a fiber-reinforced composite resin by subjecting the microfibrillated cellulose to a hydrophobic treatment and then mixing it with a resin.
[0005] Patent Document 3 shows a composite material composed of three components: microfibrillated cellulose, an elastomer, and a resin, and describes a technique for improving impact resistance by using a core-shell elastomer having a shell portion reactive with hydroxyl groups of cellulose.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: International Publication No. 2016 / 148233
[0009] Patent Document 2: International Publication No. 2019 / 230573
[0010] Patent Document 3: Japanese Patent Application Publication No. 2010-31093 Summary of the invention
[0011] Problems to be solved by the invention
[0012] However, the technology described in Patent Document 1 uses pulp that contains a certain amount of lignin, called wood cellulose, and therefore has problems with heat resistance during melt kneading. In addition, since fiber opening is performed under constrained shearing such as in the kneading and extrusion process, sufficient fiber opening cannot occur to express performance, and even if the properties of the resin are improved, the strength and elastic modulus of the composite of the resin and cellulose are still insufficient. In addition, Patent Document 2 does not fully study the technology for satisfying strength, elastic modulus, and breaking strain at a high level. As such, fiber-reinforced resins that can simultaneously satisfy strength, elastic modulus, and breaking strain at a high level have not been obtained in the prior art.
[0013] Therefore, an object of the present invention is to provide a cellulose microfiber capable of obtaining a fiber-reinforced resin having excellent strength, elastic modulus, and breaking strain.
[0014] Means for solving problems
[0015] The present disclosure includes the following items. [1]
[0017] A cellulose microfiber, wherein the fiber meets all of the following parameters when measured by an automatic fiber shape analyzer:
[0018] (i) the length-weighted average fiber length of fibers having a fiber length of 100 μm or more is 110 μm or more and 500 μm or less,
[0019] (ii) the average fiber diameter is 42.5 μm or less,
[0020] (iii) the fine fiber area ratio is 90% or less,
[0021] (iv) among fibers having a fiber length of less than 100 μm, the number frequency of fibers having a fiber length of 20 μm or more and 56 μm or less is 97% or less,
[0022] (v) the number frequency of fibers having a fiber length of 411 μm or longer among fibers having a fiber length of 100 μm or longer is 54% or less, and
[0023] (vi) The average fiber diameter calculated by specific surface area is 20 to 150 nm. [2]
[0025] The cellulose microfibers according to item 1, wherein the average fiber length is from 110 μm to 500 μm. [3]
[0027] The cellulose microfibers according to item 1 or 2, wherein the cellulose microfibers satisfy all of the following parameters when measured by an automatic fiber shape analyzer:
[0028] (i) the average fiber length is not less than 130 μm and not more than 350 μm,
[0029] (ii) the average fiber diameter is 35 μm or less,
[0030] (iii) the fine fiber area ratio is 75% or less,
[0031] (iv) among fibers having a fiber length of less than 100 μm, the number frequency of fibers having a fiber length of 20 μm or more and 56 μm or less is 75% or less,
[0032] (v) among fibers having a fiber length of 100 μm or more, the number frequency of fibers having a fiber length of 411 μm or more is 30% or less, and
[0033] (vi) The fibrillation rate is 5% or less. [4]
[0035] The cellulose fine fibers according to any one of items 1 to 3, wherein the glucose content in constituent sugar analysis is 90% by mass or more. [5]
[0037] The cellulose microfibers according to any one of items 1 to 4, wherein the cellulose microfibers have an occupied area of less than 15 μm in a scanning electron microscope (SEM) image of the surface of a sample obtained by casting and drying a 5 ppm by mass DMSO dispersion of the cellulose microfibers. 2 The ratio of the total area occupied by the ultrafine fibers to the total area occupied by the cellulose microfibers is 10% to 80%. [6]
[0039] The cellulose microfibers according to any one of items 1 to 5, which have a cellulose I-type crystal structure. [7]
[0041] The cellulose microfibers according to any one of items 1 to 6, wherein the degree of crystallinity is 60% or more. [8]
[0043] The cellulose fine fibers according to any one of items 1 to 7, wherein the halogen content is 250 ppm by mass or less. [9]
[0045] The cellulose fine fibers according to any one of items 1 to 8, wherein the degree of whiteness is 50% or more.
[10]
[0047] The cellulose fine fibers according to any one of items 1 to 9, wherein the length-weighted average fiber length of fibers having a fiber length of 100 μm or longer is 130 μm or longer and 350 μm or shorter.
[11]
[0049] The cellulose fine fibers according to any one of items 1 to 10, wherein the number frequency of fibers having a fiber length of 411 μm or longer among fibers having a fiber length of 100 μm or longer is 30% or less.
[12]
[0051] The cellulose microfibers according to any one of items 1 to 11, wherein the microfiber area ratio is 75% or less.
[13]
[0053] The cellulose microfibers according to any one of items 1 to 12, wherein the number frequency of fibers having a fiber length of 20 μm to 56 μm among fibers having a fiber length of less than 100 μm is 30% to 75%.
[14]
[0055] The cellulose fine fibers according to any one of items 1 to 13, wherein the fibrillation rate is 5% or less.
[15]
[0057] The cellulose microfibers according to any one of items 1 to 14, wherein at least the surface of the cellulose microfibers is chemically modified.
[16]
[0059] The cellulose microfibers according to Item 15, wherein the chemical modification is acetylation and the degree of acetylation is 0.5 to 1.3.
[17]
[0061] The cellulose microfibers according to any one of items 1 to 16, further satisfying the following parameters in measurement by an automatic fiber shape analyzer:
[0062] (iv) among fibers having a fiber length of less than 100 μm, the number frequency of fibers having a fiber length of 20 μm or more and 56 μm or less is 30% or more and 97% or less, and
[0063] (vi) The fibrillation rate is 5% or less.
[18]
[0065] A method for producing cellulose microfibers, which is the method for producing cellulose microfibers according to any one of items 1 to 17, wherein:
[0066] The halogen content of the cellulose microfibers is 250 ppm by mass or less,
[0067] The above method includes the step of fibrillating a cellulose raw material having a halogen content of 300 mass ppm or less.
[19]
[0069] A fiber-reinforced resin comprising the cellulose microfibers according to any one of items 1 to 17 and a resin.
[20]
[0071] The fiber-reinforced resin according to item 19, wherein the resin has a melting point of 200° C. or higher. [twenty one]
[0073] The fiber-reinforced resin according to item 19 or 20, comprising 1 mass % or more of the above-mentioned cellulose fine fibers. [twenty two]
[0075] A nonwoven fabric comprising the cellulose fine fibers according to any one of items 1 to 17. [twenty three]
[0077] The nonwoven fabric according to Item 22, comprising 50% by mass or more of synthetic fibers having a melting point of 300° C. or lower. [twenty four]
[0079] The nonwoven fabric according to Item 22 or 23, comprising 1 mass % or more of the above-mentioned cellulose fine fibers.
[25]
[0081] A fiber-reinforced resin comprising the nonwoven fabric according to any one of items 22 to 24 and a resin impregnated in the nonwoven fabric.
[26]
[0083] A method for producing a fiber-reinforced resin, comprising:
[0084] The method comprises the step of hot-pressing the nonwoven fabric according to any one of items 22 to 24 to obtain a fiber-reinforced resin.
[0085] The nonwoven fabric includes synthetic fibers, and the heat pressing is performed at a temperature not lower than the melting point of the synthetic fibers.
[0086] Effects of the Invention
[0087] The cellulose microfibers according to one embodiment of the present invention can provide a cellulose microfiber capable of obtaining a fiber-reinforced resin having excellent strength, elastic modulus, and breaking strain. BRIEF DESCRIPTION OF THE DRAWINGS
[0088] Figure 1This is an explanatory diagram of the calculation method of the IR index 1730 and the IR index 1030.
[0089] Figure 2 This is a diagram for explaining an example of arrangement of blades and grooves of a disc refiner.
[0090] Figure 3 This is a diagram for explaining the blade width, groove width, and distance between blades of a disc refiner. DETAILED DESCRIPTION
[0091] Hereinafter, exemplary embodiments of the present invention (hereinafter also referred to as the present embodiment) will be described, but the present invention is not limited to these embodiments and can be implemented with various modifications within the scope of the gist thereof.
[0092] 《Cellulose microfiber》
[0093] <Shape of cellulose microfibers>
[0094] In one embodiment, the cellulose microfibers satisfy all of the following parameters when measured by an automatic fiber shape analyzer:
[0095] (i) the length-weighted average fiber length of fibers having a fiber length of 100 μm or more is 110 μm or more and 500 μm or less,
[0096] (ii) the average fiber diameter is 42.5 μm or less,
[0097] (iii) the fine fiber area ratio is 90% or less,
[0098] (iv) among fibers having a fiber length of less than 100 μm, the number frequency of fibers having a fiber length of 20 μm or more and 56 μm or less is 97% or less, and
[0099] (v) Among fibers having a fiber length of 100 μm or longer, the number frequency of fibers having a fiber length of 411 μm or longer is 54% or less.
[0100] In one embodiment, the average fiber length of the cellulose microfibers is 110 μm or more and 500 μm or less.
[0101] In one embodiment, the cellulose microfibers satisfy all of the following parameters in an automatic fiber shape analyzer:
[0102] (i) the average fiber length is not less than 130 μm and not more than 350 μm,
[0103] (ii) the average fiber diameter is 35 μm or less,
[0104] (iii) the microfiber area ratio is 75% or less,
[0105] (iv) among fibers having a fiber length of less than 100 μm, the number frequency of fibers having a fiber length of 20 μm or more and 56 μm or less is 75% or less,
[0106] (v) among fibers having a fiber length of 100 μm or more, the number frequency of fibers having a fiber length of 411 μm or more is 30% or less, and
[0107] (vi) The fibrillation rate is 5% or less.
[0108] In one embodiment, cellulose microfibers are obtained by microfiberizing cellulose raw material using at least one physical means, and are generally referred to as cellulose nanofibers, CNFs, CeNFs, microfiberized cellulose fibers, and the like.
[0109] In one embodiment, the cellulose microfibers are chemically modified cellulose microfibers. In the present disclosure, chemically modified cellulose microfibers refer to cellulose microfibers in which at least a portion of the three hydroxyl groups contained in the pyranose glucose unit in the skeleton of the cellulose molecule present in the cellulose microfibers has been chemically modified. The portion mentioned here means that in the cellulose structure formed by the polymerization of multiple pyranose glucose units, at least one hydroxyl group of at least one pyranose glucose unit has been chemically modified. In a representative embodiment, the cellulose as a whole is not chemically modified, and the chemically modified cellulose microfibers retain the crystal structure of the cellulose before the chemical modification. For example, when analyzing by X-ray diffraction (XRD), the crystal structure of cellulose type I can be confirmed.
[0110] In one embodiment, the cellulose microfibers are chemically modified on at least their surfaces. In at least the cellulose microfibers whose surfaces are chemically modified, the length-weighted average fiber length of fibers having a fiber length of 100 μm or more may be 110 μm or more and 500 μm or less in a measurement using an automatic fiber shape analyzer, and the number frequency of fibers having a fiber length of 411 μm or more among fibers having a fiber length of 100 μm or more may be 54% or less.
[0111] Here, at least the surface of the cellulose microfibers chemically modified refers to cellulose microfibers in which at least a portion of the hydroxyl groups in the skeleton of cellulose are chemically modified. Chemically modified cellulose microfibers are usually chemically modified in the entire area from the surface to the inside, or the surface is chemically modified but has any one of the regions that are not chemically modified. In one embodiment of the cellulose microfibers, the surface is chemically modified and has a region that is not chemically modified. In one embodiment, even if the surface of the cellulose microfibers is chemically modified, the overall crystal structure of the cellulose microfibers does not change, and the crystal structure before chemical modification is maintained (for example, when the cellulose microfibers are analyzed using XRD, it can be confirmed that it is a cellulose I type crystal structure). Such cellulose microfibers can be judged as cellulose microfibers whose surfaces are chemically modified and have regions that are not chemically modified. That is, in one embodiment, the cellulose microfibers have a cellulose I type crystal structure.
[0112] In one embodiment of the cellulose microfibers, the following fiber shape parameters are preferably satisfied in an automatic fiber shape analyzer:
[0113] (1) The average fiber diameter is 42.5 μm or less,
[0114] (2) The fine fiber area ratio is less than 90%,
[0115] (3) Among fibers having a fiber length of less than 100 μm, the number frequency of fibers having a fiber length of 20 μm or more and 56 μm or less is 30% or more and 97% or less, and
[0116] (4) The fibrillation rate is 5% or less.
[0117] In addition, a cellulose microfiber dispersion having a solid content of 5 ppm by mass of dimethyl sulfoxide (DMSO) was prepared and poured onto a smooth substrate and dried. In a scanning electron microscope (SEM) image of the surface of the obtained sample, an area of 15 μm was occupied. 2 The ratio of the total area occupied by the following ultrafine fibers to the total area occupied by the cellulose fine fibers is preferably 10% to 80%.
[0118] (Automatic fiber shape analyzer)
[0119] The various characteristics of the cellulose microfibers in this embodiment are measured using an automatic fiber shape analyzer (in one embodiment, Morfi Neo manufactured by Techpap). The measurement steps are described below. It should be noted that regarding the fiber parameters during the measurement, a fiber length of 100 μm is used as a threshold, and fibers with a fiber length of more than 100 μm are defined as regular fibers, and fibers with a fiber length of less than 100 μm are defined as fine fibers.
[0120] 1. Disperse cellulose microfibers in pure water to prepare 1L of aqueous dispersion. Here, the final solid content concentration of the cellulose microfibers is set to 0.003-0.005% by mass. It should be noted that in the case of an aqueous dispersion of less than 2% by mass of cellulose microfibers before dilution, it is sufficient to simply mix using a spatula, etc. In the case of an aqueous dispersion of more than 2% by mass, a water-containing fiber cake or a powder, a high shear homogenizer (in one embodiment, the trade name "ULTRA-TURRAX T18" manufactured by IKA) is used to perform dispersion treatment under the treatment conditions of a rotation speed of 25,000 rpm × 5 minutes. When dispersed in a medium other than water, the dispersion treatment is carried out in a sufficient amount of pure water using the above-mentioned high shear homogenizer under the treatment conditions: rotation speed of 25,000 rpm×5 minutes, and then the medium is removed by means of suction filtration, and the dispersion treatment is carried out again in pure water using the above-mentioned high shear homogenizer under the treatment conditions: rotation speed of 25,000 rpm×5 minutes so that the final solid content concentration is 0.003 to 0.005% by mass, thereby replacing the medium with water.
[0121] 2. The aqueous dispersion prepared in 1. is supplied to an automatic sampler and measured.
[0122] 3. Output the measurement results in txt format (or csv format).
[0123] 4. Extract or calculate each shape parameter from the measurement results. It should be noted that each parameter uses the following values in the measurement results.
[0124] (1) Mean arithmetic length [μm]
[0125] (2) Mean length-weighted length [μm] of conventional fibers (fibers with a fiber length of 100 μm or more)
[0126] (3) Frequency of fibers with a fiber length of 411 μm or longer in normal fibers (fibers with a fiber length of 100 μm or longer): calculated from the length-weighted fiber length distribution (length-weighted fiber length, μm) of normal fibers.
[0127] (4) Mean fiber width [μm]
[0128] (5) Fine content, % in Area
[0129] (6) Number frequency of fibers with a fiber length of 20 μm or more and 56 μm or less among fine fibers (fibers with a fiber length of less than 100 μm): calculated from the fiber length distribution of fine fibers (Fine length, μm: FL).
[0130] (7) Macro Fibrillation index [%]
[0131] It should be noted that in the measurement of the fiber length distribution in this device, the data interval can be set arbitrarily, and therefore any setting may be used as long as the distribution of fibers having the above-mentioned fiber length can be confirmed.
[0132] Each shape parameter is described in detail below.
[0133] (Average fiber length)
[0134] In one embodiment of the cellulose microfiber, in the fiber shape automatic analyzer, the average fiber length is 110 μm to 500 μm, or 130 μm to 350 μm. The average fiber length here is the arithmetic mean fiber length, which refers to the length of the tortuous fiber when its ends are connected to each other by a straight line. By making the average fiber length within this range, it can be evenly dispersed when mixed in the resin, and the stress transferability is improved, so the strength and breaking strain are increased. The average fiber length of the cellulose microfiber is preferably 150 μm to 250 μm, and more preferably 160 μm to 200 μm.
[0135] (Length-weighted average fiber length)
[0136] In one embodiment of cellulose microfibers, in the measurement using a fiber shape automatic analyzer, the length-weighted average fiber length of conventional fibers (fibers with a fiber length of 100 μm or more) is between 110 μm and 500 μm, more preferably between 120 μm and 400 μm, and further preferably between 130 μm and 350 μm. The length-weighted average fiber length is defined by ISO / FDIS16065-2:2006 and is the average value of the fiber length equivalent to the actual fiber length in the tortuous fiber taking into account its tortuous shape. In cellulose microfibers, it is particularly advantageous to control the fiber length of conventional fibers within a specific range. That is, by making the fiber length of conventional fibers within this range, when mixed in the resin, the fibers that are too long will not entangle with each other to form agglomerates, but can be evenly dispersed, and the stress transferability is improved, so the strength and breaking strain are increased.
[0137] (Fiber length distribution of conventional fibers)
[0138] In one embodiment of cellulose microfibers, in the measurement using an automatic fiber shape analyzer, the number frequency of fibers with a fiber length of 411 μm or more in conventional fibers (fibers with a fiber length of 100 μm or more) is 54% or less. This number frequency can be calculated based on the above-mentioned length-weighted fiber length distribution. The length-weighted fiber length is the fiber length equivalent to the actual fiber length in a tortuous fiber, taking into account its tortuous shape. By making the fiber length of conventional fibers within this range, when mixed with a resin, the fibers that are too long will not entangle with each other to form agglomerates, but can be evenly dispersed, and the stress transferability is improved, thereby increasing the strength and breaking strain. In conventional fibers, the number frequency of fibers with a fiber length of 411 μm or more is preferably 40% or less, more preferably 30% or less. The lower limit is not particularly limited and is 0% or more.
[0139] (Average fiber diameter)
[0140] In the cellulose microfibers of the present embodiment, the average fiber diameter in the fiber shape automatic analyzer is preferably 42.5 μm or less, or 41.5 μm or less, or 40 μm or less, or 38 μm or less, or 35 μm or less, or 30 μm or less, or 25 μm or less. The length-weighted average fiber length and / or average fiber length are in the above range, and the average fiber diameter is in this range, which means that the L / D of each cellulose microfiber is large enough. By increasing L / D, the cellulose microfibers in the resin are entangled with each other, so the strength of the fiber-reinforced resin can be improved. The thinner the fiber diameter, the larger the L / D, so it is preferred, but from the resolution of the measuring device, it can be 1.5 μm or more. In addition, in order to improve the bending modulus of the fiber-reinforced resin, it is advantageous to have a certain degree of coarseness, and from this aspect, it is preferably 15 μm or more.
[0141] (Average fiber diameter calculated using specific surface area)
[0142] In cellulose microfibers, the specific surface area roughly corresponds to the average fiber diameter in one embodiment, and the specific surface area increases as the average fiber diameter decreases. In one embodiment, from the perspective of improving the strength of the fiber-reinforced resin, the specific surface area is preferably 20 m 2 / g or more, or 30m 2 / g or above, or 40m 2 / g or more, and from the perspective of increasing the flexural modulus of the fiber-reinforced resin, the specific surface area is preferably 100m 2 / g or less, or 80m 2 / g or less, or 60m 2 / g or less.
[0143] Regarding the average fiber diameter converted from the specific surface area using the steps described in the [Example] section of the present disclosure (also referred to as the converted average fiber diameter in the present disclosure), from the perspective of increasing the bending modulus of the fiber-reinforced resin, in one embodiment, it is 20 nm or more, or 30 nm or more, and from the perspective of increasing the strength of the fiber-reinforced resin by entanglement of the cellulose microfibers with each other in the resin, in one embodiment, it is 150 nm or less, or 130 nm or less, or 100 nm or less.
[0144] (fine fiber area ratio)
[0145] The fine fiber area ratio of the cellulose microfibers of this embodiment in the fiber shape automatic analyzer is preferably 90% or less, or 85% or less, or 80% or less, or 75% or less, or 60% or less, or 50% or less. Here, the fine fiber area ratio is the ratio of the sum of the areas of the observed images of fine fibers with a fiber length of less than 100 μm to the sum of the areas of the observed images of all fibers (area of conventional fibers + area of fine fibers). By making the fine fiber area ratio within this range, the fragile interface between cellulose / resin in the resin will not become too much, the starting point of destruction is reduced, and thus the failure strain is increased. From the perspective of easily producing orientation when mixed in the resin and obtaining good effects in improving the strength and elastic modulus of the fiber-reinforced resin, the fine fiber area ratio is preferably 5% or more, or 10% or more, or 20% or more, or 30% or more.
[0146] (Fiber length distribution of fine fibers)
[0147] For the cellulose microfibers of this embodiment, in the fiber shape automatic analyzer, the number frequency of fibers having a fiber length of 20 μm to 56 μm in the fine fibers (fibers having a fiber length of less than 100 μm) is preferably 97% or less, or 90% or less, or 85% or less, or 80% or less, or 75% or less, or 70% or less, or 65% or less. These fine fibers are too short in length, and therefore lack stress transferability, and their contribution to strength improvement tends to decrease. By controlling the number frequency of these fine fibers within a specified range, a particularly effective reinforcement effect can be obtained. As the cellulose raw material is refined, a large number of fine fibers having a fiber length of 20 μm to 56 μm are produced, so their number frequency can be 5% or more in one embodiment, and can be 30% or more, or 50% or more, or 55% or more, or 60% or more in another embodiment.
[0148] In a preferred embodiment, the frequency of fibers having a fiber length of 20 μm or more and 56 μm or less in fine fibers (fibers having a fiber length of less than 100 μm) is within the above range, and the frequency of fibers having a fiber length of 411 μm or more in conventional fibers (fibers having a fiber length of 100 μm or more) is less than 30%. Since the fiber length of fibers having a fiber length of 411 μm or more is too long, they are prone to agglomeration in the resin and contribute little to the improvement of the elastic modulus. Therefore, it is effective to control the frequency of fibers having a fiber length of 411 μm or more to be relatively low, preferably less than 10%, and more preferably less than 5%. The lower limit is not particularly limited, but it is difficult to completely eliminate fibers having a fiber length of 411 μm or more, so in one embodiment it can be more than 1%.
[0149] (Fibrillation rate)
[0150] The cellulose microfibers of the present embodiment preferably have a fibrillation rate of 5% or less in an automatic fiber shape analyzer. The fibrillation rate here refers to the ratio of the total length of n side chains L(Sub) branched from the main chain length L(Main) of the fiber having a structure in which at least a portion of the fiber is branched, with the portion with the largest fiber diameter as the main chain, and is defined by the following formula.
[0151] [Number 1]
[0152]
[0153] By making the fibrillation rate within this range, the surface area of each cellulose microfiber is reduced, the fragile interface between cellulose / resin in the resin does not become too much, the starting point of destruction is reduced, and thus the failure strain is increased. The fibrillation rate of the cellulose microfiber is preferably 4% or less, or 3% or less, or 2.5% or less, or 2% or less. The lower limit is not particularly limited, and in one embodiment is 0% or more, or 0.01% or more, or 0.1% or more.
[0154] (Area ratio of microfibers in SEM images)
[0155] Cellulose microfibers were prepared as a dimethyl sulfoxide (DMSO) dispersion with a solid content of 5 ppm by mass, which was then cast and dried on a smooth substrate. In a scanning electron microscope (SEM) image of the surface of the obtained sample, the area occupied by the microfibers was 15 μm. 2 The ratio of the total area occupied by the following microfibers to the total area occupied by the cellulose microfibers, that is, the area occupied by the microfibers is preferably 10% to 80%. The microfibers are fibers in the area that cannot be measured by the fiber shape automatic analyzer due to the resolution of the element. If the area occupied by the microfibers is too large, there are too many nano-sized fibers, so the microfibers in the resin are prone to agglomeration, which may become the starting point of destruction. On the other hand, if the area occupied by the microfibers is too small, there are too few nano-sized fibers, so a good nano network cannot be obtained and the strength tends to decrease. From the above aspects, the area occupied by the microfibers is more preferably 15% to 75%, more preferably 20% to 70%, and most preferably 20% to 65%. Cellulose microfibers with an area occupied by microfibers in the above range can be miniaturized using at least one physical method, and are usually referred to as cellulose nanofibers, CNF, CeNF, micronized cellulose microfibers, etc. The area occupied by the microfibers is measured according to the following steps.
[0156] 1. A cellulose microfiber aqueous dispersion having a solid content concentration of 0.2 to 2% by mass is diluted with dimethyl sulfoxide (DMSO) to a solid content of 5 ppm by mass, and stirred at 3000 rpm for 30 seconds using a homogenizer (in one embodiment, a product name "ULTRA-TURRAX T18" manufactured by IKA is used) to prepare a DMSO dispersion.
[0157] 2. Perform osmium plasma coating on a smooth substrate (silicon wafer, glass substrate) and heat it to 130° C. on a hot plate.
[0158] 3. 7 μL of the DMSO dispersion was dropped onto the center of the heated smooth substrate, and the substrate was left to dry under heating to fix the cellulose microfibers onto the substrate.
[0159] 4. The obtained substrate with fixed cellulose fine fibers was imaged using a scanning electron microscope (SEM) at an accelerating voltage of 1.5 kV, an observation magnification of 400 times, and a resolution of 400 pixels or more per 100 μm, at four different positions on the substrate.
[0160] 5. Calculate the value of the threshold value of 15 μm based on the number of pixels in the scale bar of the SEM image. 2 A comparable number of pixels.
[0161] 6. Based on the obtained SEM image, use the image processing software ImageJ to create a binary image using the MaxEntropy method.
[0162] 7. Use Analyze Particle of ImageJ to perform particle analysis on the binary image and calculate the area (pixel) of single fiber of cellulose microfibrils.
[0163] 8. The particle analysis results of the four images taken are summed up, and the particles with less than 2 pixels are deleted as noise, and the area smaller than 15μm is used as the threshold. 2 As ultra-fine fibers, the calculated size is less than 15 μm. 2 The ratio of the area of extremely small fibers to the total area of cellulose microfibers.
[0164] <Control of Fiber Shape of Cellulose Microfibers>
[0165] As a method for realizing the specific fiber shape of the cellulose microfibers of the present embodiment, more specifically, in one embodiment, the length-weighted fiber length, average fiber length, average fiber diameter, fine fiber area ratio, fine fiber length, fibrillation rate and / or the area occupied by ultrafine fibers of conventional fibers are realized within the scope of the present embodiment; or in one embodiment, the average fiber length, average fiber diameter, fine fiber area ratio (area occupied by ultrafine fibers), the number frequency of fibers with a fiber length of 20 μm or more and 56 μm or less among fibers with a fiber length of less than 100 μm, the number frequency of fibers with a fiber length of 411 μm or more among fibers with a fiber length of 100 μm or more, and / or the fibrillation rate are realized within the scope of the present embodiment, for example, one or more of the following methods can be cited. Using a disc refiner when refining the cellulose raw material, more specifically adjusting the disc structure and / or use conditions of the disc refiner, can be particularly advantageous for realizing the desired fiber shape of the present embodiment.
[0166] (Cellulose raw materials)
[0167] The raw material of the cellulose microfibers is not particularly limited, and wood-based cellulose raw materials (such as coniferous tree chips and broadleaf tree chips) or non-wood-based cellulose raw materials (cotton, hemp, bagasse, kenaf, bamboo, straw, seaweed, algae, sea squirt, and bacterial cellulose, etc.) can be used. It is preferred to use so-called wood pulps such as coniferous tree pulp and broadleaf tree pulp, and non-wood pulps such as cotton linter pulp, hemp pulp, bagasse pulp, kenaf pulp, bamboo pulp, and straw pulp, etc. Cellulose raw materials with high type I crystallinity are used. In a preferred embodiment, the cellulose microfibers are derived from plants.
[0168] In one embodiment, the average fiber length (specifically, the length-weighted average fiber length) of the cellulose raw material in an automatic fiber shape analyzer is 3 mm or less, and / or the number ratio of fibers with a fiber length of 3 mm or more is 20% or less. By making the cellulose raw material have a specific fiber length distribution, during the fiber opening process (for example, beating using a disc refiner or a high-pressure homogenizer), energy transmission in the refinement or beating section is good, and clogging is less likely to occur, so that stable fiber opening can be achieved even when the cellulose concentration is high.
[0169] The average fiber length is more preferably 2.5 mm or less, further preferably 2.0 mm or less, and particularly preferably 1.6 mm or less. The smaller the average fiber length, the more the above-mentioned effect is improved, so the lower limit is not particularly limited, but considering the mechanical properties of the cellulose microfibers after the pulping treatment when used as a resin filler, it is preferably 0.1 mm or more, and more preferably 0.5 mm or more.
[0170] The number ratio of fibers with a fiber length of 3 mm or more is more preferably 15% or less, and further preferably 10% or less. The smaller the value, the more the above effect is improved, so the lower limit is not particularly limited, and as a range obtained by actual pretreatment, it is preferably 0.5% or more, and more preferably 1% or more.
[0171] The fiber length of the cellulose raw material can be measured using an automatic fiber shape analyzer (MorfiNeo manufactured by Techpap). The measurement procedure is described below.
[0172] The cellulose raw material is dispersed in pure water to prepare a 1L aqueous dispersion. Here, the final solid content concentration of the cellulose raw material is 0.003 to 0.005 mass%. It should be noted that, in the case of an aqueous dispersion of less than 2 mass% of the cellulose raw material before dilution, it is sufficient to simply mix it with a scraper, etc., and in the case of an aqueous dispersion of more than 2 mass%, a water-containing fiber cake or a powder, etc., a high shear homogenizer (manufactured by IKA, trade name "ULTRA-TURRAX T18") is used to perform dispersion treatment under the treatment conditions: a rotation speed of 25,000 rpm × 5 minutes. When dispersed in a medium other than water, a high shear homogenizer (manufactured by IKA, trade name "ULTRA-TURRAX T18") is used to perform a dispersion treatment in a sufficient amount of pure water under the treatment conditions of a rotation speed of 25,000 rpm × 5 minutes, and then the medium is removed by suction filtration or the like, and a high shear homogenizer (manufactured by IKA, trade name "ULTRA-TURRAX T18") is used again to perform a dispersion treatment in pure water under the treatment conditions of a rotation speed of 25,000 rpm × 5 minutes so that the final solid content concentration is 0.003 to 0.005% by mass, thereby replacing the medium with water.
[0173] Next, the aqueous dispersion prepared above is supplied to an automatic sampler for measurement. The obtained measurement results are output in txt format (or csv format), and each shape parameter is extracted or calculated based on the measurement results. It should be noted that each parameter uses the following values in the measurement results.
[0174] 1) Mean length-weighted Length [μm]
[0175] 2) Ratio of fibers with a fiber length of 3 mm or longer: Based on the bar graph of fiber length distribution in 1), the ratio of the number of fibers with a fiber length of 3 mm or longer to the total number of fibers is calculated by the following formula.
[0176] Ratio of fibers with a fiber length of 3 mm or more (%) = number of fibers with a fiber length of 3 mm or more / total number of fibers measured × 100
[0177] 3) Mean fiber width [μm]
[0178] (Pretreatment of cellulose raw materials)
[0179] In the cellulose raw material of the present embodiment, in order to control its fiber length within a specific range, it can be subjected to fiber opening (e.g., beating treatment) after being subjected to one or more pretreatments selected from pulverization, grinding, and classification. One form of pretreatment is the following treatment: starting from a cellulose raw material having an average fiber length of more than 3 mm and a number ratio of fibers having a fiber length of more than 3 mm being more than 20%, a raw material having an average fiber length of less than 3 mm and / or a number ratio of fibers having a fiber length of more than 3 mm being less than 20% is generated, i.e., a pretreated cellulose raw material.
[0180] The pulverization treatment in the present embodiment is a treatment for dry pulverizing the cellulose raw material, and as the pulverizer, a coarse pulverizer, an intermediate pulverizer, a fine pulverizer, or the like can be used.
[0181] Examples of coarse crushers include jaw crushers (i.e., crushers that feed the raw materials between a fixed plate and a movable plate and use a strong compressive force to crush them), gyratory crushers (i.e., crushers that feed the raw materials between a fixed conical hole and an eccentrically rotating sleeve and use a compressive force to crush them), and impact crushers (i.e., crushers that use an impact blade mounted on a high-speed rotating cylindrical rotor to impact and crush the raw materials, causing the raw materials to further impact a rebound plate at a high speed, thereby impacting and crushing them).
[0182] Examples of intermediate pulverizers include a roller crusher (i.e., a pulverizer in which a plurality of cylindrical horizontal rollers are arranged, the raw material is passed through the gap between the rollers, and the raw material is pulverized by the pressure of two rollers with different rotation directions and rotation speeds), a wheel mill (i.e., a pulverizer in which two rollers with large diameters and weight are rotated on a horizontal disk to compress and shear, thereby pulverizing, mixing and kneading the raw material), a disintegrator (i.e., a pulverizer in which two cage-type rotors made of steel are rotated in opposite directions around coaxial axes, and the raw material supplied from the inner rotor is pulverized by applying impact force by centrifugal force and rotation), a SAG (Semi-Autogenous Grinding mill) mill, an automatic pulverizing mill, and the like.
[0183] SAG mill is a pulverizer that uses both large stones and metal balls for crushing. SAG mills usually use the smallest balls with a charge of 6 to 15%. The large stones and iron balls in the drum are thrown up by the rotation of the drum, and collide with objects to crush them. At this time, they become smaller particles through friction. The characteristics of SAG mills are the size of their diameter and the length of the barrel. Plates for mixing objects are arranged inside the mill.
[0184] In an automatic pulverizing mill (also called a ROM (Run of Mine) mill), large stones are thrown upward by a rotating drum, and the stones collide with each other to compress the particles. The principle is similar to the above-mentioned SAG mill, but it differs in that metal balls are not used.
[0185] Examples of the fine pulverizer include sieving type (sieving mill), rotating disk type, axial flow type, ball mill type pulverizers, rod mills, jet mills, and the like.
[0186] In a ball mill type pulverizer, sand or metal balls are usually placed inside a horizontal or slightly inclined rotating barrel, and the material is crushed by collision and friction with the balls. The material to be crushed is supplied from one side of the barrel, and the crushed product is discharged from the other side.
[0187] Rod mills have a similar structure to ball mills, but use rods (metal cylinders) instead of balls as the grinding medium. The rods are applied to the material to be ground by the rotating drum (machine body) to grind it. Compared with ball mills, it is less likely to be over-ground and a relatively uniform particle size of the ground product can be obtained.
[0188] In a jet mill, compressed air is used to generate supersonic airflow to pulverize the material to be pulverized. There are two types of jet mills: a flat type in which jet nozzles are arranged in a spiral shape, and a collision type in which supersonic airflow from the jet nozzles is sprayed onto a collision plate.
[0189] In the treatment of the cellulose raw material of the present embodiment, among the above-mentioned pulverizers, an intermediate pulverizer or a fine pulverizer is preferred, and a fine pulverizer is more preferred. Among the fine pulverizers, a screening type is preferred because it is excellent in terms of processing capacity.
[0190] Secondly, the grinding treatment of the present embodiment is a treatment in which the cellulose raw material is dispersed in an aqueous medium and the aqueous dispersion is subjected to a grinding treatment. It is a wet treatment, which is distinguished from the grinding treatment of the present embodiment. As the aqueous medium, water itself can be cited; or a mixed medium of one or more organic solvents selected from monohydric alcohols such as ethanol, n-propanol, isopropanol, butanol, polyhydric alcohols such as ethylene glycol, diethylene glycol, glycerol, ketones such as acetone, nitrile solvents such as acetonitrile, pyrrolidone solvents, etc. and water. The mixing ratio of the organic solvent in the mixture of the above-mentioned organic solvent and water is preferably less than 50% by mass, more preferably less than 30% by mass, and particularly preferably less than 20% by mass. The higher the water ratio, the better the grinding property, and the higher the organic solvent ratio, the more the aggregation of fine fibers is suppressed in the drying process after grinding. Therefore, the ratio of the organic solvent is preferably set in consideration of the balance between grinding property and aggregation suppression. Examples of the attritor that can be used in the present embodiment include a rotary mortar, a mortar grinder, a planetary mixer, a single-screw extruder, a twin-screw extruder, and a bead mill.
[0191] A bead mill is a medium-mixing mill that uses beads to nano-disperse or finely pulverize powders. The material to be processed and beads (medium) are placed in a pulverizing chamber (container), and the stirring mechanism rotates at high speed and imparts energy to the beads through centrifugal force, pulverizing the crushed particles through tangential stress, shear stress, friction, and impact force.
[0192] Among these grinding machines, a rotary mortar, a pounding machine, or a planetary mixer is preferred because of its excellent adjustability to the fiber length distribution. In addition, the cellulose concentration in the aqueous dispersion used in the grinding is preferably 50% by mass or less, more preferably 25% by mass or less, and particularly preferably 20% by mass or less. As the lower limit, in consideration of the efficiency of the grinding, it is preferably 1% by mass or more, more preferably 2% by mass or more, further preferably 5% by mass or more, and particularly preferably 10% by mass or more.
[0193] In addition, the classification process of the present embodiment is an operation to make the fiber length of the cellulose raw material consistent and to distinguish by the fiber length, and any method of dry classification and wet classification can be used. As dry classification, gravity field classification, inertial force field classification, and centrifugal field classification (natural vortex type or forced vortex type) can be cited, and as wet classification, gravity field classification, centrifugal field classification (free vortex type) and centrifugal field classification (forced vortex type) can be cited, and they can all be used. In addition, classification using meshes such as sieves, screens, wire screens (wedge wire screens (wedge wire)), nets, and classification using centrifugal separation can also be used. Considering production efficiency, it is preferred to use mesh classification, among which dry cyclone separators or screens, or wet screens or wedge wire screens are more preferred, and wet screens or wedge wire screens are further preferred, and wet wedge wire screens are particularly preferred.
[0194] In order to suppress the discoloration and property reduction caused by heat during composite formation for the resin, the cellulose raw material and / or cellulose microfiber of the present embodiment is preferably 80% by mass or more based on the glucose content of the constituent sugar analysis, and the cellulose fiber raw material for manufacturing cellulose microfibers is also preferably 80% by mass or more based on the glucose content of the constituent sugar analysis. These glucose contents are more preferably 85% by mass or more, or 90% by mass or more, or 91% by mass or more, or 93% by mass or more. According to the limits of impurities (such as fat components other than polysaccharides, various contaminants, etc.) that may be mixed in during the harvest of the cellulose raw material or the refining process or the manufacturing process of cellulose microfibers, the glucose content is preferably 99.5% by mass or less, or 99% by mass or less. The glucose content in the cellulose microfibers has a high value, which usually means that the cellulose purity is high, that is, the amount of lignin, hemicellulose, etc., which are components that may reduce the high elastic modulus and high heat resistance of the cellulose microfibers, is small.
[0195] In the present disclosure, the determination method of glucose content in the constituent sugar analysis is as follows. The constituent sugar analysis can be carried out with reference to the analysis process of the National Renewable Energy Institute of the U.S. Department of Energy (Sluiter, A., Hames, B., Ruiz, R., Scarlata, C., Sluiter, J., Templeton, D., Crocker, D.: Determination of structural carbohydrates and lignin in biomass. National Renewable Energy Laboratory (NREL), USA, 2008.). 72% sulfuric acid 3ml is added to 200mg of the sample, swelled at 30°C for 1 hour, and then 84ml of pure water is used to flow it into a 125ml pressure bottle and hydrolyzed at 120°C for 1 hour. Thereafter, a 1G-3 glass filter (constant weight at 105°C) can be used for hot filtration, and after solid-liquid separation, the filtrate is fixed to 100ml, and the constituent sugar is quantified by high performance liquid chromatography (HPLC) (FL detection method).
[0196] A preferred example of a cellulose raw material is a refined cellulose fiber. Refined cellulose fiber refers to a refined cellulose raw material such as a refined pulp or a cotton-like refined product obtained by a refining process and a bleaching process for the purpose of delignification and removal of hemicellulose by steaming from coniferous tree chips, broadleaf tree chips, or non-wood cellulose raw materials (cotton source, hemp source, bagasse source, kenaf source, bamboo source, straw source, seaweed source, algae source, sea squirt source, and bacterial cellulose source, etc.). Among these, the cellulose purity of cotton fiber, cottonseed linters, or bacterial-derived cellulose raw materials is high, and thus particularly preferred. In addition, the cut filaments of regenerated cellulose fibers can also be used as a raw material for cellulose microfibers, and the cut filaments of regenerated cellulose obtained by electrostatic spinning can also be used as a refined cellulose fiber raw material for cellulose microfibers. It is preferred to set appropriate refining treatment conditions (steaming temperature, alkali concentration during steaming, bleaching agent concentration, bleaching time) according to the type of cellulose raw material selected from them, and manufacture a purified cellulose fiber with high cellulose purity, which is used as a raw material.
[0197] In view of the recent need to realize a sustainable society, recycled materials such as recycled cotton and recycled wood can also be used as cellulose raw materials. The recycled cotton mentioned here refers to fibers produced by collecting and crushing the cut pieces and noil of cotton discarded from spinning mills and sewing factories; fibers obtained by crushing cotton that has been temporarily prepared into the form of cloth, clothes, etc. In addition, recycled wood refers to a material obtained by pulping waste wood from sawmills, construction wood, thinning wood, forestry residues, etc. by conventional methods. As a cellulose raw material, among the above-mentioned recycled materials, recycled cotton is preferred.
[0198] In order to obtain highly purified cellulose fibers, it is sometimes effective to purify the fibers by performing the following three treatments or by combining a plurality of these three treatments: the cellulose fibers or the purified cellulose fibers are further immersed in water and subjected to heat treatment at a temperature of 100°C or higher; the cellulose fibers or the purified cellulose fibers are immersed in a strong alkali aqueous solution such as sodium hydroxide (alkali concentration: 1% to 10% by mass), and allowed to stand or stir for a certain period of time at a temperature in the range of 0°C to 60°C, and then repeatedly washed with water for an alkali treatment; or the cellulose fibers or the purified cellulose fibers are further immersed in water and subjected to an enzyme treatment in which a hemicellulose decomposing enzyme such as xylanase or mannanase or a cellulase is allowed to act at a temperature in the range of 35°C to 55°C. These treatments not only reduce the load of the micronization treatment, but also discharge impurity components such as lignin and hemicellulose present on the surface or gaps of the microfibrils constituting the cellulose fibers into the aqueous phase, and as a result, have the effect of improving the cellulose purity of the purified cellulose fibers, and are sometimes very effective. In particular, when bacterial cellulose is used as a raw material, washing with cold water at 2°C to 10°C or the like can remove water-soluble polysaccharide components produced simultaneously with bacterial cellulose, which is sometimes effective as a purification method.
[0199] (Crystallinity)
[0200] In one embodiment, the cellulose raw material and / or the cellulose microfibers may have a cellulose I type crystal structure, or may have a cellulose II type crystal structure. In a preferred embodiment, the cellulose microfibers have a cellulose I type crystal structure. The crystallinity of the cellulose raw material or cellulose microfibers of this embodiment is preferably 55% or more, or 60% or more. When the crystallinity is within this range, the mechanical properties (especially strength and dimensional stability) of the cellulose microfibers themselves are improved, so the strength and dimensional stability of the fiber-reinforced resin formed by dispersing the cellulose microfibers in the resin tend to increase. The crystallinity of the cellulose raw material or cellulose microfibers is preferably 65% or more, more preferably 70% or more, and most preferably 80% or more. The higher the crystallinity, the more preferred it is, so the upper limit is not particularly limited, and from the production point of view, 99% is the preferred upper limit.
[0201] There are alkali soluble polysaccharides such as hemicellulose and acid insoluble components such as lignin between the microfibrils of plant-derived cellulose and between the microfibril bundles. Hemicellulose is a polysaccharide composed of sugars such as mannan and xylan, which is hydrogen-bonded with cellulose and plays a role in connecting the microfibrils. In addition, lignin is a compound with an aromatic ring, and it is known that it is covalently bonded with hemicellulose in the cell wall of plants. If the residual amount of impurities such as lignin in the cellulose microfibers is large, it may cause discoloration due to the heat during processing. Therefore, from the perspective of suppressing the discoloration of the fiber-reinforced resin during extrusion processing and molding processing, it is also preferred that the crystallinity of the cellulose microfibers is within the above range.
[0202] When the cellulose is cellulose type 1 crystal (derived from natural cellulose), the crystallinity is determined by the following formula using the Segal method from a diffraction pattern (2θ / deg.: 10 to 30) when the sample is measured by wide-angle X-ray diffraction.
[0203] Crystallinity (%) = [I (200) -I (amorphous) ] / I (200) ×100
[0204] I (200) : Diffraction peak intensity based on the 200-plane (2θ=22.5°) in cellulose type I crystals
[0205] I (amorphous) : The halo peak intensity of the amorphous cellulose type I crystal is the peak intensity at an angle 4.5° lower than the diffraction angle of the 200-plane (2θ=18.0°).
[0206] In addition, regarding the crystallinity, when the cellulose is a cellulose II type crystal (derived from regenerated cellulose), it can be calculated by the following formula based on the absolute peak intensity h0 at 2θ=12.6° of the (110) plane peak belonging to the cellulose II type crystal in wide-angle X-ray diffraction and the peak intensity h1 from the baseline at the plane spacing.
[0207] Crystallinity (%) = h1 / h0×100
[0208] As the crystalline form of cellulose, type I, type II, type III, type IV, etc. are known, among which type I and type II are particularly commonly used, and type III and type IV are not commonly used on an industrial scale, although they can be obtained on a laboratory scale. As the cellulose raw material or cellulose fine fiber disclosed in the present invention, it is preferred to contain cellulose type I crystals or cellulose type II crystals, and it is more preferred to contain cellulose type I crystals and have a crystallinity of 55% or more, because the cellulose raw material or cellulose fine fiber has relatively high structural mobility, and a resin composition having a further reduced linear expansion coefficient and better strength and elongation during stretching and bending deformation can be obtained by dispersing the cellulose fine fiber in a resin.
[0209] (Chemical modification)
[0210] The cellulose microfibers of this embodiment are cellulose microfibers obtained by modifying the hydroxyl groups on the surface of the cellulose microfibers by chemical modification. The chemical modification can be performed in a state before fiber opening (in one embodiment, in a pulp state), followed by a micronization treatment described below, or the chemical modification can be performed after the micronization treatment is performed to produce the cellulose microfibers. In the case of obtaining low-halogen cellulose microfibers, it is preferred to perform chemical modification in a state before fiber opening, followed by a fiber opening treatment described below. In addition, in the case of performing a pretreatment before fiber opening, the chemical modification can also be performed before the pretreatment, but it is easier to perform after the pretreatment, which is preferred.
[0211] As the method of chemical modification, esterification, etherification, carbamateization, etc. can be cited, preferably esterification. Among them, esterification of saturated monocarboxylic acids such as esterification of acetic acid (acetylation), propionic acid, esterification of valeric acid (valeric acid), esterification of caproic acid (caprylic acid) is preferred, wherein from the aspect of the heat resistance of the cellulose microfibers after modification (i.e. chemical modification), esterification of acetic acid (acetylation) is preferred, and esterification using dicarboxylic acids such as phthalate esterification can also be used. Chemical modification can be carried out by using a common esterification reaction method using a saturated carboxylic acid or its anhydride or acyl chloride, vinyl acetate, vinyl propionate, etc. saturated monocarboxylic acid vinyl esters, etc.
[0212] When a cellulose raw material (e.g., pulp) is chemically modified before micronization, in order to allow the chemical modification to proceed to the fiber surface inside the cellulose raw material, the chemical modification is preferably performed in a solvent that allows the cellulose raw material to swell well. The solvent that allows the cellulose raw material to swell well is, in one embodiment, an aprotic polar solvent, preferably dimethyl sulfoxide (DMSO), N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), or any mixture thereof.
[0213] On the other hand, in the case of chemical modification after micronization, the cellulose microfibers are concentrated by suction filtration, etc., and after being made into a fiber cake in a wet state, they are diluted and dispersed in a solvent for chemical modification. The method of chemical modification can be the same as the chemical modification of the cellulose raw material. At this time, if the cellulose microfibers are over-dried, they will produce agglomeration, so the cellulose solid content concentration is preferably 30% by mass or less, and more preferably 20% by mass or less. In addition, in the case of using an esterifying agent, since the esterifying agent also reacts with water, it is better to substitute less water, and as the lower limit of the cellulose solid content concentration, it is preferably 5% by mass or more, or 10% by mass or more. In the case where chemical modification is difficult due to the presence of water, the operation of suction filtration of the dispersed slurry diluted and dispersed in the above-mentioned solvent and further adding a solvent can be repeated to reduce the water content in the system, and then chemical modification is performed. In addition, in the case of chemical modification after micronization, in order to uniformly perform chemical modification, it is also preferred to use a solvent that makes the above-mentioned pulp swell well as a solvent, but since the surface of the cellulose microfibers will be exposed, a solvent other than the above-mentioned solvent can also be used.
[0214] When the group introduced by chemical modification is an acyl group (e.g., an acetyl group), the degree of substitution (DS) (degree of acylation, e.g., degree of acetylation) of the acyl group is preferably 0.5 or more, more preferably 0.6 or more, and further preferably 0.7 or more. Regarding the upper limit, if the DS is too high, the crystallinity decreases, and the mechanical properties of the resin composition obtained by compounding the cellulose microfibers with the resin tend to decrease, so the upper limit is preferably 1.3 or less, more preferably 1.1 or less, and further preferably 1.0 or less.
[0215] The degree of acyl substitution (DS) can be calculated from the peak intensity ratio of the peak derived from the acyl group to the peak derived from the cellulose skeleton in the reflective infrared absorption spectrum of the esterified cellulose microfibers. The absorption band of C=O based on the acyl group appears at 1730 cm -1 The peak of the absorption band of CO based on the cellulose backbone chain appears at 1030 cm -1 (Refer to Figure 1). Regarding the DS of esterified cellulose microfibers, a correlation curve graph can be prepared between the DS obtained by solid NMR measurement of esterified cellulose microfibers described later and the modification rate (IR index 1030) defined by the ratio of the peak intensity of the absorption band based on C=O of the acetyl group to the peak intensity of the absorption band of CO of the cellulose backbone chain, and the DS can be obtained by using a calibration curve calculated based on the correlation curve graph.
[0216] Degree of substitution DS = 4.13 × IR index (1030)
[0217] In the method for calculating the DS of esterified cellulose microfibers based on solid NMR, the DS of esterified cellulose microfibers after freeze-crushing can be calculated. 13 C solid NMR measurement, the area intensity (Inf) of the signal attributed to one carbon atom derived from the modifying group relative to the total area intensity (Inp) of the signals attributed to carbons C1-C6 derived from the pyranose ring of cellulose appearing in the range of 50 ppm to 110 ppm was calculated by the following formula.
[0218] DS=(Inf)×6 / (Inp)
[0219] For example, when the modifying group is an acetyl group, the signal of 23 ppm attributed to -CH 3 may be used.
[0220] Used 13 The conditions for C solid NMR measurement are as follows, for example.
[0221] Device: Bruker Biospin Avance500WB
[0222] Frequency: 125.77MHz
[0223] Determination method: DD / MAS method
[0224] Waiting time: 75sec
[0225] NMR sample tube: 4mmΦ
[0226] Integration times: 640 times (about 14 hours)
[0227] MAS: 14,500Hz
[0228] Chemical shift standard: glycine (external standard: 176.03 ppm)
[0229] (DS of cellulose fiber s / DS)
[0230] In one embodiment, the cellulose fiber may be a cellulose microfiber having a chemically modified surface. In one embodiment, the DS unevenness ratio (DSs / DS) defined by the ratio of the degree of substitution (DSs) on the fiber surface of the chemically modified cellulose microfiber to the degree of substitution (DS) of the entire fiber is 1.05 or more.
[0231] When the chemically modified group is an acyl group, the DS inhomogeneity ratio (DSs / DS) defined by the ratio of the acyl substitution degree (DSs) of the fiber surface to the acyl substitution degree (DS) of the entire fiber is preferably 1.05 or more. The greater the value of the DS inhomogeneity ratio, the more significant the inhomogeneous structure of the sheath-core structure (i.e., the following structure: the fiber surface layer is highly chemically modified, and on the other hand, the fiber center maintains the original structure of the cellulose close to the unmodified cellulose), which can have high tensile strength and dimensional stability from cellulose, and can improve the affinity with the resin when compounded with the resin, and improve the dimensional stability of the resin composition. The DS inhomogeneity ratio is more preferably 1.1 or more, or 1.2 or more, or 1.3 or more, or 1.5 or more, or 2.0 or more, and is preferably 30 or less, or 20 or less, or 10 or less, or 6 or less, or 4 or less, or 3 or less from the aspect of the ease of manufacturing the chemically modified cellulose microfibers.
[0232] DS s The value of varies depending on DS, and as an example, is preferably 0.1 or more, or 0.2 or more, or 0.3 or more, or 0.5 or more, and is preferably 3.0 or less, or 2.5 or less, or 2.0 or less, or 1.5 or less, or 1.2 or less, or 1.0 or less.
[0233] DSs is obtained by the following method. That is, the esterified cellulose microfibers that have been powdered by freeze-crushing are placed on a 2.5 mm Φ dish-shaped sample stand, the surface is pressed to make it flat, and the measurement is performed using X-ray photoelectron spectroscopy (XPS). The XPS spectrum reflects the constituent elements and chemical bonding state of only the surface layer of the sample (representatively about a few nm). The obtained C1s energy spectrum can be peak separated, and the DSs can be obtained by the following formula based on the area intensity (Ixf) of the peak belonging to a carbon atom from a chemically modified group relative to the area intensity (Ixp) of the peak belonging to carbon C2-C6 of the pyranose ring from cellulose (289 eV, CC bond).
[0234] DSs=(Ixf)×5 / (Ixp)
[0235] When the chemical modification group is an acetyl group, after peak separation of the C1s spectrum at 285eV, 286eV, 288eV, and 289eV, the peak at 289eV may be used in Ixp, and the peak (286eV) derived from the OC═O bond of the acetyl group may be used in Ixf.
[0236] The XPS measurement conditions used are as follows, for example.
[0237] Equipment used: ULVAC Phi VersaProbeII
[0238] Excitation source: mono.AlKα15kV×3.33mA
[0239] Analysis size: about 200μmΦ
[0240] Photoelectron extraction angle: 45°
[0241] Capture Area
[0242] Narrow scan: C 1s, O 1s
[0243] Pass energy: 23.5eV
[0244] (Changes in the morphology of cellulose raw materials or cellulose microfibers before and after chemical modification)
[0245] In the chemical modification of the present embodiment, the stirring conditions, temperature, etc. are appropriately adjusted, and the fiber length maintenance rate of the cellulose raw material or cellulose microfibers before and after the chemical modification (fiber length maintenance rate (%) = average fiber length (nm) after modification / average fiber length (nm) before modification × 100) is preferably 70% or more, more preferably 80% or more, and particularly preferably 90% or more. The average fiber length mentioned here is the length-weighted average fiber length measured using a fiber shape automatic analyzer (MorfiNeo manufactured by Techpap). When the fiber length is maintained very long after chemical modification, the fiber length of the obtained cellulose microfibers will remain very long, so it is also beneficial in terms of improving the strength of the resin composition obtained by compounding the cellulose microfibers with a resin, and improving the heat resistance. The higher the maintenance rate of the fiber length, the greater the effect, so the upper limit is not particularly limited, and considering the modification treatment in reality, it is preferably 99.5% or less.
[0246] (Micronization of cellulose)
[0247] The above raw materials can be micronized to obtain cellulose microfibers. In the micronization process, the raw pulp sheets are dispersed in water using a pulper, etc., and micronized using a refiner, a disc refiner, a high-pressure homogenizer, a water jet, a disc mill, a ball mill, a bead mill, a micro-crusher Mass Colloider, a homogeneous mixer and other micronizing devices. In one embodiment, the micronization can be a beating process. The micronization process can be performed using one stage (using one blade process) or multiple stages (using multiple blade processes). When performed in multiple stages, the same device can be used multiple times or different devices can be used in combination. In one embodiment, multiple stages are preferred.
[0248] In addition, before the micronization treatment, it is preferred to use a pulper, a homogeneous mixer, etc. to evenly disperse the raw materials in water, and then perform the micronization treatment. In particular, when the pulp is first chemically modified and then micronized, it is preferred to use a mixer such as a homogeneous mixer with a peripheral speed of, for example, 10 m / s or more, preferably 20 m / s or more, more preferably 25 m / s or more, for example, 90 m / s or less, preferably 80 m / s or less, and more preferably 50 m / s or less for dispersion treatment due to the decrease in the hydrophilicity of the pulp. By reducing lumps as a pretreatment, etc., uniform micronized cellulose microfibers can be obtained by uniform micronization. It should be noted that, regarding the water used at this time, it is sometimes effective to use high-purity water such as distilled water and ion-exchanged water.
[0249] (Multi-stage miniaturization)
[0250] When cellulose is refined in multiple stages, it is effective to combine a refinement mechanism or two or more refinement devices with different shearing speeds. Here, as a method for multi-stage refinement, it is preferred to use a disc refiner with different disc configurations for multi-stage refinement, or to use a high-pressure homogenizer for refinement after refinement using a disc refiner. The disc refiner here can use any of a single disc refiner, a double disc refiner, and a conical refiner. In one embodiment, in order to highly control the refinement, a single disc refiner with high controllability of the gap between the fixed blade and the rotating blade is preferred.
[0251] (Fine refinement by disc refiner)
[0252] When a disc refiner is used for the refinement treatment, pulp or cotton-like cellulose fibers (e.g., purified cellulose fibers) are dispersed and stored in a tank in an aqueous medium so as to have a solid content concentration of, for example, 0.5% by mass to 6% by mass, preferably 0.8% by mass to 3.5% by mass, and more preferably 1% by mass to 3% by mass, and then the pulp is refined using a disc refiner. As for the water used at this time, it is sometimes effective to use water of high purity such as distilled water or ion-exchanged water.
[0253] During the operation of the disc refiner, the fiber opening treatment can be carried out by a cyclic continuous treatment process in which the slurry retained in the tank is returned to the original tank via the disc refiner. If the fiber opening treatment is carried out by the following continuous treatment process, the slurry can be reliably passed through the disc refiner in each treatment (pass operation), so a uniform number of passes can be implemented relative to the total amount of the slurry, which is more preferred from the perspective of the uniformity of the fiber opening degree, that is, the quality stability of the cellulose microfibers. The continuous treatment process is: prepare two tanks (set as tank A and tank B) connected by piping with the disc refiner at an interval, first, send liquid from tank A into which the slurry is added to tank B through the disc refiner for storage, and at the stage when the slurry treatment in tank A is completed, switch to a process in which liquid is continuously sent from tank B to tank A through the disc refiner for accumulation, and then repeat these processes alternately.
[0254] Figure 2 This is a diagram for explaining an example of the arrangement of blades and grooves of a disc refiner. Figure 3 This is a diagram for explaining the blade width, groove width, and distance between blades of a disc refiner. When multiple disc refiners are used to perform multi-stage refinement, the blades may be one or two or more, and it is preferred to use a refiner having at least two different blades. Figure 2 and 3 As a specific blade structure, Figure 2 In the disc refiner with blades 11 and grooves 12 shown, Figure 3 Blade width W shown B , Slot width W G , and blade width W B Divide by the slot width W GIt is important to properly adjust the obtained value (hereinafter referred to as the blade-groove ratio). It is particularly preferred that after a refinement treatment (hereinafter referred to as the front section) is carried out using a refiner equipped with a blade having a blade width of 1.5 mm to 5 mm and a blade-groove ratio of 0.1 to 1.0, a refinement treatment (hereinafter referred to as the back section) is carried out using a refiner having a blade width of 0.1 mm to 1.0 mm and a blade-groove ratio of 0.5 to 1.0 is carried out. By using a disc refiner of such a structure to open the fibers, it is possible to obtain cellulose microfibers with a reduced number of fibers with a long fiber length (in one embodiment, a fiber length of 411 μm or more) that causes aggregation in the resin and a low fibrillation rate (i.e., less fuzz). In addition, at this time, in one embodiment, the generation of fibers with a fiber length of 20 μm to 56 μm that lack a reinforcing effect can be suppressed. Other refinement steps can also be added between the front section and the back section.
[0255] In addition, when a disc refiner treatment is performed using a blade in one stage, it is particularly preferred to perform fine processing using a refiner having a blade width of 0.1 mm to 1.0 mm and a blade groove ratio of 0.5 to 1.0. At this time, the fiber length of the raw material used is preferably 500 μm or more, more preferably 700 μm or more, and further preferably 900 μm or more, preferably 3000 μm or less, more preferably 2000 μm or less, more preferably 1500 μm or less, and further preferably 1300 μm or less, based on the length-weighted average fiber length of the above-mentioned fiber shape automatic analyzer (in one embodiment, Morfi Neo manufactured by Techpap). By using a raw material having a fiber length in the above range, it is possible to obtain fibers having a fiber length of 411 μm or more, which is a cause of aggregation in the resin, and a low fibrillation rate.
[0256] (Blade distance in disc refiner treatment)
[0257] In addition, refer to Figure 3 In the refinement using a disc refiner, two blades (specifically, Figure 3 The distance W between the rotating blade 21 and the fixed blade 22) LIt is advantageous to control the (gap) (hereinafter referred to as the blade distance). By controlling the blade distance, the fiber length and the degree of beating of the cellulose microfibers can be controlled. When multiple stages are used for processing, it is preferred that the blade distance be between 0.05 mm and 0.5 mm in the front stage, and between 0.05 mm and 0.3 mm in the back stage. In addition, when one stage is used for processing, it is preferred that the blade distance be between 0.05 mm and 0.3 mm. It should be noted that when adjusting the blade distance, it is preferred to gradually reduce the blade distance from a wider blade distance while suppressing the current value of the device below a certain value. By controlling in this way, clogging and overloading of the device can be prevented, and cellulose microfibers with high homogeneity can be obtained.
[0258] In the micronization treatment of cellulose using a disc refiner as described above, it is advantageous to highly control the distance between the fixed blade and the rotating blade from the perspective of producing uniform cellulose microfibers with good mechanical properties as a filler. For example, in the adjustment of the distance between the blades of the single-disk refiner used in the past, there is a clearance in the flow channel portion that fixes the rotating blade due to the use of a screw-type screw jack or the like. Therefore, when the flow channel portion is strongly stretched in the thrust direction, it moves about 0.3 mm. Therefore, in order to obtain micronized cellulose with good accuracy and good reproducibility, it is preferred that the movement amount (clearance) is small, and the movement amount is preferably less than 0.1 mm, more preferably less than 0.08 mm, and further preferably less than 0.05 mm. In addition, when the accuracy of reducing the distance between the blades is less than 5 μm, the distance between the blades can be finely reduced, so it is preferred that the accuracy is more preferably less than 3 μm, and most preferably less than 1 μm. In one embodiment, a single-disc refiner can be used in which the amount of movement in the thrust direction is 0.03 mm by making the blade distance adjustment mechanism a ball screw jack. Furthermore, in order to adjust the blade distance with good precision, it is preferred to install a reducer on the ball screw jack so that fine blade distance adjustment can be performed. By using such a single-disc refiner, fine blade distance adjustment can be performed, and beating can be performed while maintaining a certain blade distance without the blade shaking during the beating process. In the [Example] item of the present disclosure, an example of the following device is shown: it uses a single-disc refiner in which the amount of movement in the thrust direction is 0.03 mm by making the blade distance adjustment mechanism a ball screw jack, and further a reducer is installed on the ball screw jack so that fine adjustment can be made in 1 μm units of blade distance, but any mechanism can be used as long as the movement of the flow channel portion or the accuracy of reducing the blade distance can be obtained by combining the ball screw jack with a servo motor.
[0259] By using such a single-disk refiner, the distance between blades can be finely adjusted. In addition, the blades can be kept at a constant distance between blades without shaking during the refinement process, and the fiber length can be prevented from becoming too short and the coarse fiber can be reduced by preventing the blades from contacting each other when the distance between blades is reduced. As a result, excellent mechanical properties can be imparted to the fiber-reinforced resin obtained by compounding cellulose microfibers with resin, and cellulose microfibers with high uniformity of shape distribution can be produced with good reproducibility.
[0260] (Number of passes in disc refiner treatment)
[0261] The degree of miniaturization can also be controlled by the number of times the cellulose microfibers pass through the disc portion, i.e., between the rotating blade and the fixed blade (hereinafter referred to as the number of passes). By increasing the number of passes, cellulose microfibers with uniform fiber diameter and fiber length distribution can be obtained. The number of passes here refers to the number of times the refiner treatment (i.e., passing between the rotating field and the fixed field) is performed after the above-mentioned inter-blade distance is reduced to the target inter-blade distance. The number of passes of the disc refiner is preferably 5 times or more, more preferably 20 times or more, and further preferably 40 times or more. If the number of passes increases, the distribution of the fiber shape slowly converges to a certain extent, so it is preferred that the number of passes is large; if productivity is also taken into account, the upper limit of the number of passes is preferably 300 times or less.
[0262] (Method for determining the refinement conditions using a disc refiner)
[0263] The shape of the cellulose microfibers obtained by the disc refiner treatment is controlled by the combined effects of the structure of the disc refiner (type and number of blades), the distance between blades, the number of passes, the concentration, etc. In order to obtain the shape of the cellulose microfibers that is preferred for use in fiber-reinforced resins, it is preferred to increase the number of passes under treatment conditions with relatively low intensity. The treatment intensity here is determined by the structure of the blades and the distance between blades of the disc refiner. As for the structure of the blades, if the blade width and the blade groove ratio are large, the treatment intensity decreases, and if they are small, the treatment intensity increases. Similarly, if the distance between blades is large, the treatment intensity decreases, and if it is small, the treatment intensity increases. Therefore, in the case of a blade structure with high treatment intensity, it is preferred to increase the distance between blades; conversely, in the case of a blade structure with low treatment intensity, it is preferred to reduce the distance between blades. A method of increasing the distance between blades using a blade structure with high treatment intensity is more preferred, and by achieving the above-mentioned number of passes under the treatment conditions, the average fiber length and the distribution of the fiber length can be controlled within a preferred range. In one embodiment, in order to obtain a preferred shape of cellulose microfibers when used in fiber-reinforced resins, it is preferred to increase the number of passes under sticky beating conditions. Sticky beating is a beating method that tends to cause the fibers to fluff and be fined, and a beating method that tends to cause the fibers to be cut in the long direction is called free beating. As for the configuration of the blades of the disc refiner, if the number of blades is large, the blade length is long, the ratio of the blade width to the groove width (blade groove ratio) is large, and the contact angle is large, the number of intersections of the blades of the rotating blade and the fixed blade increases, so that the force applied to the fiber at one intersection is dispersed, and the number of impacts on the fiber increases, thereby showing a sticky beating tendency. On the other hand, when the above conditions are respectively opposite, a free beating tendency is shown. Regarding the distance between blades of the disc refiner, when blades showing a tendency to free beating are used, it is preferred that the distance between blades be widened, and when blades showing a tendency to sticky beating are used, it is preferred that the distance between blades be reduced. However, if the distance between blades is reduced too much, clogging or short fiberization due to cutting in the fiber length direction and excessive micronization may occur, so the distance between blades is preferably 0.05 mm or more. By adjusting the distance between blades and the number of passes according to the shape (fiber length and fiber diameter) of the cellulose raw material (e.g., pulp), the treatment concentration, and the blades used, the fiber shape such as the average fiber diameter and fiber length distribution can be controlled within a preferred range.
[0264] (Method for controlling the number of passes of disc refiner treatment)
[0265] Here, as a method for controlling the number of passes, the following methods can be used: a method of using one tank for one refiner, circulating the slurry simply, and controlling the number of passes based on the flow rate; or a method of using two tanks for one refiner, while the slurry is being processed by the refiner while being reciprocated between the tanks; etc. The former can simplify the equipment. On the other hand, in the latter, the cellulose microfibers can reliably pass through the disk portion in each treatment, so that cellulose microfibers with higher uniformity can be obtained. From the perspective of stably obtaining the cellulose microfibers of this embodiment that have a good reinforcing effect on the resin, that is, cellulose microfibers with uniform fiber shape, the latter method is preferred.
[0266] (Multi-stage refining process based on the combination of disc refiner and high-pressure homogenizer)
[0267] It is also one of the preferred methods to further subject the cellulose microfibers that have been micronized by a disc refiner to a micronizing treatment using a high-pressure homogenizer. Compared with a disc refiner, a high-pressure homogenizer has a greater effect of thinning the fibers. By combining a disc refiner with a high-pressure homogenizer, elongated cellulose microfibers can be obtained. The high-pressure homogenizer treatment is preferably performed at a pressure of 30 MPa or more, more preferably 50 MPa or more, and more preferably 80 MPa or more. The upper limit of the pressure may be preferably 300 MPa or less, more preferably 250 MPa or less, and more preferably 150 MPa or less, depending on the characteristics of the device.
[0268] Examples of high-pressure homogenizers include the NS type high-pressure homogenizer of Niro Soavi (Italy), the Lanier type (R Model) pressure homogenizer of SMT Co., Ltd., and the high-pressure homogenizer of Sanwa Machine Co., Ltd.; examples of ultrahigh-pressure homogenizers include high-pressure collision type micronizing processing machines such as the Microfluidizer of Mizuho Industrial Co., Ltd., the Nanomaizer of Yoshida Machine Co., Ltd., and the Ultimaizer of Sugino Machine Co., Ltd.; any device other than these devices may be used as long as the micronizing is performed using a mechanism substantially similar to these devices.
[0269] In the high-pressure homogenizer treatment, as in the case of the disc refiner treatment, the fiber opening treatment can be carried out by a cyclic continuous treatment process in which the slurry retained in the tank is transferred to the original tank via the high-pressure homogenizer. If the fiber opening treatment is carried out using the following continuous treatment process, the slurry can be reliably passed through (pass operation) in each high-pressure homogenizer treatment, so a uniform number of passes can be implemented relative to the total amount of the slurry, which is more preferred from the perspective of the uniformity of the fiber opening degree, that is, the quality stability of the cellulose microfibers. The continuous treatment process is as follows: prepare two tanks (set as tank A and tank B) connected by piping with a high-pressure homogenizer at an interval, first, send liquid from tank A into which the slurry is added to tank B through the high-pressure homogenizer for storage, and at the stage when the slurry treatment in tank A is completed, switch to a process in which liquid is continuously sent from tank B to tank A through the high-pressure homogenizer for accumulation, and then repeat these processes alternately.
[0270] (Processing to promote the micronization of cellulose raw materials)
[0271] In one embodiment, a pretreatment process may be performed before the micronization process. As a pretreatment method, autoclave treatment, enzyme treatment, immersion in a sodium hydroxide aqueous solution, or a combination thereof may be cited. These pretreatments all have the effect of destroying the hydrogen bonds between cellulose microfibrils, which not only reduces the load of the micronization process, but also discharges impurities such as lignin and hemicellulose present on the surface and in the gaps of the microfibrils constituting the cellulose microfibers into the aqueous phase, which results in an effect of improving the purity of the α-cellulose of the microfibers, and is therefore also effective in improving the heat resistance of the cellulose microfibers.
[0272] (Concentration and drying of cellulose microfibers)
[0273] The cellulose microfibers of this embodiment can be obtained in the form of a wet molded body (wet fiber cake) by dehydrating the slurry using a filter, a papermaking machine, etc. Among them, the papermaking method using a papermaking machine can reduce the drying shrinkage of the cellulose microfibers, which is advantageous from this aspect. In one embodiment, the slurry is filtered on a porous substrate to dehydrate it. In the papermaking method, any papermaking machine equipped with a wire screen with a mesh size that can dehydrate the slurry and retain the cellulose microfibers can be used. As a papermaking device, in the case of obtaining a flat sheet of fiber-reinforced resin, a device such as an inclined wire mesh papermaking machine, a long mesh papermaking machine, and a rotary mesh papermaking machine can be used as a papermaking machine.
[0274] Cellulose microfibers can also be used as dry fillers. In this case, a known drying device such as a hot air dryer or a spray dryer can be used for drying. Cellulose has the characteristics of being easily agglomerated in the drying process and difficult to be redispersed thereafter, so it is preferred to use a dispersant. By improving the redispersibility, the mechanical properties and stability of the obtained resin composition can be improved. Preferably, a dispersant is added to the cellulose microfiber aqueous dispersion, and then dried while applying shear to obtain a cellulose powder.
[0275] The dispersant may be at least one selected from the group consisting of a surfactant, an organic compound having a boiling point of 100° C. or higher, and a resin having a chemical structure capable of highly dispersing cellulose.
[0276] The surfactant can be any surfactant having a chemical structure in which a site having a hydrophilic substituent is covalently bonded to a site having a hydrophobic substituent. As the surfactant, surfactants used in various applications such as food and industrial use can be used, for example, one or more of the following substances can be used.
[0277] As for the surfactant, anionic surfactants, nonionic surfactants, zwitterionic surfactants, and cationic surfactants can all be used. From the aspect of affinity with cellulose, anionic surfactants and nonionic surfactants are preferred, and nonionic surfactants are more preferred.
[0278] Among the above substances, surfactants having a polyoxyethylene chain, a carboxyl group, or a hydroxyl group as a hydrophilic group are preferred from the aspect of affinity with cellulose, polyoxyethylene surfactants (polyoxyethylene derivatives) having a polyoxyethylene chain as a hydrophilic group are more preferred, and nonionic polyoxyethylene derivatives are further preferred. The polyoxyethylene chain length of the polyoxyethylene derivative is preferably 3 or more, more preferably 5 or more, more preferably 10 or more, and particularly preferably 15 or more. The longer the chain length, the higher the affinity with cellulose. In terms of balance with coating properties, the upper limit is preferably 60 or less, more preferably 50 or less, more preferably 40 or less, particularly preferably 30 or less, and most preferably 20 or less.
[0279] Among the above-mentioned surfactants, especially when the hydrophobic group is an alkyl ether type, an alkylphenyl ether type, a rosin ester type, a bisphenol A type, a β-naphthyl type, a styrenated phenyl type, or a hydrogenated castor oil type, the affinity with the resin is high, and therefore it can be used appropriately. As a preferred alkyl chain length (the number of carbon atoms excluding the phenyl group in the case of an alkylphenyl group), the preferred number of carbon atoms is 5 or more, more preferably 10 or more, further preferably 12 or more, and particularly preferably 16 or more. The more carbon atoms in the alkyl chain length, the more the affinity with common resins is improved. For example, in the case where the resin is a polyolefin, the more carbon atoms the surfactant has, the more the affinity with the resin is improved. Therefore, there is no upper limit on the number of carbon atoms, and it is preferably 30 or less, and more preferably 25 or less.
[0280] Among these hydrophobic groups, groups having a cyclic structure or groups having a bulky multifunctional structure are preferred. As the group having a cyclic structure, alkylphenyl ether type, rosin ester type, bisphenol A type, β-naphthyl type, and styrenated phenyl type are preferred, and as the group having a multifunctional structure, hydrogenated castor oil type is preferred. Among these, rosin ester type and hydrogenated castor oil type are particularly preferred.
[0281] In addition, as a non-surfactant-based dispersant, an organic compound with a boiling point of 100°C or above is sometimes effective. Examples of such organic compounds include polyethylene glycol, polypropylene glycol, and organic compounds having a glycerol structure. In addition, although it depends on the type of resin, for example, when the resin is a polyolefin, a high-boiling point organic solvent such as liquid paraffin and decalin is effective. In addition, when the resin is a polar resin such as nylon and polyacetate, it is sometimes effective to use the same solvent as the aprotic solvent that can be used when producing cellulose microfibers, such as dimethyl sulfoxide.
[0282] <Rheological properties of cellulose microfibers>
[0283] As the rheological properties of the cellulose microfibers of the present embodiment, in the strain dispersion measurement of a water dispersion having a cellulose concentration of 0.75% by mass, the reciprocal of the yield strain 1 / γ is preferably 200 or more, and more preferably 250 or more. If the parameter is in this range, when the cellulose microfibers are added to the resin, the effect of improving the dynamic viscoelasticity at high temperature is large, that is, the storage modulus in the high temperature region increases. For the cellulose microfibers, it is said that a pseudo-crosslinked structure is formed in water by the entanglement between the fibers and the hydrogen bonds acting between the cellulose molecules, and it is believed that the interaction between the cellulose microfibers in water partially reflects the interaction between the cellulose microfibers in the resin. Generally, in crosslinked bodies such as gels, it is said that the more the distance between the crosslinking points and the number of crosslinks, the higher the elastic modulus and strength of the crosslinked body, and it is believed that the cellulose microfibers contained in the above range of the yield strain interact firmly in the resin. In one embodiment, the upper limit of 1 / γ can be 1000 or less. The following describes the measurement conditions and the measurement method.
[0284] [Measurement conditions]
[0285] Measuring equipment: Rheometer HAAKE MERS (manufactured by Thermo Fisher Scientific)
[0286] Measuring fixture: Coaxial double cylinder (cup: CCB25 DIN, rotor: CC25 DIN Ti)
[0287] Measurement mode: Oscillation
[0288] Control method: Stress control
[0289] Control range: 0.01~100Pa
[0290] Temperature: 25℃
[0291] 1. Disperse the cellulose microfibers in pure water. Here, the final solid content concentration of the cellulose microfibers is 0.75% by mass. It should be noted that when the cellulose microfibers before dilution are an aqueous dispersion with a solid content concentration of less than 2% by mass, the dispersion treatment is performed by oscillating and mixing in a closed container with a filling rate of less than 75% by volume. In the case of an aqueous dispersion with a solid content concentration of more than 2% by mass, an aqueous fiber cake or a powder, a high shear homogenizer (in one embodiment, the trade name "ULTRA-TURRAX T18" manufactured by IKA) is used for dispersion treatment under the treatment conditions: a rotation speed of 25,000 rpm × 5 minutes. When dispersed in a medium other than water, the dispersion treatment is carried out in a sufficient amount of pure water using the above-mentioned high shear homogenizer under the treatment conditions: rotation speed of 25,000 rpm×5 minutes, and then the medium is removed by suction filtration or the like, and the dispersion treatment is carried out again in pure water using the above-mentioned high shear homogenizer under the treatment conditions: rotation speed of 25,000 rpm×5 minutes so that the final solid content concentration reaches 0.75% by mass, thereby replacing the medium with water.
[0292] 2. Allow the aqueous dispersion prepared in 1. to stand at 25°C for more than 24 hours.
[0293] 3. Install the fixture on the rheometer and use a pipette or dropper to add 17.0±1.0 g of cellulose microfiber aqueous dispersion.
[0294] 4. Perform measurement based on the settings, and calculate the inverse of the yield strain (1 / γ) from the analysis results (LVE analysis).
[0295] <Surface treatment of cellulose microfibers>
[0296] The cellulose microfibers of the present embodiment may have their surface layers modified as necessary. Examples of the modification method include esterification, etherification, and urethanization.
[0297] The modification method is preferably esterification, and esterification using saturated monocarboxylic acids is preferred. Specifically, the esterifying agent includes relatively short-chain substances such as acetic acid, propionic acid, valeric acid (valeric acid), caproic acid (caprylic acid) and long-chain substances such as palmitic acid and stearic acid. From the perspective of heat resistance of the modified cellulose microfibers, substances with shorter chain lengths such as acetic acid and propionic acid are more preferred.
[0298] <Surface Potential of Cellulose Microfibers>
[0299] The zeta potential of the cellulose microfibers of this embodiment is preferably not less than -50 mV and not more than 50 mV. By making the zeta potential within this range, the reactivity can be controlled to be low, so that thermal decomposition is not likely to occur, and when mixed with a resin or the like, coloration and reduction of the reinforcing effect are not likely to occur. The cellulose microfibers originally have a weak negative zeta potential of about -20 mV to 30 mV, but it is preferred that the zeta potential of the modified cellulose microfibers is within the above range even when the above surface treatment is performed.
[0300] <Cellulose microfibers having a halogen content of 250 ppm by mass or less>
[0301] One embodiment of the cellulose microfibers may be cellulose microfibers having a halogen content of 250 ppm by mass or less (also referred to as low-halogen cellulose microfibers in the present disclosure). When plant-derived cellulose microfibers are compounded with a resin, the presence of the cellulose microfibers may cause problems such as decomposition of the resin and corrosion inside devices such as mixing devices and molding devices. The halogen content of the low-halogen cellulose microfibers is below a certain level, thereby suppressing the decomposition of the resin when the cellulose microfibers are compounded with a resin, even if they are of plant origin. The fiber-reinforced resin obtained using the low-halogen cellulose microfibers has excellent stability during long-term storage, and can be stable even after undergoing more than two thermal histories associated with melt mixing, such as material regeneration. In addition, if low-halogen cellulose microfibers are used, corrosion of the device caused by the cellulose microfibers can also be suppressed.
[0302] In one embodiment, low-halogen cellulose microfibers may include both unmodified cellulose microfibers and chemically modified cellulose microfibers. In the present disclosure, the halogen content in the low-halogen cellulose microfibers refers to the halogen content remaining in the cellulose microfibers after the cellulose microfibers are subjected to the following [impregnation and filtration treatment]. In addition, in the present disclosure, the halogen content is a value measured according to the following [halogen content determination]. By making the halogen content of the cellulose microfibers within the above range, the decomposition of the resin when the cellulose microfibers are composited with the resin can be suppressed, so that the stability during long-term storage is excellent, and even after more than two thermal histories accompanied by melt kneading such as material regeneration, a stable resin composition can be obtained. In addition, the halogen content in the above range is also beneficial for suppressing corrosion inside devices such as mixing devices and molding devices.
[0303] When halogens are mixed in cellulose microfibers, the halogens are sometimes firmly connected to cellulose through chemical or physical bonding. In one embodiment, when the cellulose microfibers are temporarily immersed in pure water at 25°C for 48 hours and then filtered and dried as in the [immersion and filtration treatment] of the present invention, more than 80% by mass before the treatment can remain in the cellulose microfibers. Such halogens are caused by the firm connection with cellulose, and continue to remain when the cellulose microfibers are composited with a resin, which may cause adverse conditions such as decomposition of the resin and corrosion of the device. The cellulose microfibers of this embodiment are characterized by a low content of halogens firmly connected to cellulose. As an indicator thereof, the content of halogens remaining in the cellulose microfibers after the [immersion and filtration treatment] of the present invention is used.
[0304] [Immersion and filtration treatment]
[0305] The cellulose microfibers were immersed in pure water at 25°C for 48 hours. Specifically, the cellulose microfibers were immersed in pure water at a solid content of 2% by mass in a glass beaker with a total capacity of 200 mL, stirred for 1 hour using a 3-1 motor (HEIDON BL-600 model, SUS propeller, 100 rpm) and then allowed to stand. Then, a Teflon (registered trademark) membrane filter (mesh 1 μm) was used for vacuum filtration to prepare a 10 g / m 2 The sheet is filtered and dried in a ventilated oven at 70°C until the moisture content reaches 10% by mass or less, to obtain treated cellulose microfibers. Here, the water content is measured by the following method. 2.00 g of the cellulose sample is introduced into a glass weighing bottle, dried at 60°C for 15 hours and then dried at 105°C for 2 hours. After reaching a constant weight in the dryer, the weight is measured and the water content is calculated by the following formula. Water content (mass %) = (sample weight before drying - sample weight after drying) / (sample weight before drying) × 100
[0306] [Determination of halogen content]
[0307] 50 mg of the above-mentioned treated cellulose microfibers are measured in a quartz sample boat. The sample boat is placed in an electric furnace (manufactured by Mitsubishi Chemical Analytics Co., Ltd.) and burned at 1000°C. The gas generated by the combustion passes through a cooling section to room temperature, passes through a fluororesin tube, and is bubbled in an absorbent (the absorbent is prepared by dissolving 10 mg / L of tartaric acid ions, 600 mg / L of hydrogen peroxide, 2.7 mmol / L of sodium carbonate, and 0.3 mmol / L of sodium bicarbonate in ion exchange water). The absorbent is passed through a fluororesin tube, and the halogen is quantified using an ion chromatograph (INTEGRIONCT type manufactured by THERMOPFISHER). In addition, the quantification is based on a calibration curve made using samples of various halogen contents. At this time, the water content obtained by the above measurement is subtracted from the treated cellulose microfibers. Finally, the value (mass ppm) converted to the unit dry mass (i.e., the water-free state) of the treated cellulose microfibers is used as the halogen content of the cellulose microfibers of this embodiment.
[0308] Regarding the halogen that the cellulose microfibers of the present embodiment may contain, in one embodiment, it may be in the form of a compound (i.e., a halogen compound) containing fluorine, chlorine, bromine, iodine, and / or astatine. The halogen compound may be a halide (i.e., a compound of a halogen and an element with a lower electronegativity than the halogen), a halogen salt, etc., and may be an inorganic halogen compound or an organic halogen compound. Considering the bleaching process in the manufacturing process of the cellulose raw material, the cellulose microfibers contain fluorine and / or chlorine among the halogens in most cases, and contain chlorine in particular. In the case of using a cellulose raw material with a high halogen content, the advantages brought about by reducing the halogen content in the manufacturing process of the cellulose microfibers are more significant.
[0309] In one embodiment, the low-halogen cellulose microfibers are chemically modified cellulose microfibers.
[0310] The cellulose raw material for obtaining low-halogen cellulose microfibers is derived from plants in one embodiment, and is coniferous tree chips, broadleaf tree chips, or non-wood cellulose raw materials (cotton, hemp, bagasse, kenaf, bamboo, straw, etc.) in another embodiment. Preferably, a cellulose raw material with high I-type crystallinity is used.
[0311] In addition, in order to suppress the discoloration and property degradation caused by heat when the cellulose microfibers are composited with the resin, the cellulose raw material used to obtain the low-halogen cellulose microfibers preferably has a glucose content of 90% by mass or more, more preferably 91% by mass or more, and further preferably 93% by mass or more based on the constituent sugar analysis. The upper limit of the glucose content is not particularly limited, but considering the limit of impurities (e.g., components other than polysaccharides, such as oil components, various contaminants, etc.) that may be mixed in during the harvest of the cellulose raw material or the refining process or the manufacturing process of the cellulose microfibers, it is preferably 99.5% by mass or less.
[0312] The glucose content based on the constituent sugar analysis is not limited to being high in the cellulose raw material, but is preferably high in the cellulose microfibers. The glucose content of the cellulose microfibers is preferably 85% by mass or more, more preferably 90% by mass or more, and the upper limit is not particularly limited, but in one embodiment is 99.5% by mass or less.
[0313] In one embodiment, the cellulose raw material used to obtain the low-halogen cellulose microfibers can be a plant-derived substance in the above-mentioned refined cellulose fibers, that is, it can be a substance obtained by undergoing the above-mentioned process from coniferous tree chips, broadleaf tree chips or non-wood cellulose raw materials (cotton-derived, hemp-derived, bagasse-derived, kenaf-derived, bamboo-derived, straw-derived, etc.). Among these, cellulose raw materials derived from cotton (lint or cottonseed linters) are preferred, and cottonseed linters pulp is particularly preferred, from the aspects of higher cellulose purity, ease of industrial acquisition, and quality stability. In one embodiment, the cellulose raw material used to obtain the low-halogen cellulose microfibers can be the above-mentioned recycled material, preferably recycled cotton.
[0314] In addition, the following treatments are effective for reducing the halogen content in the cellulose raw material: the cellulose raw material or the above-mentioned purified cellulose raw material (e.g., purified pulp) is further immersed in water and subjected to heat treatment at a temperature of 100°C or higher; and the cellulose raw material or the above-mentioned purified cellulose raw material is immersed in a strong alkali aqueous solution (alkali concentration: 1% to 10% by mass) such as sodium hydroxide aqueous solution, left to stand or stirred for a certain period of time in the range of 0°C to 60°C, and then repeatedly washed with water. In addition, enzyme treatment is also effective for obtaining a purified cellulose raw material with high purity, which is a treatment in which a hemicellulolytic enzyme such as xylanase or mannanase or a cellulase is allowed to act in the range of 35°C to 55°C. In particular, a combination of two or more of the above-mentioned heat treatment, alkali treatment, and enzyme treatment is also effective for obtaining a purified cellulose raw material with higher purity. These treatments can not only reduce the load of the micronization treatment, but also discharge impurity components such as lignin and hemicellulose existing on the surface and in the gaps of the microfibrils constituting the cellulose raw material into the aqueous phase, which has the effect of improving the cellulose purity of the refined cellulose raw material, and can therefore be very effective.
[0315] (Halogen content of cellulose raw materials)
[0316] From the perspective of achieving the above-mentioned halogen content and the whiteness described later in the cellulose fiber, the halogen content (chlorine content in one embodiment) in the cellulose raw material for fiber opening is preferably 300 mass ppm or less, more preferably 250 mass ppm or less, further preferably 200 mass ppm or less, particularly preferably 150 mass ppm or less, and particularly preferably 100 mass ppm or less. The halogen content (chlorine content in one embodiment) of the cellulose raw material is preferably as low as possible, but from the perspective of the manufacturing efficiency of the cellulose microfibers, it can be 10 mass ppm or more, or 25 mass ppm or more in one embodiment. In addition, the above-mentioned halogen content is the amount per unit dry mass of the cellulose raw material measured by the same method as the above-mentioned method in the cellulose microfibers.
[0317] <Whiteness>
[0318] The whiteness of cellulose microfibers, especially low-halogen cellulose microfibers, is preferably 50% or more. The whiteness referred to herein refers to the value measured using a spectroscopic whiteness meter / colorimeter (model PF700 manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with the "ISO whiteness diffused blue light reflectance measurement method for paper, cardboard and pulp (JIS P8148, ISO 2470)". When the cellulose raw material or cellulose microfibers are obtained in the form of sheets, they are used directly for the measurement. On the other hand, in a wet state, the cellulose raw material or cellulose microfibers are mixed at a basis weight of 50 g / m 2 The above method utilizes a suction filtration device equipped with a polytetrafluoroethylene (PTFE) membrane filter for papermaking, and is dried at 80°C until the equilibrium moisture is reached to make a cellulose sheet, and the cellulose sheet is used to measure the whiteness using the above-mentioned device. The higher the whiteness, the better the heat resistance of the cellulose microfibers, so the strength, elastic modulus, and dimensional stability of the resin composition obtained by melt mixing and resin compounding are improved during mechanical recovery, so it is preferred. The whiteness of the cellulose microfibers is more preferably 60% or more, further preferably 70% or more, particularly preferably 80% or more, especially preferably 90% or more, and most preferably 95% or more. The larger the value, the more the effect of the present embodiment is improved, so the upper limit is not limited, and as the range substantially obtained, it is preferably 99% or less.
[0319] In order to achieve the whiteness of the above-mentioned cellulose microfibers, the cellulose raw material is preferably subjected to a bleaching treatment or the like before the fibrillation treatment. The fibrillation process of the present embodiment does not significantly reduce the whiteness, so the whiteness of the cellulose raw material provided for fibrillation is consistent with the whiteness of the cellulose microfibers. That is, the whiteness of the cellulose raw material is preferably 50% or more, more preferably 60% or more, further preferably 70% or more, particularly preferably 80% or more, especially preferably 90% or more, and most preferably 95% or more. The larger the value, the greater the effect of the present embodiment, so the upper limit is not limited, and as a substantially obtained range, it is preferably 99% or less.
[0320] <Control of halogen content>
[0321] (Method for bleaching cellulose raw materials)
[0322] In one embodiment, as the bleaching method of the cellulose raw material, at least one selected from the group consisting of chlorine treatment, alkali extraction treatment, hypochlorite treatment, chlorine dioxide treatment, oxygen bleaching treatment, hydrogen peroxide bleaching treatment, and ozone bleaching treatment can be used.
[0323] The chlorine treatment (hereinafter also referred to as “C” treatment) is a bleaching method using chlorine gas, and is a treatment for solubilizing lignin in a plant-derived cellulose raw material (typically unbleached pulp) by chlorinating the lignin.
[0324] The alkali extraction treatment (hereinafter also referred to as “E” treatment) is a treatment for dissolving and extracting alkali-soluble chlorinated lignin using an alkali (sodium hydroxide or the like).
[0325] The hypochlorite treatment (hereinafter also referred to as "H" treatment) is a treatment for bleaching carbohydrates such as cellulose and hemicellulose using sodium hypochlorite.
[0326] The chlorine dioxide treatment (hereinafter also referred to as "D" treatment) is a treatment for selectively decomposing and removing lignin without disintegrating carbohydrates using chlorine dioxide.
[0327] The oxygen bleaching treatment (hereinafter also referred to as "O" treatment) is a treatment for performing oxygen-based oxidative decomposition and extraction of lignin.
[0328] The hydrogen peroxide bleaching treatment (hereinafter also referred to as "P" treatment) is a treatment for performing oxidative decomposition and extraction of lignin based on hydrogen peroxide.
[0329] The ozone bleaching treatment (hereinafter also referred to as "Z" treatment) is a treatment for performing oxidative decomposition and extraction of lignin by ozone.
[0330] As an effective combination of bleaching methods, CEH treatment, CEHH treatment, CEHD treatment, CEHED treatment, CEHDED treatment, and CEDED treatment can be cited. In addition, the arrangement of these letters indicates the order of each treatment, but the order can also be changed according to the purpose. In addition, C / D treatment (here, " / " means that the two treatments sandwiched therein are performed simultaneously) in which a part of the chlorine used in the chlorine treatment is replaced by chlorine dioxide; and C / D treatment in which C in the above-mentioned sequential treatment is replaced by C / D treatment; E / O treatment or E / P treatment in which a small amount of oxygen or hydrogen peroxide is added to enhance the alkalinity during E treatment; and E in the above-mentioned sequential treatment is replaced by E / O treatment or E / P treatment; treatment in which oxygen is further added to the E / O treatment or E / P treatment; and E in the above-mentioned sequential treatment is replaced by E / OH treatment, etc., which can be appropriately combined according to the use and purpose.
[0331] Instead of the above treatments, equivalent ECF (Elemental Chlorine Free, DE / ODD, E / OEDP) treatment, TCF (Total Chlorine Free, E / OP-ZP) treatment, etc. may be used.
[0332] In order to reduce the halogen concentration in the cellulose raw material, it is preferred to use a treatment that does not use chlorine as much as possible. From this point of view, alkali extraction treatment, oxygen treatment, ozone treatment, chlorine dioxide treatment, hypochlorite treatment, or a combination of these, ECF treatment, or TCF treatment is preferred. In order to achieve a high degree of polymerization of the cellulose raw material, that is, to achieve high whiteness while maintaining strength, alkali extraction treatment, ozone treatment, ECF treatment, or TCF treatment is preferred, and ECF treatment or TCF treatment is more preferred.
[0333] The fibrillation of the cellulose raw material for obtaining low-halogen cellulose microfibers can be performed on the cellulose raw material that has undergone or has not undergone the pretreatment of the present embodiment, and is preferably performed on the cellulose raw material that has undergone the pretreatment. In one embodiment, the cellulose raw material having a specific fiber length adjusted to an average fiber length of less than 3 mm and / or a fiber length of more than 3 mm in a ratio of less than 20% by the pretreatment process is dispersed in an aqueous medium, and the obtained dispersion is subjected to the following treatment, thereby performing a beating treatment. As the aqueous medium, water itself can be cited; or a mixed medium of one or more organic solvents selected from monohydric alcohols such as ethanol, n-propanol, isopropanol, butanol, polyhydric alcohols such as ethylene glycol, diethylene glycol, glycerol, ketones such as acetone, nitrile solvents such as acetonitrile, pyrrolidone solvents, etc. and water. The mixing ratio of the organic solvent in the above-mentioned mixture of organic solvent and water is preferably less than 50% by mass, more preferably less than 30% by mass, and particularly preferably less than 20% by mass. The higher the water ratio, the better the fiber opening property, and the higher the organic solvent ratio, the more the aggregation of fine fibers in the drying process after fiber opening can be suppressed. Therefore, the ratio of the organic solvent is preferably set in consideration of the balance between fiber opening property and aggregation suppression. Beating is a wet treatment, which is different from the pulverization as a pretreatment of this embodiment, and the fiber length of the cellulose to be treated is different, which is different from the grinding as a pretreatment of this embodiment.
[0334] In the beating treatment, the cellulose raw material (such as pulp sheets) is dispersed in an aqueous medium using a pulper or a homogenizer as needed, and then finely divided using a pulping device such as a refiner, a disc refiner, a high-pressure homogenizer, a water jet, a disc mill, a ball mill, a bead mill, a mass colloider, a homogenizer, etc. The beating treatment can be performed in one stage or in multiple stages. In the case of performing the treatment in multiple stages, the same device can be used multiple times, or different devices can be used in combination.
[0335] In addition, before the beating treatment, it is preferred to use the above-mentioned pulper or homogeneous mixer to evenly disperse the cellulose raw material in the aqueous medium. In particular, when the cellulose raw material is first chemically modified and then subjected to the beating treatment, due to the reduction in the hydrophilicity of the cellulose raw material, it is preferred to use a mixer such as a homogeneous mixer with a circumferential speed of 10 m / s or more (preferably 20 m / s or more, more preferably 25 m / s or more) in one mode and 90 m / s or less (preferably 80 m / s or less, more preferably 50 m / s or less) for the dispersion treatment. By reducing lumps and the like during the dispersion treatment, uniform cellulose microfibers can be obtained by uniform beating treatment. It should be noted that as the water in the aqueous medium used at this time, high-purity water such as distilled water and ion-exchanged water can be effective.
[0336] <Applications of cellulose microfibers>
[0337] The cellulose microfibers in this embodiment have a moderate fineness that is neither too thick nor too thin, and have good uniformity, and can be suitably used as reinforcing fillers for fiber-reinforced resins. Furthermore, they can also be used as prepreg materials by molding into sheets and impregnating them with resins, and used in building materials such as concrete.
[0338] Fiber-reinforced resin
[0339] One embodiment of the present invention provides a fiber-reinforced resin comprising the cellulose microfibers disclosed herein and a resin. In one embodiment, the resin is impregnated into the cellulose microfibers. The method for obtaining the fiber-reinforced resin is not particularly limited, and the following methods can be cited: a method of mixing a resin dissolved in a solvent with cellulose microfibers and drying the solvent; a method of mixing cellulose microfibers with a dispersant and the like, drying the mixture, and adding the mixture to a resin that has been melt-kneaded using a twin-screw extruder; a method of wet-papering the cellulose microfibers, making a sheet, and then impregnating the sheet with a resin to form a composite; a method of mixing cellulose microfibers with synthetic fibers, forming a nonwoven fabric by, for example, wet-papering, and then hot-pressing the mixture above the melting point of the synthetic fibers. In one embodiment, the method for producing a fiber-reinforced resin may be as follows: a method in which cellulose microfibers are mixed with synthetic fibers (synthetic staple fibers in one embodiment), and the mixture is formed into a non-woven fabric by wet papermaking, and the non-woven fabric is then molded by hot pressing (hereinafter referred to as the non-woven fabric method); a method in which a slurry of cellulose microfibers is prepared, the slurry is supplied to a known dryer such as a spray dryer and a vacuum dryer to form a dry powder, and the dry powder is then added when the resin is melt-kneaded using a twin-screw extruder; and the like.
[0340] <Resin>
[0341] The resin (i.e., matrix resin) used in the present embodiment can be a thermosetting resin, a photocurable resin, or a thermoplastic resin. Among them, for the reason that the cellulose microfibers of the present embodiment are excellent in heat resistance, thermoplastic resins are preferred. The cellulose microfibers of the present embodiment can also be suitably compounded with resins having, for example, a melting point of more than 200°C and a melt mixing temperature of more than 250°C. As thermoplastic resins, for example, styrene resins, acrylic resins, aliphatic or aromatic polycarbonate resins, aliphatic or aromatic polyester resins (polyethylene terephthalate, polylactic acid, etc.), chain polyolefin resins, cyclic olefin resins, aliphatic or aromatic polyamide resins, polyphenylene ether resins, polyvinyl alcohol resins, polyoxyalkylene resins, polyphenylene sulfide resins, thermoplastic polyimide resins, polyacetal resins, polysulfone resins, amorphous fluorine resins, epoxy resins, etc. These thermoplastic resins can be used alone or contain more than two kinds.
[0342] More preferred examples of thermoplastic resins are one or more selected from the group consisting of polyolefins (polyethylene, polypropylene, etc.), polyesters (polyethylene terephthalate, polylactic acid, etc.), polyamides (PA6, PA66, PA4, PA12, aromatic polyamides, etc.), polyacrylonitrile, polymethyl methacrylate, polystyrene, polyvinyl alcohol, polyphenylene ether, polyoxymethylene, and polyphenylene sulfide.
[0343] The melting point of the thermoplastic resin may be 80° C. or more, 90° C. or more, 100° C. or more, 120° C. or more, 140° C. or more, 160° C. or more, 180° C. or more, or 200° C. or more in one embodiment, and may be 300° C. or less, 250° C. or less, or 230° C. or less in one embodiment. In the present disclosure, the melting point refers to the peak top temperature of an endothermic peak (when there are two or more, the peak on the highest temperature side) that appears when the temperature is increased at a temperature increase rate of 10° C. / min using a differential scanning calorimeter (DSC).
[0344] In the case of using the nonwoven fabric method, the synthetic fiber needs to have a melting point because the synthetic fiber melts during hot pressing. As the resin having a melting point, specifically, polyethylene, polystyrene, polypropylene, ABS resin, polycarbonate, polyamide 6, polyamide 12, polyamide 66, polyvinyl chloride, methacrylic resin, polyvinyl alcohol, polyvinylidene chloride, polyvinylidene fluoride, polyetherimide, polyoxymethylene, polysulfone, polyethylene terephthalate, polyphenylene sulfide and other known resins can be cited. Even if it is other than these, as long as it is a resin with a melting point. The melting point of these resins is preferably below 250°C. This is because the cellulose fine fibers mainly composed of type I crystals begin to significantly reduce in weight due to thermal decomposition or oxidation between 260°C and 300°C, and have a tendency to color the composite while losing the original strength of cellulose. From the perspective of molding the fiber-reinforced resin by heating and melting (e.g., hot pressing in the nonwoven fabric production method) while suppressing the decomposition of cellulose, the melting point of the resin is preferably low, preferably 250° C. or less, more preferably 230° C. or less. In consideration of heat resistance during use, in one embodiment, the melting point of the resin may be 80° C. or more.
[0345] <Contents of Cellulose Microfibers and Resin in Fiber-Reinforced Resin>
[0346] The content of the cellulose microfibers contained in the fiber-reinforced resin is preferably 1% by mass or more, more preferably 5% by mass or more, further preferably 10% by mass or more, and further preferably 20% by mass or more, from the viewpoint of good effect as a reinforcing fiber. If the content of the cellulose microfibers is too high, there is a tendency that the continuous layer of the resin in the fiber-reinforced resin is disconnected and the performance of the fiber-reinforced resin is reduced, and in one embodiment, the fluidity of the fiber-reinforced resin during molding is low and molding defects are likely to occur, so the upper limit is preferably 60% by mass or less, more preferably 50% by mass or less, and further preferably 40% by mass or less.
[0347] From the perspective of easily improving the strength of the fiber-reinforced resin by forming a continuous layer of the matrix resin, the resin content in the fiber-reinforced resin is preferably 50 mass % or more, or 60 mass % or more, and from the perspective of not reducing the content of the cellulose microfibers too much and obtaining a good reinforcement effect based on the cellulose microfibers, the content is preferably 99 mass % or less, or 95 mass % or less, or 90 mass % or less.
[0348] <Compounding by nonwoven fabric method>
[0349] As a method for obtaining a fiber-reinforced resin containing cellulose microfibers and a resin, for example, a nonwoven fabric method can be used. Regarding the nonwoven fabric, one embodiment contains the cellulose microfibers disclosed in the present invention, and another embodiment contains the cellulose microfibers disclosed in the present invention and synthetic fibers. According to the composite rule in the fiber-reinforced resin, the strength of the fiber-reinforced resin significantly depends on the orientation of the fibers in the resin and the continuity of the fibers. Controlling the orientation and continuity of the fibers is advantageous in controlling the strength of the fiber-reinforced resin. By using the nonwoven fabric method, the cellulose microfibers in the resin are continuously layered by hydrogen bonding, and the continuous layers become a structure in which the continuous layers are highly oriented in the two-dimensional plane direction, and a material with excellent strength can be obtained.
[0350] From the same viewpoint as described above, a preferred example of the content of the fine cellulose fibers in the nonwoven fabric is the same range as the content of the fine cellulose fibers in the fiber-reinforced resin.
[0351] The content of synthetic fibers in the nonwoven fabric is preferably 50% by mass or more, or 60% by mass or more, from the perspective of being able to form a continuous layer by melting the synthetic fibers during the manufacture of the fiber-reinforced resin, thereby easily improving the strength of the fiber-reinforced resin; and from the perspective of having a small dehydration load in the papermaking process during the manufacture of the nonwoven fabric, and preferably 99% by mass or less, or 95% by mass or less, or 90% by mass or less, from the perspective of obtaining a good reinforcing effect based on the cellulose microfibers without reducing the content of the cellulose microfibers too much. The content of synthetic fibers can be set arbitrarily for the purpose of adjusting the strength, elastic modulus, and breaking strain, but is more preferably 60% by mass or more and 90% by mass or less.
[0352] The following is an explanation of a method for producing a fiber-reinforced resin by a nonwoven fabric method. In one embodiment, the nonwoven fabric method includes the following steps: a slurry preparation step, in which cellulose microfibers and synthetic fibers are stirred and mixed in a medium containing water to obtain a slurry; a papermaking step, in which a wet molded body (wet nonwoven fabric) is obtained from the slurry by a wet papermaking method; a drying step, in which the wet molded body is dried to obtain a nonwoven fabric; and a hot pressing step, in which the nonwoven fabric is hot pressed at a temperature above the melting point of the synthetic fibers in the nonwoven fabric to obtain a fiber-reinforced resin.
[0353] (synthetic fiber)
[0354] The synthetic fibers used in the nonwoven fabric production method are synthetic staple fibers in one embodiment. Synthetic staple fibers refer to short fibers obtained by cutting synthetic polymer fibers into any fiber length, and are sometimes referred to as chopped fibers or simply short fibers. Regarding synthetic staple fibers, in one embodiment, they may be fibers with an average fiber length of less than 20 mm, or in one embodiment, they may be fibers with an average fiber length of less than 10 mm. Synthetic staple fibers may be fibrillated fibers obtained by fibrillating fibers cut after spinning by beating treatment or the like, or may be fibrillated fibers obtained by spinning fibers with a multi-branch structure obtained by spinning based on flash spinning or electrospinning and then cutting them. Preferred examples of the material of the synthetic fibers are as exemplified above for the resin.
[0355] Regarding the average fiber diameter of the synthetic fibers, from the perspective of the ease of obtaining the synthetic fibers, it is preferably 0.1 μm or more, or 0.3 μm or more, or 1.0 μm or more, and from the perspective of being easy to evenly mix with the cellulose microfibers and to easily form a uniform nonwoven fabric based on this, it is preferably 50 μm or less, or 40 μm or less, or 25 μm or less. In the case where the synthetic fibers have a relatively small average fiber diameter (for example, less than 10 μm), the difference in fiber diameter between the cellulose microfibers and the synthetic fibers is small, so the coefficient of variation of air permeability resistance is low, and the uniformity of the structure in the nonwoven fabric is good. On the other hand, in the case where the synthetic fibers have a relatively large average fiber diameter (for example, greater than 40 μm), the difference in fiber diameter between the cellulose microfibers and the synthetic fibers is large, the structural deviation in the nonwoven fabric tends to increase, and the nonwoven fabric has a high basis weight (for example, 200 g / m 2 In the case of above), a good (ie, low) coefficient of variation of air permeability resistance can be shown.
[0356] From the perspective of obtaining nonwoven fabrics and fiber-reinforced resins with good mechanical properties, the average fiber length of the synthetic fibers is preferably greater than 0.5 mm, or greater than 1.0 mm, or greater than 1.5 mm. From the perspective of facilitating uniform dispersion of the cellulose microfibers among the synthetic fibers, the average fiber length is preferably less than 20 mm, or less than 15 mm, or less than 10 mm.
[0357] In addition, the average fiber diameter and average fiber length of the synthetic fiber are measured by the following method. Each synthetic fiber sample is dispersed in water in a manner of 0.01 to 0.1% by mass, and after ultrasonic treatment (several minutes) as needed, it is dropped onto a glass slide, clamped with a cover glass so that air does not enter, and the periphery of the cover glass is sealed with nail polish (the concentration of the aqueous dispersion is adjusted so that the fibers do not tangle with each other during microscopic photography). Thereafter, an image is obtained using a microscope (VHX-7000 manufactured by KEYENCE Co., Ltd., the magnification is adjusted so that the long side of the fiber falls into the image), and the long diameter and short diameter of 100 fibers of each sample are measured, and the averages are respectively averaged, and the average values obtained are used as the average fiber length and average fiber diameter.
[0358] The melting point of the synthetic fiber is preferably 300° C. or less, more preferably 250° C. or less, from the perspective of preventing thermal degradation of the cellulose microfibers during hot pressing. On the other hand, if the melting point is too low, the practicality as a fiber-reinforced resin is low, so the melting point is preferably 90° C. or more, more preferably 160° C. or more.
[0359] As polymers constituting synthetic fibers, the above-mentioned substances as resins can be cited. Among them, preferred polymers are polyamide, polyester (polyethylene terephthalate, polylactic acid, etc.), polyoxymethylene, polyacrylonitrile, etc., from the aspects of high affinity with cellulose microfibers and easy uniform mixing. In addition, polyphenylene sulfide, polyphenylene ether, polyester, aromatic polyamide, etc. are suitable for applications requiring heat resistance.
[0360] The specific steps of the nonwoven fabric production method are shown below. The nonwoven fabric production method includes the following steps: a slurry preparation step, in which cellulose microfibers and synthetic fibers are stirred and mixed in a medium containing water to obtain a slurry; a papermaking step, in which a wet molded body is obtained from the slurry by a wet papermaking method; a drying step, in which the wet molded body is dried to obtain a nonwoven fabric; and a hot pressing step, in which the nonwoven fabric is hot pressed at a temperature above the melting point of the synthetic fibers in the nonwoven fabric to obtain a fiber-reinforced resin.
[0361] (Slurry preparation process)
[0362] In this process, cellulose microfibers and synthetic fibers are stirred in a medium containing water so that the bundled synthetic fibers are monodispersed and highly distributed in the cellulose microfibers. As a stirring device, a known stirring device such as a homogeneous mixer, a stirrer mixer, etc. can be used. Here, from the perspective of increasing the elastic modulus of the fiber-reinforced resin obtained by highly dispersing the cellulose microfibers and synthetic fibers, and increasing the orientation of the cellulose microfibers in the two-dimensional direction to increase the strength and breaking strain, the total value of the solid content concentration of the cellulose microfibers and the synthetic fibers is preferably 3.0% by mass or less, or 1.0% by mass or less, or 0.8% by mass or less, and from the perspective of shortening the filtration time and improving productivity, the total value is preferably 0.05% by mass or more, or 0.1% by mass or more, or 0.25% by mass or more. At this time, in order to improve the dispersibility of the synthetic fibers or improve the miscibility of the synthetic fibers and the cellulose microfibers, a dispersant such as a surfactant or a paper medicine can be used.
[0363] (Papermaking process)
[0364] In this process, the slurry is dehydrated by a wet papermaking method to obtain a wet nonwoven fabric as a wet molded body. In one mode, the slurry is filtered by suction on a porous substrate to dehydrate it. In the papermaking method, any filter material with a pore size that can trap cellulose microfibers and synthetic fibers after the slurry is dehydrated can be used. As specific filter materials, filter paper, filter cloth, metal mesh, etc. can be cited. At this time, by also using a pressing process in which a roller, etc. is used to contact and pressurize the wet molded body from the top in addition to suction filtration, a more effective high dehydration effect can be obtained.
[0365] When using an inclined screen paper machine, a fourdrinier paper machine, a cylinder paper machine or the like as a papermaking device, a flat sheet-like wet molded body with few defects can be obtained appropriately. In addition, by using a metal mold for pulp molding, a wet molded body of a desired shape can be obtained.
[0366] Papermaking can be continuous or batch, and can be used according to the purpose. In the case of obtaining a flat sheet, it is preferable from an industrial point of view to manufacture a long sheet and make it into a roll product form by continuous papermaking using a paper machine in terms of cost. In particular, in the case of continuous papermaking using a paper machine, in the case of ordinary papermaking (for example, papermaking using pulp fibers obtained by beating and synthetic fibers), a tangential stress is generated by the water dispersion of fibers put into the papermaking wire net and the movement of the wire net conveyor belt. The fibers in the water dispersion are oriented along the travel direction of the wire net conveyor belt by the tangential stress. As a result, in the obtained flat sheet, anisotropy of physical properties (strength, elastic modulus, etc.) caused by the orientation of the fibers occurs between the travel direction (machine direction, MD) and the orthogonal direction (transverse direction, TD). In contrast, the continuous papermaking according to this embodiment has an advantageous feature that it is not easy to show a difference in physical properties between the MD direction and the TD direction. This feature is believed to be due to the fact that when a flat sheet as a non-woven fabric is made using a papermaking machine, in an aqueous dispersion containing cellulose microfibers and synthetic fibers fed into the papermaking machine, the cellulose microfibers form isotropic soft agglomerates based on inter-fiber association, and a composite soft agglomerate is formed in which the synthetic fibers are introduced into the soft agglomerate (i.e., integrated). Even if the synthetic fibers have an anisotropic shape, they are introduced into the composite soft agglomerate in a non-oriented state (i.e., in a disordered, non-anisotropic state).
[0367] The composite soft aggregate retains a certain strength and will not disintegrate due to the shear stress based on the belt travel applied to the water dispersion such as the usual papermaking. Therefore, the composite soft aggregate can be formed into a non-anisotropic sheet by directly stacking and dehydrating the synthetic fibers in a non-oriented fixed state on the belt, and then drying them. Usually, in continuous papermaking, the physical property ratio of, for example, tensile strength, tensile elastic modulus, bending strength, bending modulus, linear thermal expansion coefficient, etc. in the MD / TD direction increases according to the traveling speed during papermaking (usually 5m / min or more) (refer to Comparative Example I-8 of the present disclosure). When the flat sheet of the present embodiment is made by the continuous papermaking method, the MD / TD physical property ratio can be made to be 1.6 or less, preferably 1.4 or less, and more preferably 1.2 or less in one mode (refer to Example I-27 of the present disclosure). In addition, the method of the present embodiment shows that even in three-dimensional molding such as pulp molding, it is not easy to show anisotropy in not only the part with high planarity but also the part with high curvature.
[0368] (Drying process)
[0369] In this process, at least the wet molded body is dried to obtain a nonwoven fabric. The drying method is not particularly limited, and it is preferably carried out by using a rotary dryer, a pin tentering machine, or the like, so that the width of the wet molded body becomes a fixed length state, and a fixed-length drying type dryer that can dry a liquid medium is used. By using such a dryer, the internal structure of the nonwoven fabric changes little during drying, and it is easy to control the orientation of the cellulose microfibers in the nonwoven fabric. It should be noted that the air permeability resistance of the nonwoven fabric can be controlled by the composition ratio of the cellulose microfibers and synthetic fibers constituting the slurry, the overall basis weight, the dispersion method of the stock solution, the mixing conditions of various additives, the average fiber diameter of the cellulose microfibers, etc.
[0370] The drying temperature is preferably 45°C or higher, 60°C or higher, 80°C or higher, 85°C or higher, or 90°C or higher from the viewpoint of drying efficiency (particularly from the viewpoint of increasing the evaporation rate of the liquid medium and obtaining good productivity), and preferably 180°C or lower, 150°C or lower, 120°C or lower, 115°C or lower, or 110°C or lower from the viewpoint of preventing the thermal denaturation of the hydrophilic polymer (specifically, cellulose microfibers and other components) constituting the nonwoven fabric, preventing the reduction of energy efficiency that affects the cost, and further preventing the reaction of the reactive crosslinking agent when the reactive crosslinking agent is used. For example, when performing multi-stage drying in which low-temperature drying is first performed at a temperature of 100°C or lower and then drying is performed at a temperature higher than 100°C, it is also effective in obtaining a nonwoven fabric with high uniformity. For example, when a blocked polyisocyanate is used as a reactive crosslinking agent, the above conditions are suitable.
[0371] (Hot pressing process)
[0372] In this process, the nonwoven fabric obtained by the drying process is pressed using a heated mold, thereby melting and flowing the synthetic fibers contained in the nonwoven fabric, filling the gaps, and obtaining a fiber-reinforced resin as a composite of cellulose microfibers and resin. At this time, since the cellulose microfibers will not melt due to heat, a highly oriented state along the two-dimensional surface direction can be maintained inside the nonwoven fabric. The heating temperature only needs to be above the melting point of the synthetic fiber. If it is near the melting point, the viscosity of the resin is high, and gaps may remain inside the composite. Therefore, the heating temperature is preferably higher than the melting point of the synthetic fiber by more than 10°C. In addition, in order to adjust the thickness of the molded body, multiple sheets of nonwoven fabric can also be stacked and provided in the hot pressing process.
[0373] <Melt Kneading Method>
[0374] In one method, a slurry of cellulose microfibers is prepared in the same manner as in the above-mentioned method of the nonwoven fabric production method, and is supplied to a known dryer such as a spray dryer or a vacuum dryer to be made into a dry powder. The dry powder is then added when a resin is melt-kneaded using a twin-screw extruder kneader, thereby manufacturing a fiber-reinforced resin.
[0375] <Applications of fiber-reinforced resins>
[0376] The fiber-reinforced resin, which is a composite of fine cellulose fibers and a resin obtained in this embodiment, is excellent in all mechanical properties including elastic modulus, strength and breaking strain, and can be suitably used in a wide range of applications such as automobile parts, building materials, and home appliances.
[0377] The present disclosure also includes the following groups of items.
[0378] Project Group I
[0379] [1] A cellulose microfiber having at least a surface chemically modified, wherein:
[0380] In the measurement by a fiber shape analyzer, the length-weighted average fiber length of fibers having a fiber length of 100 μm or more is 110 μm or more and 500 μm or less,
[0381] Among fibers having a fiber length of 100 μm or longer, the number frequency of fibers having a length-weighted fiber length of 411 μm or longer is 54% or less.
[0382] [2] The cellulose microfibers according to item 1 above, wherein the microfibers satisfy all of the following parameters when measured by an automatic fiber shape analyzer:
[0383] (1) The average fiber diameter is 42.5 μm or less,
[0384] (2) The fine fiber area ratio is less than 90%,
[0385] (3) Among fibers having a fiber length of less than 100 μm, the number frequency of fibers having a fiber length of 20 μm or more and 56 μm or less is 30% or more and 97% or less, and
[0386] (4) The fibrillation rate is 5% or less.
[0387] [3] The cellulose microfibers according to item 1 or 2 above, wherein the chemical modification is acetylation and the degree of acetylation is 0.5 to 1.3.
[0388] [4] The cellulose microfibers according to any one of items 1 to 3 above, wherein the glucose content in constituent sugar analysis is 90% by mass or more.
[0389] [5] The cellulose microfibers as described in any one of items 1 to 4 above, wherein a 5 ppm by mass DMSO dispersion of the cellulose microfibers is poured and dried, and in a scanning electron microscope (SEM) image of the surface of the obtained sample, the area occupied is less than 15 μm 2 The ratio of the total area occupied by the ultrafine fibers to the total area occupied by the cellulose microfibers is 10% to 80%.
[0390] [6] The cellulose microfibers according to any one of items 1 to 5 above, which have a cellulose I type crystal structure.
[0391] [7] The cellulose microfibers according to any one of items 1 to 6 above, wherein the microfibers have a crystallinity of 60% or more.
[0392] [8] A fiber-reinforced resin comprising the cellulose microfibers according to any one of items 1 to 7 above and a resin having a melting point of 200° C. or higher.
[0393] [9] A nonwoven fabric comprising the cellulose microfibers according to any one of items 1 to 7 above.
[0394]
[10] The nonwoven fabric according to item 9 above, comprising 50% by mass or more of synthetic fibers having a melting point of 300° C. or less.
[0395]
[11] A fiber-reinforced resin comprising the nonwoven fabric according to item 9 above, and a resin impregnated into the nonwoven fabric.
[0396]
[12] A method for producing a fiber-reinforced resin, which is a method for producing a fiber-reinforced resin comprising cellulose microfibers and a resin, wherein:
[0397] The manufacturing method comprises the step of hot-pressing the nonwoven fabric described in item 10 to obtain a fiber-reinforced resin.
[0398] The heat pressing is performed at a temperature above the melting point of the synthetic fiber.
[0399] Project Group II
[0400] [1] A cellulose microfiber that satisfies all of the following parameters when measured by an automatic fiber shape analyzer:
[0401] (i) the average fiber length is not less than 130 μm and not more than 350 μm,
[0402] (ii) the average fiber diameter is 35 μm or less,
[0403] (iii) the microfiber area ratio is 75% or less,
[0404] (iv) among fibers having a fiber length of less than 100 μm, the number frequency of fibers having a fiber length of 20 μm or more and 56 μm or less is 75% or less,
[0405] (v) among fibers having a fiber length of 100 μm or more, the number frequency of fibers having a fiber length of 411 μm or more is 30% or less, and
[0406] (vi) The fibrillation rate is 5.0% or less.
[0407] [2] The cellulose microfibers according to item 1 above, wherein the inverse number 1 / γ of the yield strain (γ) in a strain dispersion measurement in a water-dispersed slurry having a concentration of 0.75 mass % is 200 or more.
[0408] [3] The cellulose microfibers according to item 1 or 2 above, wherein the zeta potential is from -50 mV to 50 mV.
[0409] [4] A fiber-reinforced resin comprising 1.0 mass % or more of the cellulose microfibers according to any one of items 1 to 3 above and a resin.
[0410] [5] A nonwoven fabric comprising 1.0 mass % or more of the cellulose fine fibers according to any one of items 1 to 3 above.
[0411] [6] The nonwoven fabric according to item 5 above, comprising 50% by mass or more of synthetic fibers having a melting point of 250° C. or less.
[0412] [7] A method for producing a fiber-reinforced resin, which is a method for producing a fiber-reinforced resin comprising cellulose microfibers and a synthetic resin, wherein:
[0413] The production method comprises the steps of hot-pressing a nonwoven fabric containing cellulose microfibers and synthetic fibers to obtain a fiber-reinforced resin.
[0414] The nonwoven fabric is the nonwoven fabric described in item 5 or 6 above,
[0415] The heat pressing is performed at a temperature above the melting point of the synthetic fiber.
[0416] Project Group III
[0417] [1] A cellulose microfiber derived from a plant and having a halogen content (more specifically, a content of halogen bound to cellulose) of 250 ppm by mass or less.
[0418] [2] The cellulose microfibers according to item 1 above, wherein the degree of whiteness is 50% or more.
[0419] [3] A method for producing cellulose microfibers, which is the method for producing cellulose microfibers according to item 1 or 2 above, comprising the step of fiberizing a cellulose raw material having a halogen content (more specifically, a content of halogen bound to cellulose) of 300 ppm by mass or less.
[0420] [4] The method for producing fine cellulose fibers according to item 3 above, wherein the cellulose raw material is a chemically modified product.
[0421] [5] The method for producing fine cellulose fibers according to item 4 above, wherein the chemically modified product is an acetylated product.
[0422] [6] The method for producing fine cellulose fibers according to any one of items 3 to 5 above, wherein the cellulose raw material is derived from cotton.
[0423] [7] The method for producing cellulose microfibers according to any one of items 3 to 6 above, wherein the fiber opening is performed by beating treatment using a disc refiner.
[0424] [8] A resin composition comprising the cellulose microfibers according to item 1 or 2 above and a resin.
[0425] [9] A method for producing a resin composition, comprising the following steps:
[0426] A step of obtaining fine cellulose fibers by the method described in any one of items 3 to 7 above; and
[0427] The step of mixing the cellulose microfibers with a resin to obtain a composition.
[0428] Example
[0429] The present invention will be specifically described below based on Examples and Comparative Examples, but the present invention is not limited to these Examples.
[0430] Example I:
[0431] 《Measurement Method》
[0432] [Fiber shape automatic analyzer measurement]
[0433] Using an automatic shape analyzer (MorfiNeo manufactured by TechPap), various properties of the cellulose microfibers were evaluated in the following order.
[0434] 1. Disperse cellulose microfibers in pure water to prepare 1 L of aqueous dispersion. Here, the final solid content concentration of the cellulose microfibers is 0.003 to 0.005% by mass. It should be noted that for aqueous dispersions of cellulose microfibers less than 2% by mass before dilution (i.e., Preparation Examples 6, 7, and 11), simple mixing was performed using a spatula or the like, and for aqueous dispersions of 2% by mass or more, aqueous fiber cakes or powders (i.e., Preparation Examples 1 to 5, 8 to 10, 12, and Comparative Preparation Examples 1 to 7), a high shear homogenizer (manufactured by IKA, trade name "ULTRA-TURRAX T18") was used for dispersion treatment under the treatment conditions of a rotation speed of 25,000 rpm × 5 minutes. Since any of the manufacturing examples are dispersed in a medium other than water, the dispersion treatment is carried out in a sufficient amount of pure water using the above-mentioned high shear homogenizer under the treatment conditions: rotation speed of 25,000 rpm×5 minutes, and then the medium is removed by means of suction filtration, and the dispersion treatment is carried out again in pure water using the above-mentioned high shear homogenizer under the treatment conditions: rotation speed of 25,000 rpm×5 minutes so that the final solid content concentration is 0.003 to 0.005% by mass, thereby replacing the medium with water.
[0435] 2. The aqueous dispersion prepared in 1. is supplied to an automatic sampler and measured.
[0436] 3. Output the measurement results in txt format (or csv format).
[0437] 4. Extract or calculate each shape parameter from the measurement results. It should be noted that each parameter uses the following values in the measurement results.
[0438] Mean length-weighted length [μm] of conventional fibers (fibers with a fiber length of 100 μm or more)
[0439] Average fiber length in conventional fibers (fibers with a fiber length of 100 μm or more): Mean arithmetic length [μm]
[0440] Frequency of fibers with a fiber length of 411 μm or longer in regular fibers: calculated from the length-weighted fiber length distribution (μm) of regular fibers.
[0441] Average fiber diameter: Mean fiber width[μm]
[0442] Fine fiber area ratio: Fine content, % in Area
[0443] The number frequency of fibers with a fiber length of 20 μm or more and 56 μm or less among fine fibers (fibers with a fiber length of less than 100 μm): calculated from the fiber length distribution (Fine length, μm:FL) of fine fibers.
[0444] Macro Fibrillation index [%]
[0445] [Specific surface area, and average fiber diameter calculated from the specific surface area]
[0446] About 0.2 g of cellulose microfibers were dried at 120°C for 5 hours under vacuum using a specific surface area and pore distribution measuring device (Nova-4200e, manufactured by Quantachrome Instruments). The adsorption of nitrogen at the boiling point of liquid nitrogen was measured at 5 points in the range of relative vapor pressure (P / P0) of 0.05 to 0.2 (multi-point method). The BET specific surface area (m2) was calculated using the device program. 2 / g), and the measurement is carried out accordingly.
[0447] The average fiber diameter was calculated from the specific surface area using the following formula.
[0448] Since the density of cellulose is 1.5 (g / cm 3 ), so the volume of 1g of cellulose is 6.7×10 -7 (m 3 / g).
[0449] When the converted average fiber diameter of the cellulose microfibers is defined as r (m), the average outer perimeter of the cellulose microfibers = πr, and the average cross-sectional area of the cellulose microfibers = 0.25πr 2 Therefore, the total fiber length per 1g of cellulose microfibers = 6.7 × 10 -7 (m 3 ) / average cross-sectional area (=0.25πr 2 )
[0450] Total surface area = specific surface area (m 2 )=6.7×10 -7 (m 3 ) / average cross-sectional area = 0.25πr 2 )×average outer circumference (=πr)=6.7×10 -7 (m 3 ) / 0.25r.
[0451] So, for example, a specific surface area of 40m 2 The average fiber diameter r of CNF was calculated to be 67 nm.
[0452] [Area occupied by ultra-fine fibers]
[0453] The occupied area ratio was measured by the following procedure using a field emission scanning electron microscope (manufactured by Hitachi, Ltd., FE-SEMRegulus 8220 / 5060FQ).
[0454] 1. A cellulose microfiber aqueous dispersion having a solid content concentration of 0.2 to 2% by mass was diluted with dimethyl sulfoxide (DMSO) to a solid content of 5 ppm by mass, and stirred at 3000 rpm for 30 seconds using a homogenizer (manufactured by IKA, trade name "ULTRA-TURRAX T18") to prepare a DMSO dispersion.
[0455] 2. Osmium plasma coating was performed on a smooth substrate (silicon wafer) and heated to 130° C. on a hot plate.
[0456] 3. 7 μL of the DMSO dispersion was dropped onto the center of the heated smooth substrate, and the substrate was left to dry under heating to fix the cellulose microfibers onto the substrate.
[0457] 4. The obtained substrate with fixed cellulose fine fibers was imaged using a scanning electron microscope (SEM) at an accelerating voltage of 1.5 kV, an observation magnification of 400 times, and a resolution of 400 pixels or more per 100 μm, at four different positions on the substrate.
[0458] 5. Calculate the value of the threshold value of 15 μm based on the number of pixels in the scale bar of the SEM image. 2 A comparable number of pixels.
[0459] 6. Based on the obtained SEM image, use the image processing software ImageJ to create a binary image using the MaxEntropy method.
[0460] 7. Use Analyze Particle of ImageJ to perform particle analysis on the binary image and calculate the area (pixel) of single fiber of cellulose microfibrils.
[0461] 8. The particle analysis results of the four images taken are summed up, and the particles with less than 2 pixels are deleted as noise, and the area smaller than 15μm is used as the threshold. 2 As ultra-fine fibers, the calculated size is less than 15 μm. 2 The ratio of the area of extremely small fibers to the total area of cellulose microfibers.
[0462] [Glucose content]
[0463] The glucose content of cellulose microfibers based on structural sugar analysis was determined according to the following steps, referring to the analysis procedure of the National Renewable Energy Institute of the U.S. Department of Energy (Sluiter, A., Hames, B., Ruiz, R., Scarlata, C., Sluiter, J., Templeton, D., Crocker, D.: Determination of structural carbohydrates and lignin biomass. National Renewable Energy Laboratory (NREL), USA, 2008.).
[0464] 3 ml of 72% sulfuric acid was added to 200 mg (dry basis) of the sample, and the mixture was swollen at 30° C. for 1 hour. Then, 84 ml of pure water was poured into a 125 ml pressure bottle and hydrolyzed at 120° C. for 1 hour. The mixture was then filtered while hot using a 1G-3 glass filter (constant weight at 105° C.), and after solid-liquid separation, the filtrate was fixed to 100 ml, and the constituent sugars (glucose, mannose, xylose) were quantified by high performance liquid chromatography (HPLC) (manufactured by Agilent Technology, 1260 Infinity II).
[0465] [DS]
[0466] The acetyl substitution degree (DS) of the cellulose microfibers was evaluated by the following procedure using an infrared spectrometer (FT / IR-6200 manufactured by JASCO Corporation) and a nuclear magnetic resonance apparatus (NMR) (AVANCE III 500 MHz manufactured by Bruker Corporation).
[0467] The degree of acetyl substitution (DS) is calculated from the peak intensity ratio of the peak derived from acetyl groups to the peak derived from the cellulose skeleton in the reflective infrared absorption spectrum of cellulose microfibers. The peak of the absorption band derived from C=O of acetyl groups appears at 1730 cm -1 The peak of the absorption band of CO based on the cellulose backbone chain appears at 1030 cm -1 Regarding the DS of cellulose microfibers, a correlation curve graph is prepared between the DS obtained by solid NMR measurement of cellulose microfibers described later and the modification rate (IR index 1030) defined by the ratio of the peak intensity of the absorption band based on C=O of the acetyl group to the peak intensity of the absorption band of CO of the cellulose skeleton chain, and the DS is obtained by using a calibration curve calculated based on the correlation curve graph.
[0468] Degree of substitution DS = 4.13 × IR index (1030)
[0469] Regarding the method for calculating the DS of cellulose microfibers based on solid-state NMR, the cellulose microfibers after freeze-crushing were subjected to 13 C solid NMR measurement, the area intensity (Inf) of the signal attributed to one carbon atom derived from the modifying group relative to the total area intensity (Inp) of the signals attributed to carbons C1-C6 derived from the pyranose ring of cellulose appearing in the range of 50 ppm to 110 ppm was calculated by the following formula.
[0470] DS=(Inf)×6 / (Inp)
[0471] Since the modification group was an acetyl group, the signal of 23 ppm attributed to -CH 3 was used.
[0472] 13 The conditions for C solid NMR measurement are as follows.
[0473] Device: Bruker Biospin Avance500WB
[0474] Frequency: 125.77MHz
[0475] Determination method: DD / MAS method
[0476] Waiting time: 75sec
[0477] NMR sample tube: 4mmΦ
[0478] Integration times: 640 times (about 14 hours)
[0479] MAS: 14,500Hz
[0480] Chemical shift standard: glycine (external standard: 176.03 ppm)
[0481] [Crystallinity]
[0482] The crystallinity of the cellulose fine fibers was evaluated by the following method using an X-ray diffraction apparatus (MiniFlexII manufactured by Rigaku Corporation).
[0483] The molecular weight can be determined from the diffraction pattern (2θ / deg.: 10 to 30) of a sample measured by wide-angle X-ray diffraction by the Segal method using the following formula.
[0484] Crystallinity (%) = [I (200) -I (amorphous) ] / I (200) ×100
[0485] I (200) : Diffraction peak intensity based on the 200-plane (2θ=22.5°) in cellulose type I crystals
[0486] I (amorphous) : The halo peak intensity of the amorphous cellulose type I crystal is the peak intensity at an angle 4.5° lower than the diffraction angle of the 200-plane (2θ=18.0°).
[0487] [Whiteness measurement]
[0488] The measurement was performed using a spectrophotometer / colorimeter (PF700 manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with the "ISO whiteness of paper, cardboard and pulp - determination of diffuse blue light reflectance (JIS P8148, ISO 2470)". The cellulose raw material or cellulose microfiber slurry was prepared at a basis weight of 50 g / m 2 The paper was made by using a suction filtration device equipped with a polytetrafluoroethylene (PTFE) membrane filter in the above manner, and dried at 80° C. until the moisture content reached equilibrium, thereby producing a cellulose sheet, which was subjected to the above measurement.
[0489] [Determination of halogen content in cellulose raw material or cellulose microfibers]
[0490] (Immersion and filtration treatment)
[0491] The cellulose raw material or cellulose microfiber was immersed in pure water at 25°C for 48 hours. Specifically, the cellulose raw material or cellulose microfiber was immersed in pure water at a solid content of 2% by mass in a glass beaker with a total capacity of 200 mL, stirred for 1 hour using a 3-1 motor (HEIDON BL-600 model, SUS propeller, 100 rpm) and then allowed to stand. Then, a Teflon (registered trademark) membrane filter (mesh 1 μm) was used for vacuum filtration to prepare a 10 g / m 2 The flakes were filtered and dried in a ventilated oven at 70° C. until the moisture content reached 10% by mass or less, thereby obtaining a treated cellulose raw material or treated cellulose fine fibers.
[0492] (Determination of halogen content)
[0493] 50 mg of the above-mentioned treated cellulose raw material or treated cellulose microfibers are weighed in a quartz sample boat. The sample boat is placed in an electric furnace (manufactured by Mitsubishi Chemical Analytics Co., Ltd.) and burned at 1000°C. The gas generated by the combustion passes through a cooling section to room temperature, passes through a fluororesin tube, and is bubbled in an absorption liquid (the absorption liquid is prepared by dissolving 10 mg / L of tartrate ions, 600 mg / L of hydrogen peroxide, 2.7 mmol / L of sodium carbonate, and 0.3 mmol / L of sodium bicarbonate in ion exchange water). The absorption liquid is passed through a fluororesin tube, and the halogen is quantified using an ion chromatograph (INTEGRION CT manufactured by THERMOPHISHER). In addition, the quantification is performed based on a calibration curve prepared using samples of various halogen contents. At this time, the water content in the treated cellulose raw material or the treated cellulose microfibers is subtracted by the loss on drying method (2.00 g of the cellulose sample is introduced into a glass weighing bottle, dried at 60°C for 15 hours, and then dried at 105°C for 2 hours. After reaching a constant weight in a desiccator, the weight is measured and the water content (mass %) is calculated as follows: (weight of sample before drying - weight of sample after drying) / (weight of sample before drying) × 100). Finally, the value (mass ppm) converted to the dry mass per unit (i.e., water-free state) of the treated cellulose raw material or the treated cellulose microfibers is taken as the halogen content remaining in the cellulose fibers.
[0494] [Heat resistance evaluation: Appearance of fiber-reinforced resin]
[0495] Regarding the appearance of the fiber-reinforced resin sample obtained by kneading the cellulose microfibers with the resin, the case where there was obvious burning was rated as poor, the case where there was slight burning was rated as acceptable, and the case where there was no color change was rated as good.
[0496] [Tensile test]
[0497] Using an injection molding machine with a maximum clamping pressure of 75 tons, a multi-purpose test piece (as a fiber-reinforced resin) in accordance with ISO-37 was molded from the kneaded product, and a tensile test was performed under the conditions in accordance with JIS K6920-2 to measure the tensile strength, tensile elastic modulus, and fracture strain. It should be noted that since polyamide resin changes due to moisture absorption, it was stored in an aluminum moisture-proof bag immediately after molding to suppress moisture absorption.
[0498] [Bending test]
[0499] Regarding the bending test, for the fiber-reinforced resin produced by the injection molding method, a strip with a width of 10 mm, a length of 80 mm, and a thickness of 4 mm was produced; for the plate-shaped fiber-reinforced resin produced by the non-woven fabric method, a strip with a width of 2.5 mm and a length of 50 mm was cut out, and the bending strength, bending modulus, and bending strain were measured under the conditions in accordance with JIS K7171:2008. It should be noted that since polyamide resin changes due to moisture absorption, it was stored in an aluminum moisture-proof bag immediately after molding to suppress moisture absorption.
[0500] [Thermal stability of resin]
[0501] The same multi-purpose test piece as used for the tensile test was placed in a polyethylene bag with a clip, stored at 100°C for 1 month, returned to room temperature for 1 day, and then visually observed. If no visual discoloration was observed, it was rated as good, and if visual discoloration was observed, it was rated as bad.
[0502] [Regeneration of resin]
[0503] The same strips as those used for the bending test were cut into 5 mm Φ or less using a cutter, and processed twice using an ultracentrifugal mill (ZM200 manufactured by Retsch, sieve opening 2 mm Φ, rotation speed 10000 rpm). In each embodiment and comparative example, melt mixing and injection molding were performed using the method described in each example, and after repeating this 5 times, the bending strength was measured. In comparison with the pre-storage, a bending strength retention rate of 90% or more was recorded as good, and less than 90% was recorded as poor.
[0504] Materials used
[0505] [pulp]
[0506] (Cottonseed linter pulp A)
[0507] The length-weighted average fiber length of cotton linter pulp A (hereinafter referred to as pulp A) obtained from Nippon Paper Pulp & Shoji Co., Ltd. as natural cellulose measured by the above-mentioned fiber shape automatic analyzer was 1660 μm.
[0508] (Cotton linter pulp B)
[0509] The length-weighted average fiber length of cotton linter pulp B (hereinafter referred to as pulp B) obtained from Nippon Paper Pulp & Shoji Co., Ltd. as natural cellulose measured by the above-mentioned fiber shape automatic analyzer was 1006 μm.
[0510] (Wood pulp C)
[0511] The length-weighted average fiber length of natural cellulose wood pulp (NBLP) C (hereinafter referred to as pulp C) obtained from Nippon Paper Pulp & Paper Co., Ltd. measured by the above-mentioned fiber shape automatic analyzer was 1315 μm.
[0512] (Acetylated cotton linter pulp D)
[0513] The pulp A was immersed in dimethyl sulfoxide to a pulp concentration of 5 mass%, and 0.1 mass% potassium carbonate was added as a catalyst, and the pulp was fully dispersed and swollen with a stirring blade. The mixture was heated to 60°C, and vinyl acetate was added for acetylation to obtain acetylated cotton linter pulp D (hereinafter referred to as acetylated pulp D).
[0514] (Acetylated cotton linter pulp E)
[0515] The pulp B was immersed in dimethyl sulfoxide to a pulp concentration of 5 mass%, and 0.1 mass% potassium carbonate was added as a catalyst, and the pulp was fully dispersed and swollen with a stirring blade. The mixture was heated to 60°C and vinyl acetate was added for acetylation to obtain acetylated cotton linter pulp E (hereinafter referred to as acetylated pulp E).
[0516] [Cellulose microfiber]
[0517] (Production Example 1)
[0518] Pulp A was immersed in water so that the solid content was 1.5% by mass, and dispersed using a laboratory pulper (manufactured by Aikawa Iron Works Co., Ltd.). The obtained slurry was introduced into a fiber opening device having a single disc refiner (manufactured by Aikawa Iron Works Co., Ltd., SDR14 Lab Refiner pressurized DISK type) and tanks A and B connected by piping with the disc refiner interposed therebetween, and the pulp was fiber-opened. First, the liquid was sent from tank A into which the slurry was put through the disc refiner to tank B for storage. At the stage when the slurry treatment in tank A was completed, the liquid was continuously sent from tank B to tank A through the disc refiner for storage. By this method, the number of times (number of passes) of passing through the disc refiner was controlled to open the fibers. It should be noted that a ball screw jack and a speed reducer were provided as a blade adjustment mechanism of the disc refiner. The deviation amplitude of the distance between blades in the beating process after reaching the target distance between blades was measured by a displacement sensor and was less than 0.005 mm. As the blade of the disc refiner, a blade with a blade width of 4.0 mm and a blade groove ratio of 0.89 (disc blade A) was used, and 30 passes were performed at a distance between blades of 0.25 mm. Then, a blade with a blade width of 0.8 mm and a blade groove ratio of 0.53 (disc blade B) was used, and 30 passes were performed at a distance between blades of 0.25 mm.
[0519] The obtained slurry was treated three times at 80 MPa using a high pressure homogenizer (NS3015H manufactured by Niro Soavi). In the high pressure homogenizer treatment, two tanks were set as in the above-mentioned disc refiner treatment, and the number of passes through the high pressure homogenizer treatment was controlled to perform fiber opening.
[0520] The obtained unmodified cellulose microfiber slurry is filtered under reduced pressure, and the obtained wet cake with a solid content of 18% by mass is placed in a reaction container, and dimethyl sulfoxide (DMSO) is added in such a way that the solid content is 2% by mass, and potassium carbonate equivalent to 0.1% by mass is added, and the mixture is heated to 60°C while being uniformly stirred. Vinyl acetate is added thereto, and acetylation is carried out until the prescribed degree of substitution is reached. After the reaction, 10% by mass of quenching water is added, and pure water with a mass of 50 times the mass of the cellulose solid content is used for stirring and filtering by a pressure filter, and this operation is repeated to fully wash the solvent, etc., to obtain a wet cake of acetylated cellulose microfibers.
[0521] (Production Example 2)
[0522] Pulp A was immersed in water to a solid content of 1.5% by mass in the same manner as in Production Example 1, dispersed in a laboratory pulper, and then subjected to 50 passes of a disc refiner with a blade width of 2.5 mm and a blade groove ratio of 0.36 at a blade spacing of 0.20 mm, and then subjected to 100 passes of a disc refiner with a blade width of 0.6 mm and a blade groove ratio of 0.60 at a blade spacing of 0.10 mm. It should be noted that no high-pressure homogenizer treatment was performed.
[0523] The obtained unmodified cellulose microfiber slurry is filtered under reduced pressure, and the obtained wet cake with a solid content of 18% by mass is placed in a reaction container, and dimethyl sulfoxide (DMSO) is added in such a way that the solid content is 2% by mass, and potassium carbonate equivalent to 0.1% by mass is added, and the mixture is heated to 60°C while being uniformly stirred. Vinyl acetate is added thereto, and acetylation is carried out until the prescribed degree of substitution is reached. After the reaction, 10% by mass of quenching water is added, and pure water with a mass of 50 times the mass of the cellulose solid content is used for stirring and filtering by a pressure filter, and this operation is repeated to fully wash the solvent, etc., to obtain a wet cake of acetylated cellulose microfibers.
[0524] (Production Example 3)
[0525] As in Production Example 1, pulp B was immersed in water so as to have a solid content of 1.5 mass %, dispersed using a laboratory pulper, and then subjected to 50 passes of a disc refiner with a blade having a blade width of 2.5 mm and a blade groove ratio of 0.36 and a blade spacing of 0.20 mm. Thereafter, the refiner was subjected to 50 passes of a disc refiner with a blade width of 0.8 mm and a blade groove ratio of 0.53 and a blade spacing of 0.20 mm.
[0526] The obtained slurry was processed 5 times using a high-pressure homogenizer.
[0527] The obtained unmodified cellulose microfiber slurry is filtered under reduced pressure, and the obtained wet cake with a solid content of 18% by mass is placed in a reaction container, and dimethyl sulfoxide (DMSO) is added in such a way that the solid content is 2% by mass, and potassium carbonate equivalent to 0.1% by mass is added, and the mixture is heated to 60°C while being uniformly stirred. Vinyl acetate is added thereto, and acetylation is carried out until the prescribed degree of substitution is reached. After the reaction, 10% by mass of quenching water is added, and pure water with a mass of 50 times the mass of the cellulose solid content is used for stirring and filtering by a pressure filter, and this operation is repeated to fully wash the solvent, etc., to obtain a wet cake of acetylated cellulose microfibers.
[0528] (Production Example 4)
[0529] Pulp A was immersed in water in the same manner as in Production Example 1 so as to have a solid content of 3.0% by mass, dispersed using a laboratory pulper, and then subjected to 30 passes of a disc refiner using a blade having a blade width of 2.5 mm and a blade groove ratio of 0.36 with a blade spacing of 0.20 mm. Thereafter, the refiner was subjected to 30 passes of a disc refiner using a blade having a blade width of 0.6 mm and a blade groove ratio of 0.60 with a blade spacing of 0.20 mm.
[0530] The obtained slurry was processed 5 times using a high-pressure homogenizer.
[0531] The obtained unmodified cellulose microfiber slurry is filtered under reduced pressure, and the obtained wet cake with a solid content of 18% by mass is placed in a reaction container, and dimethyl sulfoxide (DMSO) is added in such a way that the solid content is 2% by mass, and potassium carbonate equivalent to 0.1% by mass is added, and the mixture is heated to 60°C while being uniformly stirred. Vinyl acetate is added thereto, and acetylation is carried out until the prescribed degree of substitution is reached. After the reaction, 10% by mass of quenching water is added, and pure water with a mass of 50 times the mass of the cellulose solid content is used for stirring and filtering by a pressure filter, and this operation is repeated to fully wash the solvent, etc., to obtain a wet cake of acetylated cellulose microfibers.
[0532] (Production Example 5)
[0533] Pulp A was immersed in water in the same manner as in Production Example 1 so that the solid content was 1.5% by mass, and after being dispersed using a laboratory pulper, a disc refiner was used to perform 100 passes with a blade having a blade width of 2.5 mm and a blade groove ratio of 0.36 at a blade spacing of 0.15 mm, and then 50 passes with a blade having a blade width of 0.8 mm and a blade groove ratio of 0.53 at a blade spacing of 0.15 mm.
[0534] The obtained slurry was processed 10 times using a high-pressure homogenizer.
[0535] The obtained unmodified cellulose microfiber slurry is filtered under reduced pressure, and the obtained wet cake with a solid content of 18% by mass is placed in a reaction container, and dimethyl sulfoxide (DMSO) is added in such a way that the solid content is 2% by mass, and potassium carbonate equivalent to 0.1% by mass is added, and the mixture is heated to 60°C while being uniformly stirred. Vinyl acetate is added thereto, and acetylation is carried out until the prescribed degree of substitution is reached. After the reaction, 10% by mass of quenching water is added, and pure water with a mass of 50 times the mass of the cellulose solid content is used for stirring and filtering by a pressure filter, and this operation is repeated to fully wash the solvent, etc., to obtain a wet cake of acetylated cellulose microfibers.
[0536] (Production Example 6)
[0537] As in Production Example 1, acetylated pulp D was immersed in water so as to have a solid content of 1.5 mass %, dispersed using a laboratory pulper, and then subjected to 75 passes of a disc refiner with a blade having a blade width of 2.5 mm and a blade groove ratio of 0.36 and a blade spacing of 0.05 mm. Thereafter, the refiner was subjected to 40 passes of a disc refiner with a blade width of 0.8 mm and a blade groove ratio of 0.53 and a blade spacing of 0.05 mm.
[0538] The obtained slurry was processed 10 times using a high-pressure homogenizer.
[0539] (Production Example 7)
[0540] Acetylated pulp E was immersed in water to a solid content of 1.5% by mass in the same manner as in Production Example 1, dispersed in a laboratory pulper, and then subjected to 50 passes of a disc refiner with a blade width of 0.8 mm and a blade groove ratio of 0.53 at a blade interval of 0.15 mm. The disc refiner treatment was performed in only one stage, and the obtained pulp was subjected to 10 passes of a high-pressure homogenizer.
[0541] (Production Example 8)
[0542] Pulp A was immersed in water in the same manner as in Production Example 1 so that the solid content was 1.5% by mass, and after being dispersed using a laboratory pulper, a disc refiner was used to perform 100 passes with a blade having a blade width of 2.5 mm and a blade groove ratio of 0.36 at a blade spacing of 0.15 mm, and then 50 passes with a blade having a blade width of 0.8 mm and a blade groove ratio of 0.53 at a blade spacing of 0.15 mm.
[0543] The obtained slurry was processed three times using a high-pressure homogenizer.
[0544] The obtained unmodified cellulose microfiber slurry is filtered under reduced pressure, and the obtained wet cake with a solid content of 18% by mass is placed in a reaction container, and dimethyl sulfoxide (DMSO) is added in such a way that the solid content is 2% by mass, and potassium carbonate equivalent to 0.1% by mass is added, and the mixture is heated to 60°C while being uniformly stirred. Vinyl acetate is added thereto, and acetylation is carried out until the prescribed degree of substitution is reached. After the reaction, 10% by mass of quenching water is added, and pure water with a mass of 50 times the mass of the cellulose solid content is used for stirring and filtering by a pressure filter, and this operation is repeated to fully wash the solvent, etc., to obtain a wet cake of acetylated cellulose microfibers.
[0545] (Production Example 9)
[0546] Pulp A was immersed in water in the same manner as in Production Example 1 so that the solid content was 1.5% by mass, and after being dispersed using a laboratory pulper, a disc refiner was used to perform 100 passes with a blade having a blade width of 2.5 mm and a blade groove ratio of 0.36 at a blade spacing of 0.15 mm, and then 50 passes with a blade having a blade width of 0.8 mm and a blade groove ratio of 0.53 at a blade spacing of 0.15 mm.
[0547] The obtained slurry was processed 5 times using a high-pressure homogenizer.
[0548] The obtained unmodified cellulose microfiber slurry is filtered under reduced pressure, and the obtained wet cake with a solid content of 18% by mass is placed in a reaction container, and dimethyl sulfoxide (DMSO) is added in such a way that the solid content is 2% by mass, and potassium carbonate equivalent to 0.1% by mass is added, and the mixture is heated to 60°C while being uniformly stirred. Vinyl acetate is added thereto, and acetylation is carried out until the prescribed degree of substitution is reached. After the reaction, 10% by mass of quenching water is added, and pure water with a mass of 50 times the mass of the cellulose solid content is used for stirring and filtering by a pressure filter, and this operation is repeated to fully wash the solvent, etc., to obtain a wet cake of acetylated cellulose microfibers.
[0549] (Production Example 10)
[0550] Pulp A was immersed in water in the same manner as in Production Example 1 so as to have a solid content of 1.5% by mass, dispersed using a laboratory pulper, and then subjected to 10 passes of a disc refiner with a blade having a blade width of 2.5 mm and a blade groove ratio of 0.36 and a blade spacing of 0.05 mm. Thereafter, the refiner was subjected to 10 passes of a disc refiner with a blade width of 0.8 mm and a blade groove ratio of 0.53 and a blade spacing of 0.05 mm.
[0551] The obtained slurry was processed 10 times using a high-pressure homogenizer.
[0552] The obtained unmodified cellulose microfiber slurry is filtered under reduced pressure, and the obtained wet cake with a solid content of 18% by mass is placed in a reaction container, and dimethyl sulfoxide (DMSO) is added in such a way that the solid content is 2% by mass, and potassium carbonate equivalent to 0.1% by mass is added, and the mixture is heated to 60°C while being uniformly stirred. Vinyl acetate is added thereto, and acetylation is carried out until the prescribed degree of substitution is reached. After the reaction, 10% by mass of quenching water is added, and pure water with a mass of 50 times the mass of the cellulose solid content is used for stirring and filtering by a pressure filter, and this operation is repeated to fully wash the solvent, etc., to obtain a wet cake of acetylated cellulose microfibers.
[0553] (Production Example 11)
[0554] Acetylated pulp E was immersed in water to a solid content of 1.5% by mass in the same manner as in Production Example 1, dispersed in a laboratory pulper, and then subjected to 40 passes of a disc refiner with a blade width of 0.8 mm and a blade groove ratio of 0.53 at a blade interval of 0.10 mm. The disc refiner treatment was performed in only one stage, and the obtained pulp was subjected to 10 passes of a high-pressure homogenizer.
[0555] (Production Example 12)
[0556] As in Production Example 1, pulp B was immersed in water so as to have a solid content of 1.5 mass %, dispersed using a laboratory pulper, and then subjected to 70 passes of a disc refiner with a blade having a blade width of 2.5 mm and a blade groove ratio of 0.36 at a blade spacing of 0.15 mm, and then subjected to 40 passes of a disc refiner with a blade width of 0.6 mm and a blade groove ratio of 0.60 at a blade spacing of 0.15 mm.
[0557] The obtained slurry was processed 10 times using a high-pressure homogenizer.
[0558] The obtained unmodified cellulose microfiber slurry is filtered under reduced pressure, DMSO is added to the obtained wet fiber cake with a solid content of 18% by mass, and suction filtration is performed after stirring. This operation is repeated twice to remove water. The cellulose microfiber replaced by DMSO is added to the DMSO solution dissolved with maleic anhydride, and the reaction is carried out while heating until the specified degree of substitution is reached. After the reaction, pure water washing, acetone washing, and pure water washing are repeated to remove the solvent, unreacted reagents and by-products to obtain a wet filter cake of maleic acid-modified cellulose microfibers.
[0559] (Manufacturing Comparative Example 1)
[0560] Using the disc refiner and high-pressure homogenizer described in Production Example 1, pulp A was immersed in water so as to have a solid content of 1.5% by mass, dispersed using a laboratory pulper, and then subjected to 20 passes of the disc refiner using a blade having a blade width of 2.5 mm and a blade groove ratio of 0.36 with a blade spacing of 0.30 mm, and then subjected to 50 passes of the disc refiner using a blade having a blade width of 0.8 mm and a blade groove ratio of 0.53 with a blade spacing of 0.35 mm.
[0561] The obtained slurry was treated once using a high-pressure homogenizer.
[0562] The obtained unmodified cellulose microfiber slurry is filtered under reduced pressure, and the obtained wet cake with a solid content of 18% by mass is placed in a reaction container, and dimethyl sulfoxide (DMSO) is added in such a way that the solid content is 2% by mass, and potassium carbonate equivalent to 0.1% by mass is added, and the mixture is heated to 60°C while being uniformly stirred. Vinyl acetate is added thereto, and acetylation is carried out until the prescribed degree of substitution is reached. After the reaction, 10% by mass of quenching water is added, and pure water with a mass of 50 times the mass of the cellulose solid content is used for stirring and filtering by a pressure filter, and this operation is repeated to fully wash the solvent, etc., to obtain a wet cake of acetylated cellulose microfibers.
[0563] (Manufacturing Comparative Example 2)
[0564] Pulp B was immersed in water to a solid content of 1.5% by mass in the same manner as in Production Example 1, dispersed using a laboratory pulper, and then subjected to 120 passes of a disc refiner with a blade width of 2.5 mm and a blade groove ratio of 0.36 at a blade spacing of 0.50 mm, and then subjected to 100 passes of a disc refiner with a blade width of 0.6 mm and a blade groove ratio of 0.60 at a blade spacing of 0.03 mm. It should be noted that no high-pressure homogenizer treatment was performed.
[0565] The obtained unmodified cellulose microfiber slurry is filtered under reduced pressure, and the obtained wet cake with a solid content of 18% by mass is placed in a reaction container, and dimethyl sulfoxide (DMSO) is added in such a way that the solid content is 2% by mass, and potassium carbonate equivalent to 0.1% by mass is added, and the mixture is heated to 60°C while being uniformly stirred. Vinyl acetate is added thereto, and acetylation is carried out until the prescribed degree of substitution is reached. After the reaction, 10% by mass of quenching water is added, and pure water with a mass of 50 times the mass of the cellulose solid content is used for stirring and filtering by a pressure filter, and this operation is repeated to fully wash the solvent, etc., to obtain a wet cake of acetylated cellulose microfibers.
[0566] (Manufacturing Comparative Example 3)
[0567] Pulp C was immersed in water to a solid content of 1.5 mass % in the same manner as in Production Example 1, dispersed in a laboratory pulper, and then subjected to 40 passes of a disc refiner with a blade width of 2.5 mm and a blade groove ratio of 0.36 at a blade interval of 0.35 mm. The disc refiner treatment was performed in only one stage, and the obtained pulp was subjected to two passes of treatment in a high-pressure homogenizer.
[0568] The obtained unmodified cellulose microfiber slurry is filtered under reduced pressure, and the obtained wet cake with a solid content of 18% by mass is placed in a reaction container, and dimethyl sulfoxide (DMSO) is added in such a way that the solid content is 2% by mass, and potassium carbonate equivalent to 0.1% by mass is added, and the mixture is heated to 60°C while being uniformly stirred. Vinyl acetate is added thereto, and acetylation is carried out until the prescribed degree of substitution is reached. After the reaction, 10% by mass of quenching water is added, and pure water with a mass of 50 times the mass of the cellulose solid content is used for stirring and filtering by a pressure filter, and this operation is repeated to fully wash the solvent, etc., to obtain a wet cake of acetylated cellulose microfibers.
[0569] (Manufacturing Comparative Example 4)
[0570] Pulp A was immersed in water to a solid content of 1.5% by mass in the same manner as in Production Example 1, dispersed in a laboratory pulper, and then subjected to five passes of a disc refiner with blades having a blade width of 4.0 mm and a blade groove ratio of 0.89 at a blade spacing of 0.40 mm. The disc refiner treatment was performed in only one stage, and no high-pressure homogenizer treatment was performed.
[0571] The obtained unmodified cellulose microfiber slurry is filtered under reduced pressure, and the obtained wet cake with a solid content of 18% by mass is placed in a reaction container, and dimethyl sulfoxide (DMSO) is added in such a way that the solid content is 2% by mass, and potassium carbonate equivalent to 0.1% by mass is added, and the mixture is heated to 60°C while being uniformly stirred. Vinyl acetate is added thereto, and acetylation is carried out until the prescribed degree of substitution is reached. After the reaction, 10% by mass of quenching water is added, and pure water with a mass of 50 times the mass of the cellulose solid content is used for stirring and filtering by a pressure filter, and this operation is repeated to fully wash the solvent, etc., to obtain a wet cake of acetylated cellulose microfibers.
[0572] (Manufacturing Comparative Example 5)
[0573] As in Production Example 1, pulp C was immersed in water so as to have a solid content of 1.5 mass %, dispersed using a laboratory pulper, and then subjected to 50 passes of a disc refiner with a blade having a blade width of 2.5 mm and a blade groove ratio of 0.36 at a blade spacing of 0.05 mm. Thereafter, the refiner was subjected to 50 passes of a disc refiner with a blade width of 0.8 mm and a blade groove ratio of 0.53 at a blade spacing of 0.03 mm.
[0574] The obtained slurry was processed 20 times using a high-pressure homogenizer.
[0575] The obtained unmodified cellulose microfiber slurry is filtered under reduced pressure, and the obtained wet cake with a solid content of 18% by mass is placed in a reaction container, and dimethyl sulfoxide (DMSO) is added in such a way that the solid content is 2% by mass, and potassium carbonate equivalent to 0.1% by mass is added, and the mixture is heated to 60°C while being uniformly stirred. Vinyl acetate is added thereto, and acetylation is carried out until the prescribed degree of substitution is reached. After the reaction, 10% by mass of quenching water is added, and pure water with a mass of 50 times the mass of the cellulose solid content is used for stirring and filtering by a pressure filter, and this operation is repeated to fully wash the solvent, etc., to obtain a wet cake of acetylated cellulose microfibers.
[0576] (Manufacturing Comparative Example 6)
[0577] As in Production Example 1, pulp A was immersed in water so that the solid content was 1.5% by mass, and after being dispersed using a laboratory pulper, a disc refiner was used to perform 120 passes with a blade having a blade width of 2.5 mm and a blade groove ratio of 0.36 at a blade spacing of 0.03 mm, and then 60 passes with a blade having a blade width of 0.8 mm and a blade groove ratio of 0.53 at a blade spacing of 0.03 mm.
[0578] The obtained slurry was processed 15 times using a high-pressure homogenizer.
[0579] The obtained unmodified cellulose microfiber slurry is filtered under reduced pressure, and the obtained wet cake with a solid content of 18% by mass is placed in a reaction container, and dimethyl sulfoxide (DMSO) is added in such a way that the solid content is 2% by mass, and potassium carbonate equivalent to 0.1% by mass is added, and the mixture is heated to 60°C while being uniformly stirred. Vinyl acetate is added thereto, and acetylation is carried out until the prescribed degree of substitution is reached. After the reaction, 10% by mass of quenching water is added, and pure water with a mass of 50 times the mass of the cellulose solid content is used for stirring and filtering by a pressure filter, and this operation is repeated to fully wash the solvent, etc., to obtain a wet cake of acetylated cellulose microfibers.
[0580] (Manufacturing Comparative Example 7)
[0581] In the production of Comparative Example 7, a single disc refiner was used in which the amount of movement when the flow channel portion was pulled in the thrust direction was 0.3 mm.
[0582] Pulp A was immersed in water so as to have a solid content of 1.5% by mass, dispersed using a laboratory pulper, and then subjected to 80 passes of a disc refiner with a blade having a blade width of 2.5 mm and a blade groove ratio of 0.36 at a blade spacing of 0.20 mm. Thereafter, the refiner was subjected to 100 passes of a disc refiner with a blade width of 0.8 mm and a blade groove ratio of 0.53 at a blade spacing of 0.10 mm.
[0583] The obtained slurry was processed 5 times using a high-pressure homogenizer.
[0584] The obtained unmodified cellulose microfiber slurry is filtered under reduced pressure, and the obtained wet cake with a solid content of 18% by mass is placed in a reaction container, and dimethyl sulfoxide (DMSO) is added in such a way that the solid content is 2% by mass, and potassium carbonate equivalent to 0.1% by mass is added, and the mixture is heated to 60°C while being uniformly stirred. Vinyl acetate is added thereto, and acetylation is carried out until the prescribed degree of substitution is reached. After the reaction, 10% by mass of quenching water is added, and pure water with a mass of 50 times the mass of the cellulose solid content is used for stirring and filtering by a pressure filter, and this operation is repeated to fully wash the solvent, etc., to obtain a wet cake of acetylated cellulose microfibers.
[0585] Tables 1 and 2 show the evaluation results of the obtained chemically modified cellulose fine fibers.
[0586] 《Manufacturing of fiber-reinforced resins》
[0587] (Compounding by injection molding: Examples I-1 to I-12, Comparative Examples I-1 to I-7)
[0588] Using each of the obtained chemically modified cellulose microfibers, a fiber-reinforced resin as a composite by injection molding was prepared in the following procedure.
[0589] 1. The wet cakes of chemically modified cellulose fine fibers prepared in Production Examples 1 to 12 and Comparative Production Examples 1 to 7 were dispersed in hexafluoroisopropanol (hereinafter referred to as HFIP) at a solid content concentration of 1 vol% using a homogenizer (ULTRA-TURRAX T18 manufactured by IKA) at a rotation speed of 12,000 rpm for 3 minutes.
[0590] 2. A solution was prepared by dissolving polyamide 6 (1013B manufactured by Ube Industries, Ltd.) in HFIP at a solid content of 1% by mass.
[0591] 3. 1 and 2 were placed in a container so that the solid content mass ratio of chemically modified cellulose microfibers to polyamide 6 was 1:9, and mixed at 2,000 rpm for 5 minutes using a rotation / revolution mixer (Awatori Rentaro ARE-310 manufactured by Thinky).
[0592] 4. The obtained mixed solution of 3 was cast on a release film (X88B manufactured by Mitsui Chemicals Tohcello Co., Ltd.) into a film shape and dried in an oven at 80°C for 1 hour.
[0593] 5. 4 was pulverized using a table pulverizer (Mini High Speed Mill MS-05 manufactured by Labonect).
[0594] 6. Dry the powder of 5 in a vacuum dryer for more than 24 hours.
[0595] 7. 6 was kneaded for 2 minutes in a small kneader (manufactured by DSM, Xplore MC 15HT) at a temperature of 250°C and a rotation speed of 200 rpm.
[0596] 8. After kneading, the resin was poured into an injection molding machine (Xplore IM12) to produce strip test pieces with a width of 10 mm, a length of 80 mm, and a thickness of 4 mm for bending tests, and multi-purpose test pieces (as fiber-reinforced resin) in accordance with ISO-37 for tensile tests.
[0597] Table 3 shows the evaluation results of the obtained test pieces by the bending test and the tensile test.
[0598] (Resin composite by nonwoven fabric method-1: Examples I-13 to I-24, Comparative Examples I-8 to I-14)
[0599] Short fibers made of polypropylene (cut length: 2.0 mm, fineness: 0.2 T) and the chemically modified cellulose microfibers prepared above were added to pure water at a solid content mass ratio of 80:20 to obtain a slurry with a solid content concentration of 0.5% by mass. The slurry was stirred for 4 minutes using a household mixer to prepare a papermaking slurry. The papermaking slurry prepared above was mixed with a basis weight of 300 g / m 2 The paper was put into a batch papermaking machine (automatic square plate press 25 cm×25 cm, 80 mesh manufactured by Kumagai Riki Kogyo Co., Ltd.) equipped with a filter cloth (TT35 manufactured by Shikishima Canvas Co., Ltd.), and then the vacuum degree was set to 50 kPa relative to the atmospheric pressure to carry out papermaking (dehydration).
[0600] The wet paper composed of the concentrated composition in a wet state placed on the filter cloth was peeled off from the wire mesh and then heated to 1 kg / cm 2 The nonwoven fabric was then dried for about 120 seconds using a rotary dryer with the surface temperature set at 130°C to obtain a nonwoven fabric. Four 10 cm square nonwoven fabrics were cut from the obtained nonwoven fabric, and the laminated fabric was sandwiched with a 0.1 μm thick PET film. The nonwoven fabric was pressed using a hot press at a temperature of 200°C and a molding pressure of 10 kg / cm 2 The heat molding was performed for 5 minutes under the condition of . Here, a 1.5 mm stainless steel spacer was set between the PET films to control the thickness of the molded product. After that, the heating of the hot press was terminated, and the entire press was slowly cooled for about 30 minutes using a blower while maintaining the pressure. When the temperature of the press reached 90°C or less, the pressure was released to obtain a resin reinforced resin molded into a plate shape. The obtained resin reinforced resin was evaluated by the above-mentioned bending test, and the results are shown in Table 4.
[0601] (Resin composite by nonwoven fabric method-2: Examples I-25 to I-36, Comparative Examples I-15 to I-21)
[0602] Short fibers made of polyamide 66 (cut length: 2.0 mm, fineness: 0.6 T) and the chemically modified cellulose microfibers prepared above were added to pure water at a solid content mass ratio of 80:20 to obtain a slurry with a solid content concentration of 0.5 mass%. The slurry was stirred for 4 minutes using a household mixer to prepare a papermaking slurry. The papermaking slurry prepared above was mixed with a basis weight of 300 g / m 2 The paper was put into a batch papermaking machine (automatic square plate press 25 cm×25 cm, 80 mesh manufactured by Kumagai Riki Kogyo Co., Ltd.) equipped with a filter cloth (TT35 manufactured by Shikishima Canvas Co., Ltd.), and then the vacuum degree was set to 50 kPa relative to the atmospheric pressure to carry out papermaking (dehydration).
[0603] The wet paper composed of the concentrated composition in a wet state placed on the filter cloth was peeled off from the wire mesh and then heated to 1 kg / cm 2 The nonwoven fabric was then dried for about 120 seconds using a rotary dryer with the surface temperature set at 130°C to obtain a nonwoven fabric. Four 10 cm square nonwoven fabrics were cut from the obtained nonwoven fabric, and the laminated fabric was clamped with a Teflon (registered trademark) sheet with a thickness of 0.1 μm. The nonwoven fabric was pressed using a hot press at a temperature of 300°C and a molding pressure of 10 kg / cm 2The heat molding was performed for 5 minutes under the condition of . Here, a 1.5 mm stainless steel spacer was set between the PET films to control the thickness of the molded product. After that, the heating of the hot press was terminated, and the entire press was slowly cooled for more than 30 minutes using a blower while maintaining the pressure. When the temperature of the press reached 90°C or less, the pressure was released to obtain a fiber reinforced resin molded into a plate shape. The obtained fiber reinforced resin was evaluated by the above-mentioned bending test, and the results are shown in Table 5.
[0604]
[0605]
[0606]
[0607] Example II:
[0608] 《Measurement Method》
[0609] [Fiber shape automatic analyzer measurement]
[0610] Using an automatic fiber shape analyzer (Morfi neo, manufactured by Technidyne), various properties of the cellulose microfibers were measured in the following procedures.
[0611] 1. Disperse cellulose microfibers in pure water to prepare 1 L of water dispersion. The final solid content concentration is adjusted to about 0.004% by mass. Since all cellulose microfibers are water dispersions with a solid content concentration of 2% by mass or less, they are dispersed by shaking and mixing in a closed container with a filling rate of 75% by volume or less.
[0612] 2. The aqueous dispersion prepared in 1. is supplied to an automatic sampler and measured.
[0613] 3. Output the measurement results in txt format (or csv format).
[0614] 4. Extract or calculate the same shape parameters as in Example I based on the measurement results.
[0615] [Specific surface area, and average fiber diameter calculated from the specific surface area]
[0616] The measurement was carried out in the same manner as in Example 1.
[0617] [Measurement of rheological properties of cellulose microfibers]
[0618] The rheological properties of the aqueous dispersion of cellulose microfibers were measured according to the following procedure, and the inverse of the yield strain (1 / γ) was calculated. The measuring equipment and measuring conditions used were set as follows.
[0619] (Measurement conditions)
[0620] Measuring equipment: Rheometer HAAKE MERS (manufactured by Thermo Fisher Scientific)
[0621] Measuring fixture: Coaxial double cylinder (cup: CCB25 DIN, rotor: CC25 DIN Ti)
[0622] Measurement mode: Oscillation
[0623] Control method: Stress control
[0624] Control range: 0.01~100Pa
[0625] Temperature: 25℃
[0626] 1. Disperse the cellulose microfibers in pure water. Here, the final solid content concentration of the cellulose microfibers is 0.75% by mass. Since all the cellulose microfibers are water dispersions with a solid content concentration of 2% or less, they are dispersed by shaking and mixing in a closed container with a filling rate of 75% by volume or less.
[0627] 2. Allow the aqueous dispersion prepared in 1. to stand at 25°C for more than 24 hours.
[0628] 3. Install the fixture on the rheometer and use a dropper to add 17.0±1.0 g of cellulose microfiber aqueous dispersion.
[0629] 4. The measurement was carried out, and the yield strain (γ) was calculated by LVE analysis, and its reciprocal (1 / γ) was calculated.
[0630] [Whiteness measurement]
[0631] The measurement was carried out in the same manner as in Example 1.
[0632] [Determination of halogen content in cellulose raw material or cellulose microfibers]
[0633] The measurement was carried out in the same manner as in Example 1.
[0634] [Tensile test]
[0635] A multipurpose test piece was prepared according to ISO-37 by the method described later, and a tensile test was carried out under the conditions according to JIS K6920-2 to measure the tensile strength, tensile elastic modulus, and fracture strain.
[0636] [Dynamic viscoelasticity measurement]
[0637] A multipurpose test piece was prepared according to ISO-37 by the method described later, and DMA measurement was performed under the following conditions to measure the storage modulus at 150°C.
[0638] Device: Gabo Eplexor 500N
[0639] Measurement mode: Tensile
[0640] Measuring temperature range: -130~200℃
[0641] Heating rate: 3℃ / min
[0642] Static load strain: 0.5%
[0643] Dynamic load strain: 0.3%
[0644] Vibration frequency: 10Hz
[0645] Contact load: 1N
[0646] [Bending test]
[0647] A strip having a width of 25 mm and a length of 50 mm was cut out from the plate-like composite obtained by the nonwoven fabric method, and the flexural strength, flexural modulus, and flexural failure strain were measured under the conditions in accordance with JIS K7171.
[0648] [Thermal stability of resin]
[0649] The measurement was carried out in the same manner as in Example 1.
[0650] Preparation of cellulose microfibers
[0651] (Cellulose microfiber A)
[0652] Cottonseed linter pulp obtained from Nippon Paper & Pulp Co., Ltd. as natural cellulose was used. It was immersed in water in such a manner that the cottonseed linter pulp was 1.5% by mass, and after being simply dispersed using a laboratory pulper (manufactured by Aikawa Iron Works), it was sent to a tank. A single-disc refiner (front stage) with a disk having a blade width of 2.5 mm, a groove width of 7.0 mm, and a blade-to-groove ratio of 0.36 connected to the tank was used to circulate the slurry while refining it. At this time, the operation was started from a blade distance of 1.0 mm, and the blade distance was gradually reduced while the blade distance was finally 0.05 mm. After the blade distance reached 0.05 mm, the operation was continued while the flow rate was further confirmed, and the operation was terminated at the stage when the total amount of slurry passed through the disk 10 times. Then, a single-disc refiner (rear stage) with a disk having a blade width of 0.6 mm, a groove width of 1.0 mm, and a blade-to-groove ratio of 0.6 was used to circulate the slurry while refining it. At this time, the operation was started from the distance between the blades of 1.0 mm, and the distance between the blades was gradually reduced while the distance between the blades was finally 0.05 mm. After the distance between the blades reached 0.05 mm, the operation was continued while confirming the flow rate, and the operation was terminated at the stage when the total amount of slurry passed through the disc 10 times. The obtained cellulose microfibers were referred to as cellulose microfibers A (MFC-A). The analysis results of various fiber shape parameters and rheological properties are shown in Table 6.
[0653] (Cellulose microfiber B)
[0654] Cellulose microfibers B (MFC-B) were obtained in the same manner as for cellulose microfibers A, except that the number of treatments with the single disc refiner (latter stage) was changed to 30. Table 6 shows the analysis results of various fiber shape parameters and rheological properties.
[0655] (Cellulose microfiber C)
[0656] Cottonseed linter pulp obtained from Nippon Paper & Pulp Co., Ltd. as a natural cellulose was used. It was immersed in water in such a manner that the cottonseed linter pulp was 1.5% by mass, and after being simply dispersed using a laboratory pulper (manufactured by Aikawa Iron Works), it was sent to a tank. A single-disc refiner (front section) with a disk having a blade width of 2.5 mm, a groove width of 7.0 mm, and a blade-to-groove ratio of 0.36 connected to the tank was used to circulate the slurry while refining it. At this time, the operation was started from a blade distance of 1.0 mm, and the blade distance was gradually reduced while the blade distance was finally 0.3 mm. After the blade distance reached 0.3 mm, the operation was continued while the flow rate was further confirmed, and the operation was terminated at the stage when the total amount of slurry passed through the disk part 90 times. Then, a single-disc refiner (rear section) with a disk having a blade width of 0.8 mm, a groove width of 1.5 mm, and a blade-to-groove ratio of 0.53 was used to circulate the slurry while refining it. At this time, the operation was started from the distance between the blades of 1.0 mm, and the distance between the blades was gradually reduced while the distance between the blades was finally 0.15 mm. After the distance between the blades reached 0.15 mm, the operation was continued while confirming the flow rate, and the operation was terminated at the stage where the total amount of slurry passed through the disc 40 times. The obtained cellulose microfibers were referred to as cellulose microfibers C (MFC-C). The analysis results of various fiber shape parameters and rheological properties are shown in Table 6.
[0657] (Cellulose microfiber D)
[0658] The cellulose fine fibers C were subjected to 10 micronization treatments at an operating pressure of 100 MPa using a high-pressure homogenizer (NS015H manufactured by Niro Soavi (Italy)) to obtain cellulose fine fibers D (MFC-D). Table 6 shows the analysis results of various fiber shape parameters and rheological properties.
[0659] (Cellulose microfiber E)
[0660] Cottonseed linter pulp obtained from Nippon Paper & Pulp Co., Ltd. as a natural cellulose was used. It was immersed in water in such a manner that the cottonseed linter pulp was 1.5% by mass, and after being simply dispersed using a laboratory pulper (manufactured by Aikawa Iron Works), it was sent to a tank. A single-disc refiner (front stage) with a disk having a blade width of 2.5 mm, a groove width of 7.0 mm, and a blade-to-groove ratio of 0.36 connected to the tank was used to circulate the slurry while refining it. At this time, the operation was started from a blade distance of 1.0 mm, and the blade distance was gradually reduced while the blade distance was finally 0.05 mm. After the blade distance reached 0.05 mm, the operation was continued while the flow rate was further confirmed, and the operation was terminated at the stage when the total amount of slurry passed through the disk part 90 times. Then, a single-disc refiner (rear stage) with a disk having a blade width of 0.8 mm, a groove width of 1.5 mm, and a blade-to-groove ratio of 0.53 was used to circulate the slurry while refining it. At this time, the operation was started from the distance between the blades of 1.0 mm, and the distance between the blades was gradually reduced while the distance between the blades was finally 0.05 mm. After the distance between the blades reached 0.05 mm, the operation was continued while confirming the flow rate, and the operation was terminated at the stage where the total amount of slurry passed through the disc 90 times. The obtained cellulose microfibers were referred to as cellulose microfibers E (MFC-E). The analysis results of various fiber shape parameters and rheological properties are shown in Table 6.
[0661] (Cellulose microfiber F)
[0662] Cottonseed linter pulp obtained from Nippon Paper & Pulp Co., Ltd. as natural cellulose was used. It was immersed in water in such a manner that the cottonseed linter pulp was 1.5% by mass, and after being simply dispersed using a laboratory pulper (manufactured by Aikawa Iron Works), it was sent to a tank. A single-disc refiner (only one unit) with a disc having a blade width of 2.5 mm, a groove width of 7.0 mm, and a blade-groove ratio of 0.36 connected to the tank was used to circulate the pulp while refining it. At this time, the operation was started from a blade distance of 1.0 mm, and the blade distance was gradually reduced while the blade distance was finally 0.05 mm. After the blade distance reached 0.05 mm, the operation was continued while confirming the flow rate, and the operation was terminated at the stage when the total amount of pulp passed through the disc 150 times. The obtained cellulose microfibers were referred to as microfibrillated cellulose F (MFC-F). The analysis results of various fiber shape parameters and rheological properties are shown in Table 6.
[0663] (Cellulose microfiber G)
[0664] Cottonseed linter pulp obtained from Nippon Paper & Pulp Co., Ltd. as a natural cellulose was used. It was immersed in water in such a manner that the cottonseed linter pulp was 1.5% by mass, and after being simply dispersed using a laboratory pulper (manufactured by Aikawa Iron Works), it was sent to a tank. A single-disc refiner (front section) with a disk having a blade width of 2.5 mm, a groove width of 7.0 mm, and a blade-groove ratio of 0.36 connected to the tank was used to circulate the slurry while refining it. At this time, the operation was started from a blade distance of 1.0 mm, and the blade distance was gradually reduced while the blade distance was finally 0.05 mm. After the blade distance reached 0.05 mm, the operation was continued while the flow rate was further confirmed, and the operation was terminated at the stage when the total amount of slurry passed through the disk 10 times. Then, a single-disc refiner (rear section) with a disk having a blade width of 0.6 mm, a groove width of 1.0 mm, and a blade-groove ratio of 0.6 was used to circulate the slurry while refining it. At this time, the operation was started from a distance between blades of 1.0 mm, and the distance between blades was gradually reduced while the distance between blades was finally 0.05 mm. The operation was terminated immediately after the distance between blades reached 0.05 mm (for convenience, the number of times the disk passed was expressed as 0 times), and the obtained cellulose microfibers were referred to as cellulose microfibers G (MFC-G). The analysis results of various fiber shape parameters and rheological properties are shown in Table 6.
[0665] (Cellulose microfiber H)
[0666] Cottonseed linter pulp obtained from Nippon Paper & Pulp Co., Ltd. as natural cellulose was used. It was immersed in water in such a manner that the cottonseed linter pulp was 1.5% by mass, and after being simply dispersed using a laboratory pulper (manufactured by Aikawa Iron Works), it was sent to a tank. A single-disc refiner (only one unit) with a disk having a blade width of 0.8 mm, a groove width of 1.5 mm, and a blade-groove ratio of 0.53 connected to the tank was used to circulate the slurry while refining it. At this time, the operation was started from a blade distance of 1.0 mm, and the blade distance was gradually reduced while the blade distance was finally 0.05 mm. After the blade distance reached 0.05 mm, the operation was continued while confirming the flow rate, and the operation was terminated at the stage when the total amount of slurry passed through the disk 90 times. The obtained cellulose microfibers were referred to as cellulose microfibers H (MFC-H). The analysis results of various fiber shape parameters and rheological properties are shown in Table 6.
[0667] (Cellulose microfiber I)
[0668] Cottonseed linter pulp obtained from Nippon Paper & Pulp Co., Ltd. as natural cellulose was used. It was immersed in water in such a manner that the cottonseed linter pulp was 1.5% by mass, and after being simply dispersed using a laboratory pulper (manufactured by Aikawa Iron Works), it was sent to a tank. A single-disc refiner (front section) with a disk having a blade width of 4.0 mm, a groove width of 4.5 mm, and a blade-to-groove ratio of 0.89 connected to the tank was used to circulate the slurry while refining it. At this time, the operation was started from a blade distance of 1.0 mm, and the blade distance was gradually reduced while the blade distance was finally 0.05 mm. After the blade distance reached 0.05 mm, the operation was continued while the flow rate was further confirmed, and the operation was terminated at the stage when the total amount of slurry passed through the disk 30 times. Then, a single-disc refiner (rear section) with a disk having a blade width of 0.8 mm, a groove width of 1.5 mm, and a blade-to-groove ratio of 0.53 was used to circulate the slurry while refining it. At this time, the operation was started from the distance between the blades of 1.0 mm, and the distance between the blades was gradually reduced while the distance between the blades was finally 0.05 mm. After the distance between the blades reached 0.05 mm, the operation was continued while confirming the flow rate, and the operation was terminated at the stage where the total amount of slurry passed through the disc 30 times. The obtained cellulose microfibers were referred to as cellulose microfibers I (MFC-I). The analysis results of various fiber shape parameters and rheological properties are shown in Table 6.
[0669] (Cellulose microfiber J)
[0670] Cellulose microfibers J (MFC-J) were obtained in the same manner as cellulose microfibers A (MFC-A) except that the number of treatments with the single disc refiner (latter stage) was changed to 180. Table 6 shows the analysis results of various fiber shape parameters and rheological properties.
[0671] (Cellulose microfiber K)
[0672] Cottonseed pulp obtained from Nippon Paper & Pulp Co., Ltd. as natural cellulose was used. It was immersed in water in a manner that the cottonseed pulp was 1.5% by mass, and after being simply dispersed using a laboratory pulper (manufactured by Aikawa Iron Works), it was sent to a tank. A single-disc refiner (only one unit) with a disc having a blade width of 4 mm, a groove width of 4.5 mm, and a blade-groove ratio of 0.89 connected to the tank was used to circulate the slurry while refining it. At this time, the operation started from a blade distance of 1.0 mm, and the blade distance was gradually reduced while the blade distance was finally 0.05 mm. After the blade distance reached 0.05 mm, the operation was continued while confirming the flow rate, and the operation was terminated at the stage where the total amount of slurry passed through the disc 250 times. Then, a high-pressure homogenizer (NS015H manufactured by Niro Soavi (Italy)) was used to perform 10 refining treatments at an operating pressure of 100 MPa, and the resulting cellulose microfibers were referred to as cellulose microfibers K (MFC-K). The analysis results of various fiber shape parameters and rheological properties are shown in Table 6.
[0673] (Cellulose microfiber L)
[0674] Cottonseed linter pulp obtained from Nippon Paper & Pulp Co., Ltd. as natural cellulose was used. It was immersed in water in such a manner that the cottonseed linter pulp was 1.5% by mass, and after being simply dispersed using a laboratory pulper (manufactured by Aikawa Iron Works), it was sent to a tank. A single-disc refiner (only one unit) with a disc having a blade width of 2.5 mm, a groove width of 7.0 mm, and a blade-groove ratio of 0.36 connected to the tank was used to circulate the pulp while refining it. At this time, the operation was started from a blade distance of 1.0 mm, and the blade distance was gradually reduced while the blade distance was finally 0.3 mm. After the blade distance reached 0.3 mm, the operation was continued while confirming the flow rate, and the operation was terminated at the stage when the total amount of pulp passed through the disc 90 times. The obtained cellulose microfibers were referred to as microfibrillated cellulose L (MFC-L). The analysis results of various fiber shape parameters and rheological properties are shown in Table 6.
[0675] 《Manufacturing of fiber-reinforced resins》
[0676] (Example II-1-1)
[0677] Using MFC-A as the cellulose fine fibers, a composite was prepared by injection molding in the following manner.
[0678] 1. Cellulose microfibers were concentrated by suction filtration (filter material: TT35 manufactured by Shikishima Canvas Co., Ltd.) to prepare a wet fiber cake having a solid content of about 20% by mass.
[0679] 2. The wet fiber cake was dispersed in hexafluoroisopropanol (hereinafter referred to as HFIP) at a final concentration of 1 vol% using a homogenizer (manufactured by IKA, trade name "ULTRA-TURRAX T18") at a rotation speed of 12,000 rpm for 3 minutes.
[0680] 3. A solution was prepared by dissolving 1 mass % of polyamide 6 (manufactured by Ube Industries, Ltd., 1013B, melting point 225° C.) in HFIP.
[0681] 4. 2 and 3 were placed in the same container so that the solid content mass ratio of MFC-A to polyamide 6 was 1:9, and mixed at 2,000 rpm for 5 minutes using a rotation / revolution mixer (manufactured by Thinky, Defoaming Rentaro ARE-310).
[0682] 5. 4 was cast on a release film (X88B manufactured by Mitsui Chemicals Tohcello Co., Ltd.) into a film shape and dried in an oven at 80°C for 1 hour.
[0683] 6. 5 was pulverized using a table pulverizer (Mini High Speed Mill MS-05 manufactured by Labonect).
[0684] 7. Dry the powder of 6 in a vacuum dryer for more than 24 hours.
[0685] 8. 7 was kneaded for 2 minutes in a small kneader (manufactured by DSM, Xplore MC 15HT) at a temperature of 250°C and a rotation speed of 200 rpm.
[0686] 9. After kneading, the kneaded product was poured into an injection molding machine (Xplore IM12) to prepare a multi-purpose test piece in accordance with ISO-37 as a composite 1-A.
[0687] The composite 1-A was evaluated by the above-mentioned tensile test and dynamic viscoelasticity measurement. The results are shown in Table 6.
[0688] (Example II-1-2)
[0689] A composite 1-B was obtained by the same method as in Example II-1-1 except that MFC-B was used as the cellulose fine fibers. The obtained composite 1-B was evaluated by the above-mentioned tensile test and dynamic viscoelasticity measurement. The results are shown in Table 6.
[0690] (Example II-1-3)
[0691] A composite 1-C was obtained by the same method as in Example II-1-1 except that MFC-C was used as the cellulose fine fibers. The obtained composite 1-C was evaluated by the above-mentioned tensile test and dynamic viscoelasticity measurement. The results are shown in Table 6.
[0692] (Example II-1-4)
[0693] A composite 1-D was prepared by the same method as in Example II-1-1 except that MFC-D was used as the cellulose fine fibers. The obtained composite 1-D was evaluated by the above-mentioned tensile test and dynamic viscoelasticity measurement. The results are shown in Table 6.
[0694] (Example II-1-5)
[0695] A composite 1-E was obtained by the same method as in Example II-1-1 except that MFC-E was used as the cellulose fine fibers. The obtained composite 1-E was evaluated by the above-mentioned tensile test and dynamic viscoelasticity measurement. The results are shown in Table 6.
[0696] (Example II-1-6)
[0697] A composite 1-F was obtained by the same method as in Example II-1-1 except that MFC-F was used as the cellulose fine fibers. The obtained composite 1-F was evaluated by the above-mentioned tensile test and dynamic viscoelasticity measurement. The results are shown in Table 6.
[0698] (Example II-1-7)
[0699] A composite 1-G was obtained by the same method as in Example II-1-1 except that MFC-G was used as the cellulose fine fibers. The obtained composite 1-G was evaluated by the above-mentioned tensile test and dynamic viscoelasticity measurement. The results are shown in Table 6.
[0700] (Example II-1-8)
[0701] A composite 1-H was obtained by the same method as in Example II-1-1 except that MFC-H was used as the cellulose fine fibers. The obtained composite 1-H was evaluated by the above-mentioned tensile test and dynamic viscoelasticity measurement. The results are shown in Table 6.
[0702] (Example II-1-9)
[0703] A composite 1-I was obtained by the same method as in Example II-1-1 except that MFC-I was used as the cellulose fine fibers. The obtained composite 1-I was evaluated by the above-mentioned tensile test and dynamic viscoelasticity measurement. The results are shown in Table 6.
[0704] (Comparative Example II-1-1)
[0705] A composite 1-J was prepared by the same method as in Example II-1-1 except that MFC-J was used as the cellulose fine fibers. The obtained composite 1-J was evaluated by the above-mentioned tensile test and dynamic viscoelasticity measurement. The results are shown in Table 6.
[0706] (Comparative Example II-1-2)
[0707] A composite 1-K was obtained by the same method as in Example II-1-1 except that MFC-K was used as the cellulose fine fibers. The obtained composite 1-K was evaluated by the above-mentioned tensile test and dynamic viscoelasticity measurement. The results are shown in Table 6.
[0708] (Comparative Example II-1-3)
[0709] A composite 1-L was prepared by the same method as in Example II-1-1 except that MFC-L was used as the cellulose fine fibers. The obtained composite 1-L was evaluated by the above-mentioned tensile test and dynamic viscoelasticity measurement. The results are shown in Table 6.
[0710] (Example II-2-1)
[0711] Short fibers made of polypropylene (cut length: 2.0 mm, fineness: 0.2T, melting point 160°C) and MFC-A were added to pure water at a solid content mass ratio of 80:20 to give a final solid content concentration of 0.5% by mass. The slurry was stirred for 4 minutes using a household mixer to prepare a papermaking slurry.
[0712] The papermaking pulp prepared above was prepared at a basis weight of 300 g / m 2 The paper was put into a batch papermaking machine (manufactured by Kumagai Riki Kogyo Co., Ltd., automatic square plate press 25 cm×25 cm, 80 mesh) equipped with a filter cloth (TT35 manufactured by Shikishima Canvas Co., Ltd.), and then the vacuum degree was set to 50 KPa relative to the atmospheric pressure to implement papermaking (dehydration).
[0713] The wet paper composed of the concentrated composition in a wet state placed on the filter cloth was peeled off from the wire mesh and then heated to 1 kg / cm 2The nonwoven fabric S1 was obtained by cutting 4 pieces of 10 cm square nonwoven fabric from the obtained nonwoven fabric S1, and the laminated material was sandwiched with a PET film having a thickness of 0.1 μm. The nonwoven fabric was pressed by a hot press at a temperature of 200°C and a molding pressure of 10 kg / cm 2 The molding was performed under the conditions of 5 minutes. Here, a 1.5 mm stainless steel spacer was set between the PET films to control the thickness of the molded product. The heating of the hot press was then terminated, and the entire press was slowly cooled for about 30 minutes using a blower while maintaining the pressure. When the temperature of the press reached below 90°C, the pressure was released to obtain a composite 2-A molded in a plate shape. The obtained composite 2-A was evaluated by the above-mentioned bending test, and the results are shown in Table 7.
[0714] (Example II-2-2)
[0715] A composite 2-B was obtained by the same method as in Example II-2-1 except that MFC-B was used as the cellulose fine fibers. The obtained composite 2-B was evaluated by the above-mentioned bending test. The results are shown in Table 7.
[0716] (Example II-2-3)
[0717] A composite 2-C was obtained by the same method as in Example II-2-1 except that MFC-C was used as the cellulose fine fibers. The obtained composite 2-C was evaluated by the above-mentioned bending test. The results are shown in Table 7.
[0718] (Example II-2-4)
[0719] A composite 2-D was obtained by the same method as in Example II-2-1 except that MFC-D was used as the cellulose fine fibers. The obtained composite 2-D was evaluated by the above-mentioned bending test. The results are shown in Table 7.
[0720] (Example II-2-5)
[0721] A composite 2-E was obtained by the same method as in Example II-2-1 except that MFC-E was used as the cellulose fine fibers. The obtained composite 2-E was evaluated by the above-mentioned bending test. The results are shown in Table 7.
[0722] (Example II-2-6)
[0723] A composite 2-F was obtained by the same method as in Example II-2-1 except that MFC-F was used as the cellulose fine fibers. The obtained composite 2-F was evaluated by the above-mentioned bending test. The results are shown in Table 7.
[0724] (Example II-2-7)
[0725] A composite 2-G was obtained by the same method as in Example II-2-1 except that MFC-G was used as the cellulose fine fibers. The obtained composite 2-G was evaluated by the above-mentioned bending test. The results are shown in Table 7.
[0726] (Example II-2-8)
[0727] A composite 2-H was obtained by producing a composite in the same manner as in Example II-2-1 except that MFC-H was used as the cellulose fine fibers. The obtained composite 2-H was evaluated by the above-mentioned bending test. The results are shown in Table 7.
[0728] (Example II-2-9)
[0729] A composite 2-I was obtained by the same method as in Example II-2-1 except that MFC-I was used as the cellulose fine fibers. The obtained composite 2-I was evaluated by the above-mentioned bending test. The results are shown in Table 7.
[0730] (Example II-2-10)
[0731] Using MFC-A as the cellulose fine fibers, a composite was prepared by injection molding in the following manner.
[0732] 1. Short fibers made of polypropylene (cut length: 2.0 mm, fineness: 0.2T, melting point 160° C.) were placed on a release film (X88B manufactured by Mitsui Chemicals Tohcello Co., Ltd.) and heated in an oven at 200° C. to melt.
[0733] 2. 1 was cooled and solidified, and the solidified product was pulverized using a table pulverizer (Mini High Speed Mill MS-05 manufactured by Labonect).
[0734] 3. Cellulose microfibers and rosin ethylene oxide adduct (rosin-polyethylene glycol ester, manufactured by Harima Chemicals Co., Ltd.) are placed in a closed planetary mixer (manufactured by Kodaira Seisakusho Co., Ltd., trade name "ACM-5LVT", with hook-type stirring blades) at a mass ratio of cellulose microfibers / rosin ethylene oxide adduct of 80 / 20, stirred at 70 rpm for 60 minutes at normal temperature and pressure, and finally reduced pressure (-0.1 MPa), placed in a warm bath at 40°C, and coated and dried under reduced pressure at 307 rpm for 2 hours to obtain a powdered cellulose microfiber preparation A.
[0735] 4. The powders of 2 and 3 were mixed so that the mass ratio of cellulose microfibers to polypropylene was 20:80, and kneaded for 5 minutes in a small kneader (manufactured by DSM, Xplore MC 15HT) at a temperature of 200° C. and a rotation speed of 200 rpm.
[0736] 5. After kneading, the kneaded product was poured into an injection molding machine (Xplore IM12) to prepare a long test piece (10 mm×75 mm×4 mm), which was designated as composite 2-A2.
[0737] The composite 2-A2 was evaluated by the above-mentioned bending test. The results are shown in Table 7.
[0738] (Comparative Example II-2-1)
[0739] A composite 2-J was prepared by the same method as in Example II-2-1 except that MFC-J was used as the cellulose fine fibers. The obtained composite 2-J was evaluated by the above-mentioned bending test. The results are shown in Table 7.
[0740] (Comparative Example II-2-2)
[0741] A composite 2-K was obtained by the same method as in Example II-2-1 except that MFC-K was used as the cellulose fine fibers. The obtained composite 2-K was evaluated by the above-mentioned bending test. The results are shown in Table 7.
[0742] (Comparative Example II-2-3)
[0743] A composite 2-L was obtained by the same method as in Example II-2-1 except that MFC-L was used as the cellulose fine fibers. The obtained composite 2-L was evaluated by the above-mentioned bending test. The results are shown in Table 7.
[0744] (Comparative Example II-2-4)
[0745] A composite was prepared by the same method as in Example II-2-10 except that MFC-J was used as the cellulose fine fibers. The obtained composite was designated as composite 2-J2 and evaluated by the above-mentioned bending test. The results are shown in Table 7.
[0746]
[0747]
[0748] As can be seen from Tables 6 and 7, for the composites obtained in Examples II-1-1 to II-1-9 and Examples II-2-1 to II-2-10, all the properties of strength, elastic modulus, and breaking strain are excellent regardless of the molding method of the composite. On the other hand, for the composites obtained in Comparative Examples II-1-1 to II-1-3 and Comparative Examples II-2-1 to II-2-4, at least one of the physical properties of strength, elastic modulus, and breaking strain is not excellent. It is believed that this is because, in cellulose microfibers J, excessive refining occurs due to the large number of passes of the disc refiner (latter stage), in cellulose microfibers K, excessive refining and excessive fibrillation occur by beating at high viscosity and treatment with a high-pressure homogenizer, and in cellulose microfibers L, the refining is insufficient due to the small number of passes and the width of the blades of the disc refiner.
[0749] Industrial Applicability
[0750] When the cellulose microfibers of the present invention are blended with a resin, they can provide a fiber-reinforced resin having excellent elastic modulus, strength and breaking strain, and can be suitably used as a reinforcing material for resins used in automobiles, houses, home appliances, buildings, and the like.
[0751] Explanation of symbols
[0752] 11 blades
[0753] 12 slots
[0754] 21 Spinning Blade
[0755] 22 Fixed Blade
[0756] W B Blade width
[0757] W G Slot width
[0758] W L Distance between blades
Claims
1. A cellulose microfiber, wherein: In the determination of the fiber shape automatic analyzer, all the following parameters are met: (i) the length-weighted average fiber length of fibers having a fiber length of 100 μm or more is 110 μm or more and 500 μm or less, (ii) the average fiber diameter is 42.5 μm or less, (iii) the fine fiber area ratio is 90% or less, where the fine fiber area ratio refers to the ratio of the total area of the observed image of fine fibers with a fiber length of less than 100 μm to the total area of the observed image of all fibers, (iv) among fibers having a fiber length of less than 100 μm, the number frequency of fibers having a fiber length of 20 μm or more and 56 μm or less is 97% or less, (v) the number frequency of fibers having a fiber length of 411 μm or longer among fibers having a fiber length of 100 μm or longer is 54% or less, and (vi) The average fiber diameter calculated by specific surface area is 20 nm to 150 nm.
2. The cellulose microfibers according to claim 1, wherein The average fiber length is not less than 110 μm and not more than 500 μm.
3. The cellulose microfibers according to claim 1, wherein In the determination of the fiber shape automatic analyzer, all the following parameters are met: (i) the average fiber length is not less than 130 μm and not more than 350 μm, (ii) the average fiber diameter is 35 μm or less, (iii) the fine fiber area ratio is 75% or less, where the fine fiber area ratio refers to the ratio of the total area of the observed image of fine fibers with a fiber length of less than 100 μm to the total area of the observed image of all fibers, (iv) among fibers having a fiber length of less than 100 μm, the number frequency of fibers having a fiber length of 20 μm or more and 56 μm or less is 75% or less, (v) among fibers having a fiber length of 100 μm or more, the number frequency of fibers having a fiber length of 411 μm or more is 30% or less, and (vi) The fibrillation rate is 5% or less.
4. The cellulose microfibers according to claim 1, wherein The glucose content in the constituent sugar analysis is 90 mass % or more.
5. The cellulose microfibers according to claim 1, wherein A 5 ppm by mass DMSO dispersion of cellulose microfibers was poured and dried. In a scanning electron microscope (SEM) image of the surface of the obtained sample, the occupied area was less than 15 μm. 2 The ratio of the total area occupied by the ultrafine fibers to the total area occupied by the cellulose microfibers is 10% to 80%. The cellulose microfibers according to claim 1 , which have a cellulose I type crystal structure.
7. The cellulose microfibers according to claim 1, which have a crystallinity of 60% or more.
8. The cellulose microfibers according to claim 1, wherein The halogen content is 250 mass ppm or less.
9. The cellulose microfibers according to claim 1, wherein The whiteness is 50% or more.
10. The cellulose microfibers according to claim 1, wherein The length-weighted average fiber length of fibers having a fiber length of 100 μm or more is 130 μm or more and 350 μm or less.
11. The cellulose microfiber according to claim 1, wherein Among fibers having a fiber length of 100 μm or longer, the number frequency of fibers having a fiber length of 411 μm or longer is 30% or less.
12. The cellulose microfibers according to claim 1, wherein The thin fiber area ratio is 75% or less, where the thin fiber area ratio refers to the ratio of the total area of the observed image of thin fibers having a fiber length of less than 100 μm to the total area of the observed image of all fibers.
13. The cellulose microfibers according to claim 1, wherein Among fibers having a fiber length of less than 100 μm, the number frequency of fibers having a fiber length of 20 μm to 56 μm is 30% to 75%.
14. The cellulose microfibers according to claim 1, wherein The fibrillation rate is 5% or less. The cellulose microfibers according to claim 1 , which are cellulose microfibers at least surface of which is chemically modified.
16. The cellulose microfibers according to claim 15, wherein The chemical modification is acetylation, and the degree of acetylation is 0.5 to 1.
3.
17. The cellulose microfibers according to claim 1, wherein In the determination of the fiber shape automatic analyzer, the following parameters are further satisfied: (iv) among fibers having a fiber length of less than 100 μm, the number frequency of fibers having a fiber length of 20 μm or more and 56 μm or less is 30% or more and 97% or less, and (vi) The fibrillation rate is 5% or less.
18. A method for producing cellulose microfibers, which is the method for producing cellulose microfibers according to any one of claims 1 to 17, wherein: The cellulose microfibers have a halogen content of 250 ppm by mass or less, The method includes the step of fiberizing a cellulose raw material having a halogen content of 300 ppm by mass or less.
19. A fiber-reinforced resin comprising the cellulose microfibers according to any one of claims 1 to 17 and a resin.
20. The fiber-reinforced resin according to claim 19, wherein The resin has a melting point of 200° C. or higher. 21 . The fiber-reinforced resin according to claim 19 , comprising 1 mass % or more of the cellulose fine fibers.
22. A nonwoven fabric comprising the cellulose microfibers according to any one of claims 1 to 17. 23 . The nonwoven fabric according to claim 22 , comprising 50% by mass or more of synthetic fibers having a melting point of 300° C. or less. The nonwoven fabric according to claim 22, comprising 1 mass % or more of the cellulose fine fibers. 25 . A fiber-reinforced resin comprising the nonwoven fabric according to claim 22 and a resin impregnated in the nonwoven fabric.
26. A method for producing a fiber-reinforced resin, comprising: The method comprises the step of hot pressing the nonwoven fabric according to claim 22 to obtain a fiber-reinforced resin, The nonwoven fabric includes synthetic fibers, and the heat pressing is performed at a temperature above the melting point of the synthetic fibers.
27. A wet molded product comprising the cellulose microfibers according to any one of claims 1 to 17.
Citation Information
Patent Citations
Manufacturing method of microfibrilized cellulose / elastomer / resin composite material and manufacturing method of molded article
JP2010031093A
Fiber-reinforced resin composition comprising chemically modified cellulose nanofibers and thermoplastic resin
WO2016148233A1
Fibrous cellulose and production method thereof, and fibrous cellulose composite resin and production method thereof
WO2019230573A1
Nanofiber sheet, process for producing the same, and fiber-reinforced composite material
CN101535567A
Non-coated paper and coated paper
WO2013015323A1